Characteristics and constitutive model of segmented damage and fracture in granite under thermo-hydro-mechanical (THM) condition - Luping Cheng; Chun Wang; Yi Tan; Hao Li; Zonghong Zhou; Yumeng Ren; Juanjuan Li; Taihao Cui (Geothermics, 2026)

Dual-network anionic polysaccharide films: pH-induced negative charge loading enhances film performance - Xiao Liu; Zhi Cheng; Menghan Zhong; Shixiao Zhang; Qiping Zhan; Xiao Chen; Qiuhui Hu; Yinglin Tan; Liyan Zhao (Food Hydrocolloids, 2026)

A process of microwave pyrolysis treatment of amidoxime functionalized fiber and enrichment of uranium for uranium extraction from seawater - Shen Zhang; Wencai Cheng; Junwen Tan; Benyao Yu; Tianjun Li; Congcong Ding; Xirui Lu; Jun Wen; Hao Li (Desalination, 2026)

Engineered lipase enables selective hydrolysis of palmitic over oleic acyl chains at a two‑phase microfluidic interface - Jin-Zheng Wang; Lu Tan; Cheng-Kun Wu; Xin-Ying Wang; Kheng Lim Goh; Richard Ansah Herman; Shuai You; Sheng Sheng; Fu-An Wu; Jun Wang (Bioresource Technology, 2026)

A kinetic-based framework for the selection of in vitro osteoarthritis models: integrating temporal dynamics of inflammatory inducers - Guoyun Cheng; Nur Atheeqah-Hamzah; Xiaoqian Liu; Fengyang Lv; Kwong Weng Loh; Atiqah Aziz; Han Ling Tan; Kamarul Tunku (Molecular Biology Reports, 2026)

Study of dynamic characteristics of nitrogen pressurizer under ocean condition with system code and CFD code coupled analysis method - Lei Cheng; Minyang Gui; Junfeng Li; Minglong Yue; Pu Tan; Bin Yang; Jiming Wen; Sichao Tan; Ruifeng Tian (Annals of Nuclear Energy, 2026)

From substrate limitation to competition control: straw input regulates sulfate-mediated suppression of methanogenesis in paddy soils - Tianzhuo Cheng; Wankun Pan; Wolfgang Wanek; Che Tan; Roland Bol; Yongchao Liang; Qingxu Ma (Soil Biology and Biochemistry, 2026)

Short-time high-intensity ultrasound directly induces soy protein isolate-glucono-δ-lactone gels - Xi Cheng; Tan Hu; Hongchen Su; Yuxin Xie; Yuan Yuan; Hao Hu (Food Hydrocolloids, 2026)

Trace element concentrations and tissue distribution in cetaceans from different ecological groups in Chinese waters - Yaoyao Shi; Hao Cheng; Fanyu Lin; Yang Liu; Cai Lin; Yi Liu; Yan Tan; Qianhui Zeng; Yuke Zhang; Xianyan Wang; Liyuan Zhao (Environmental Pollution, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Constructing hollow tubular nanoreactors with nanoconfined Co sites for ultrafast water purification in Fenton-like reactions - Xi Wang; Yuheng Yao; Yi Yang; Ke Zhu; Song Yang; Huige Cheng; Jianli Huang; Xiao Tan; Kai Yan (Chemical Engineering Journal, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Adhesin gene overexpression stimulates biofilm formation and catalytic performance in recombinant Escherichia coli - Hai-Fei Zhang; Cheng-Hai Yan; Fang-Hui Chen; Ding Wang; Min Tan; Yan Xu; Richard Ansah Herman; Jun Wang (Bioresource Technology, 2026)

BmK IT2 suppresses proliferation while differentially modulates migration and invasion of neural tumor cells: Association with down-regulation of functional VGSCs and transcriptional reprogramming - Shiqi Jing; Jishuai Wang; Shuai Cheng; Qingqing Ma; Jie Tao; Hongjie Wang; Yonghua Ji; Zhiyong Tan; You Zhou (Toxicon, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

Sodium dehydroacetate reduces postharvest banana decay caused by Lasiodiplodia theobromae by disrupting pathogen cell membrane and inducing fruit resistance - Chenxiang Li; Ruogu Cheng; Meirou Zhuang; Nengguo Tao; Xiaoli Tan; Jianye Chen (Postharvest Biology and Technology, 2026)

PpPRE1 and PpPRE2 mediate gibberellin-induced internode elongation by regulating brassinosteroid biosynthesis in peach - Huanbing Lu; Mengmeng Zhang; Ning Liu; Bo Zhao; Jun Cheng; Bin Tan; Xianbo Zheng; Wei Wang; Xia Ye; Haipeng Zhang; Xiaobei Wang; Zhiqian Li; et al. (Plant Science, 2026)

Discovery of swertimusins A‒D: Four pairs of rearranged nor-secoiridoid derivatives with a hexahydrofuro[2,3-b]furan ring from Swertia mussotii - Xue Cheng; Qi-Feng Zhang; Rui-Kang Tan; Wen-Di Wang; Yu-Rui Dou; Jia-Yi Wei; Ke-Xun She; Xiao-Feng He (Phytochemistry, 2026)

Vane-roller separation and impact analysis for rotary compressors via tribo-dynamics modeling and experimental validation - Liu Wang; Shupeng Tan; Zhaonan Liu; Chaoran Zhou; Dongliang Liu; Shuai Cheng; Xianghui Meng (International Journal of Refrigeration, 2026)

Error-calibrated sensing: ratiometric biosensor for carcinogenic formaldehyde in food safety monitoring - Catarina Meliana; Michelle Tien Tien Tan; Hwei-San Loh; Cheng Heng Pang; Sze Shin Low (Food Chemistry, 2026)

A graded MDA-equivalent dietary challenge disrupts intestinal homeostasis and compromises flesh quality in hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Tao Cheng; Cong Peng; Shiwei Xie; Shuyan Chi; Beiping Tan; Junming Deng (Food Bioscience, 2026)

Research progress on the extraction, purification, biological activity, and applications of polygonatum polysaccharides - Yan Chen; Fengyi Wei; Yurui Chen; Yinping Li; Zhen Tan; Shajie Luo; Cheng Peng (Food Bioscience, 2026)

Integrating the machine learning framework to decipher ozone control strategies in coastal regions: From seasonal management to source interaction effects - Yan Tan; Yujia Zhang; Fangxiao Du; Yifan Wang; Likun Xue; Yi Chen; Linyang Zhang; Zizhen Ma; Shun-cheng Lee; Yu Huang (Environmental Pollution, 2026)

Metagenomic insights into Thermus-mediated sulfur oxidation, nitrogen cycling, and thermoadaptation in thermophilic autotrophic denitrification bioreactors - Yuan-Yuan Xu; Xin Tan; Cheng-Cheng Dang; Zhi-Cheng Zhao; Rui Fang; Liang Fan; Nan-Qi Ren; Guo-Jun Xie; Yi-Ning Wu (Bioresource Technology, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Long-term cognitive enrichment research provides insight into the change of dolphins' social organisation - Eszter MATRAI; Shaw Ting KWOK; Iris Ziying TAN; Keith CHENG; Ákos POGÁNY; Paolo MARTELLI (Applied Animal Behaviour Science, 2026)

Shaking table test of a novel slope-type sliding pendulum isolation system for seismic protection of electrical equipment - Wanchen Meng; Liang Cheng; Yanhui Liu; Wenzhi Zheng; Ping Tan; Fubao Guo (Soil Dynamics and Earthquake Engineering, 2026)

Fluorine migration, solidification, and secondary release mechanisms during high-value utilization of spent carbon cathode and bulk solid wastes - Wang Yongfa; Zhu Jiajing; Zheng Yongxing; Hu Jianhang; Li Kongzhai; Tan Cheng; Su Ruichun; Yu Yong; Wang Hua (Journal of Hazardous Materials, 2026)

Research progress on the biological activity and applications of gamma-aminobutyric acid - Zhen Tan; Qiuju Dai; Li Shen; Yu Lei; Fengyi Wei; Fajian Ren; Sheng Hu; Yan Chen; Yafei Du; Cheng Peng (Food Research International, 2026)

High internal-phase Pickering emulsions stabilized by whole egg liquid and its application in 3D printing - Min Wang; Qing Lv; Feng Wang; Mingqian Tan; Haitao Wang; Shasha Cheng (Food and Bioproducts Processing, 2026)

Tuning interfacial sulfur vacancy level of ZnIn2S4 for boosting photocatalytic water purification - Peng-Peng Duan; Yong-Sheng Tan; Heng-Heng Guo; Zhi-Cheng Pan; Ya-Meng Dong; Yun-long Wei; Qi-Nian Wang; Xing Zhang (Environmental Research, 2026)

Melatonin breaks the superoxide-driven autocatalytic loop to achieve UV-stable SnPb perovskite solar cells - Sirui Han; Mingzhe Zhu; Jiakang Zhang; He Sun; Cheng Peng; Wei Tan; Siyu Song; Ruotong Kang; Chenyang Xia; Zhongmin Zhou (Chemical Engineering Journal, 2026)

FcRn-hitchhiking BSA-galactose nanoparticles for liver-targeted delivery of astaxanthin in non-alcoholic fatty liver - Ruojing Liu; Hang Xu; Huihui Wang; Kexin Xia; Shasha Cheng; Yukun Song; Mingqian Tan (Chemical Engineering Journal, 2026)

Coordination-driven self-assembly of cerium-baicalein nanozyme promotes spinal cord injury repairing by simultaneously scavenging mitochondrial ROS and reprogramming macrophage polarization - Zhefan Xie; Cheng Peng; Xiaofeng Li; Yuqi Zhao; Shenghang Liu; Xuenian Ye; Yuxue Wang; Wenchong Tan; Huimin Hu; Jianqiang Li; Yanming Ma; Chunlai Fu (Chemical Engineering Journal, 2026)

Geochemical and hydrological controls on aragonite versus calcite precipitation in speleothems and paleoclimatic implications - Rui Zhang; Haiwei Zhang; Christoph Spötl; Carlos Pérez-Mejías; Zixin Guan; Heather Stoll; Yanjun Cai; Liangcheng Tan; Fudong Wang; Xunlin Yang; Yan Yang; Lijuan Sha; et al. (Chemical Geology, 2026)

Pyrolysis kinetics and mechanism study of walnut shell via Asym2sig deconvolution, Sestak-Berggren reconstruction, and multi-dimensional product analysis - Yuhan Wang; Chaowei Ma; Jianhang Hu; Yong Yu; Cheng Tan; Yuanyuan Duan; Hua Wang (Bioresource Technology, 2026)

A dynamic point-association graph method for surface settlement prediction in subway foundation pits: application to Daqiao Station - Tao Kong; Zhen-hua Yang; Qing Tan; Zhao-cheng Liu; Ke Liu; Chuan-dong Yao; Zhen-long Xue; Yu-heng Li (Applied Geophysics, 2026)

Early Fibroblast Remodeling Associated with Lung Tissue Preservation After FLASH Irradiation - Caihui Li; Luhao Tan; Qixiang Liu; Zhihui Li; Menghua Li; Xuefeng Yang; Guofu Dong; Cheng Quan; Jie Ping; Changzhen Wang; Hao Lu (Phenomics, 2026)

Inflammatory Signatures of Tinnitus in Patients and Mice - Shuai Cheng; Qi Zhao; Guiyuan Rong; Shichu Sun; Hongjie Wang; Zhiyong Tan; Yonghua Ji; You Zhou (Neuroscience Bulletin, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Nonlinear and spatially heterogeneous effects of the built environment on urban flood resilience: An interpretable spatially weighted machine learning framework - Cheng Tan; Xiaoyang Liu; Zhigang Li (Sustainable Cities and Society, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Using network pharmacology and structural biology to elucidate the molecular mechanism by which Macrolactin A protects against aphids - Min Cheng; Aoping Tan; Ruyi Ma; Shibo Yang; Ziang Zhou; Kangbo Zhao; Mengqian Guo; Ting Guo; Wenjun Wu; Hong Xu; Shaopeng Wei; Nana Wang; et al. (Pesticide Biochemistry and Physiology, 2026)

Enhancing understanding of vegetation responses to flash droughts: the need for high-temporal-resolution monitoring data - Zixuan Qi; Yuchen Ye; Yanpeng Cai; Chaoxia Yuan; Qian Tan; Lian Sun; Zhifeng Yang; Guanhui Cheng (Journal of Hydrology, 2026)

Two new species of Hamacanthidae (Porifera) from the abyssal nodule fields of the Clarion-Clipperton Zone (Pacific Ocean) - Swee-Cheng Lim; Koh-Siang Tan (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Triboelectric-motorized electromagnetic conversion enables frequency upconversion and impedance reduction for low-frequency mechanical energy harvesting - Tingyu Wang; Lihua Wang; Ai Chen; Bocheng Chen; Liming Tan; Junyin Cheng; Fan Xu; Huiyuan Wu; Kaixian Li; Yilan Zhang; Yuqing Wen; Haixuan Gan; et al. (Chemical Engineering Journal, 2026)

Electrospinning-constructed polysaccharide-based multilayer nanofiber composite membrane for bridging hemostasis and tissue repair - Ruiyi Tan; Zhou Wen; Xinying He; Bitao Lu; Enling Hu; Ruiqi Xie; Guangqian Lan; Cuibin Guo; Chunzu Cheng; Bowen Cheng; Fei Lu (Carbohydrate Polymers, 2026)

Streptococcus suis in Asia: epidemiology, transmission and zoonotic risk at the animal–human interface - Chew Yee Tan; Peck Toung Ooi; Michelle Wai Cheng Fong; Chee Yien Lee; Jia Wei Lee (Veterinary Research Communications, 2026)

A new flavonol glycoside isolated from the stems and leaves of Astragalus membranaceus - Jia-Xin Zhao; Yun Zang; Pei Li; Jia-Ning Zhang; Si-Qi Yang; Hui-Feng Li; Yan Wang; Jin-Yan Tan; Ying-Li Wang; Yan-Gang Cheng (Natural Product Research, 2026)

Debris flow volume prediction model based on a hybrid BP neural network optimized by adaptive weighted average algorithm with spiral search enhancement - Xi Wang; Li Li; Yue Qiang; Chen Cheng; Xinyi Tan; Nanxi Chen; Xing Wang (Acta Geophysica, 2026)

First report of Fusarium asiaticum causing stem rot on pitaya in China - Dan Lei; Xueying Shang; Zhu Li; Kun Guo; Ziqin Bai; Geng Liu; Qing Tan; Jieyu Li; Chenlan Li; Li Cheng; Hui Luo (Crop Protection, 2026)

Collapse of underground cavities: initiated by cyclic pipeline leakage and triggered by rainfall infiltration - Zi-Ye Wang; Yong Tan; Jun-Cheng Liu (Tunnelling and Underground Space Technology, 2026)

Vegetation of exotic fast-growing species Sonneratia apetala increases the potential of methylmercury production: Insights from carbon bioavailability, microbial metabolism and mercury methylators - Xiaoxin Chen; Qiao-Guo Tan; Ke Pan; Anwen Xiao; Hao Cheng; Xun Wang (Journal of Hazardous Materials, 2026)

Petrogenesis and element enrichment of Miocene leucogranite in the Chongshan Shear Zone, SW China: Constraints from geochronology, geochemistry, and Hf-Sr-Nd isotopes - Liang Huang; Ye Zhou; Zai-Bo Sun; Feng Zhao; Yan Dao; Su-mei Tian; Shu-Cheng Tan; Xue-long Liu; Shi-tao Zhang; Jia-Xi Zhou (Journal of Asian Earth Sciences, 2026)

Effects of heat treatment on the characteristics of low-molecular-weight oyster peptides (LOPs) W1/O/W2 double emulsions: Physicochemical, interfacial, and rheological properties - Xiaolin Guo; Wanqi Chen; Wenhong Cao; Haisheng Lin; Zhongqin Chen; Jialong Gao; Guoping Zhu; Mingtang Tan; Ming Cheng; Huina Zheng (Food Chemistry, 2026)

Genetic basis of cadmium accumulation and tolerance in maize seedlings uncovered through integrated linkage mapping and transcriptome analysis - Mutian Gao; Haibin Tang; Zhijie Liao; Yanmei Xiao; Wei Jia; Yong Chen; Hui Tan; Liusheng Zhong; Zijing Tang; Hongbing Luo; Zhili Wang; Cheng Huang (Theoretical and Applied Genetics, 2026)

SETD2 Improves Endothelial Function and Angiogenesis in Diabetic Hindlimb Ischemia Via Activating ANGPT2-PI3K/AKT Pathway - Langtao Wang; Qing Wang; Jiaxing Duan; Yu Tan; Yuanyuan Liu; Shuai Hu; Cheng Wang; Chen Yang; Yanzhu Long; Jinxuan Wang; Tao Yu; Tianhu Liu; et al. (Cardiovascular Toxicology, 2026)

Facile preparation of new bidentate quaternary ammonium-type stationary phase for the separation of versatile analytes in hydrophilic interaction liquid chromatography - Xiao-dong Cheng; Kai-feng Tan; Cai-yong Lin; Yun-ping Li; Xue-xin Dai (Analytica Chimica Acta, 2026)

Simulation-Based Maritime Scheduling Optimization for Bidirectional Ship Flow in Multi-Chamber Lock Systems: Incorporating Chamber Operations for Efficient Management - Nini Zhang; Xin Li; Wen Xie; Sudong Xu; Weikai Tan; Cheng Cheng; Ran Yan (Journal of Marine Science and Engineering, 2026)
This paper addresses the bidirectional multi-chamber lock scheduling problem by formulating a multi-objective mixed-integer linear programming (MILP) model that simultaneously minimizes average ship waiting time and maximizes chamber utilization. A tailored adaptive large neighborhood search (ALNS) algorithm is developed specifically based on the principle of the destruction and reconstruction of solutions. The algorithm efficacy is validated using the real-word data from Huai’an Lock of the Subei canal. The scheduling rules and parameters are defined from practical operation records. Simulation results demonstrate that the ALNS-based optimization significantly improves lock performance with average chamber utilization increasing by 12.98% and waiting time decreasing by 44.40%. Sensitivity analyses on objective weights further confirm the robustness of the proposed method. Benchmark comparisons with a greedy heuristic, genetic algorithm (GA), and particle swarm optimization (PSO) highlight the effectiveness and computational efficiency of ALNS. This study further explores a threshold-based directional control strategy, showing that relaxing strict alternating-direction rules under asymmetric traffic demand can improve efficiency. The findings provide practical insights for lock scheduling, offering decision support for lock authorities in designing adaptive scheduling and directional control policies.

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

Moisture-Dependent Evolution of Creep and Permeability in Argillaceous Siltstone During Shear–Compression Transition - Bo Hu; Jiajun Ran; Qiaohai Tan; Xianghe Ye; Yugang Cheng; Xuefu Zhang; Zhiqiang Lv; Mostafa Sharifzadeh; Mi Nie; Jinzhou Tang (Rock Mechanics and Rock Engineering, 2026)

Chloride ions accelerated the removal of naproxen in Cu(II)/peracetic acid system: Promotion of copper cycling through the formation of copper-chloride complexes - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li (Water Research, 2026)

PpZAT10 inhibits PpTST1 expression to regulate sugar accumulation in peach (Prunus persica) fruit - Qinqi Liu; Beibei Feng; Liuqing Han; Dongsheng Wang; Kexin Liu; Xiaobei Wang; Nan Hou; Lei Wang; Xianbo Zheng; Xiaodong Lian; Jun Cheng; Wei Wang; et al. (Plant Science, 2026)

Enhanced removal of organic pollutants and effective suppression of chlorinated/brominated by-products in heat/peroxymonosulfate system by adding sodium percarbonate - Yao Huang; Chenyu Tang; Bingyu Lu; Jianhang Li; Lukai Zhuang; Minfeng Wang; Haoqiang Tan; Qingfeng Cheng; Qingsong Li; Bo Sun; Jing Zou (Journal of Environmental Chemical Engineering, 2026)

Remediation effects of humic acid and hydroxyapatite on cadmium-contaminated alkaline wheat soil and its microbial community response: A field trial - Yineng Lu; Haoyu Yue; Rong Tan; Zihao Ding; Geng Chen; Shuangting Zhang; Ziyi Li; Ram Proshad; Xiuwen Cheng; Zhuanjun Zhao (Journal of Environmental Sciences, 2026)

Litsea cubeba essential oil mitigates postharvest blueberry decay by damaging the cell barrier of Penicillium crustosum - Ruogu Cheng; Chunxiu Wan; Ziyu Wang; Jiao Hu; Xiumei Chen; Nengguo Tao; Xiaoli Tan (International Journal of Food Microbiology, 2026)

Thermal effects induced by high-intensity ultrasound on the formation of whey protein isolate fibrils - Yuxin Zhao; Tan Hu; Xi Cheng; Yuxin Xie; Arsalan Khan; Youyou Lv; Jingyao Chen; Hao Hu (Food Research International, 2026)

Comparison of three kinds of models for detecting tartrazine in tea powder by synchronous fluorescence spectroscopy combined with chemometrics - Hui Chen; Chao Tan; Bin Cheng; Zan Lin (Food Chemistry, 2026)

Green immobilization of lipase based on a catechol-polyamine coating for efficient synthesis of octenyl succinic anhydride starch - Xiaolu Liu; Zhenyu Hu; Yao Li; Bozhi Tan; Jing Tian; Cong Wang; Sheng Cheng; Xu Fei (Food Chemistry, 2026)

Development of iron-crosslinked sodium alginate/carboxymethyl cellulose films functionalized with zeolite imidazolate framework-L for salmon preservation - Yuanda Sun; Shiyu Jia; Shasha Cheng; Wentao Su; Haitao Wang; Mingqian Tan (Food Hydrocolloids, 2026)

Quantifying the synergies between air pollutant reduction and CO2 mitigation in the transportation sector of Guangdong, China - Jiayi Tan; Yun Zhu; Ji-cheng Jang; Zhaoxin Dong; Shicheng Long; Jia Xing; Bin Zhao; Bingyao Zhang; Mengmeng Zhang; Xuehao Yan; Zhiqiang You (Environmental Pollution, 2026)

PpBRC1 negatively regulates branching via modulating GA signal transduction gene PpGID1b in peach (Prunus persica) - Yulu Wu; Yajia Zhang; Junjie Zhang; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Nan Hou; Xianbo Zheng; Jun Cheng; Wei Wang; Langlang Zhang; Xia Ye; et al. (Plant Cell Reports, 2026)

Taxonomy and Phylogeny of the Little-Known Ciliate Genus Cyclotrichium: With Special Reference to Two New Species - Zijun Cheng; Bowen Ye; Gang Li; Xiping Lian; Yehui Tan; Xiaofeng Lin; Weiwei Liu (Journal of Ocean University of China, 2026)

Investigation on agglomerated debris formation during fuel–coolant interactions with multiple series of experiments - Shaojie Tan; Songbai Cheng; Yanan Zhao (Annals of Nuclear Energy, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

The efficient treatment of landfill leachate using a novel osmotic microbial fuel cell system employing forward osmosis membrane featuring proton-conducting medium - Enling Tian; Fengjun Yin; Cheng Song; Ying Zhao; Hao Tan; Fuqing Zhao; Hong Liu (Water Research, 2026)

Plant bioavailable phosphorus content in animal manure- and sewage sludge-based char and ash: Effect of thermal treatment temperature and condition - Xuan Luo; Wei Ding; Adi Radian; Ling Tan; Yukun Sheng; Cheng Li; Zhenyu Wu; Keke Xiao (Waste Management, 2026)

Five novel Haloarchaeobius species from coastal tidal flats and saline-alkali soil in China using integrated culture-dependent and culture-independent approaches - Guo-Liang Xu; Shun Tan; Yao Hu; Mu Cheng; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Cold exposure impairs the muscle growth-promoting effect of nighttime-restricted feeding by desynchronizing mitochondrial energy supply rhythm in rabbits - Yuan-Yuan Tan; Xiao-Han Ma; Chun-Hua Shan; Shuai He; Quan-Gang Wang; Meng-Qi Zhu; Jian-Xiang Cheng; Ke-Hao Zhang; Lei Zhang; Zhong-Ying Liu; Yao Guo; Zhong-Hong Wu (Journal of Thermal Biology, 2026)

Unintentional Weight Loss as a Predictor of Adverse Prognosis in Older Adults With Chronic Obstructive Pulmonary Disease in the Intensive Care Unit: A Retrospective Cohort Study - Hongtao Cheng; Yonglan Tang; Shanyuan Tan; Simeng Song; Jia-Ming Xiong; Xiaxuan Huang; Yitong Ling; Zichen Wang; Fuling Zhou; Jun Lyu (Journal of the Academy of Nutrition and Dietetics, 2026)

Effects of digital economy-driven Chinese-style agricultural modernisation--based on analysis of mediating effects and spatial spillovers - Pan Hong; Tan Shuang; Liu Mingyu; Ying Xie; Suwan (Cheng) Long (Journal of Rural Studies, 2026)

Assessing the fidelity of clay-size lithium isotopes as chemical-weathering tracers in detrital sedimentary successions - Xia Zhang; Chunming Lin; Robert W. Dalrymple; Cheng Cao; Daidu Fan; Guyue Tan; Xin Li (Geochimica et Cosmochimica Acta, 2026)

Innovative silk protein peptide-modified soy protein isolate-xanthan gum films for food packaging - Meixia Zheng; Shaojie Zhong; Cheng Lin; Jianfu Chen; Yangyang Liu; Kok Bing Tan; Yujing Zhu (Food Chemistry, 2026)

Pickering emulsion stabilized by whole Basa fish slurry as fat replacer in fish cakes: Enhanced the water-holding capacity and textural properties - Qing Lv; Min Wang; Feng Wang; Mingqian Tan; Wentao Su; Haitao Wang; Shasha Cheng (Food and Bioproducts Processing, 2026)

Impact of NOx titration on nighttime isoprene in coastal South China: Preserving ozone precursors via suppressed oxidation - Yan Tan; Yujia Zhang; Yifan Wang; Yi Chen; Tao Wang; Zizhen Ma; Linyang Zhang; Meng Wang; Shun-cheng Lee (Environmental Research, 2026)

Effects of Iodine Nutritional Status on Thyroid Proliferation of SD Rat - Junshuai Cheng; Zifan Gao; Yuan Zhao; Qiuyi Song; Yu Wang; Tingting Xu; Kai Lv; Yanlei Li; Wanqi Zhang; Juan Liu; Long Tan (Biological Trace Element Research, 2026)

Spatiotemporal distribution, source apportionment, and ecological risks of polycyclic aromatic hydrocarbons in surface water of the Southern Ocean - Tao Yang; Linlin Shi; Saizhang Tan; Bangping Deng; Yu Ke; Shengming Cheng; Yubin Li; Shuangcheng Zhang; Jingwei Wu; Lichen Zhao; Jun Shi (Frontiers in Marine Science, 2026)
In Antarctica, low temperatures favor the trapping and deposition of polycyclic aromatic hydrocarbons (PAHs), whereas the biogeochemical cycling of PAHs on the Southern Ocean adjacent to Antarctica is highly sensitive to climate change. However, very little environmental and ecological information is available on interannual PAHs variations in the surface of the Southern Ocean. From 2022 to 2024, we employed the 38 th , 39 th , and 40 th Chinese National Antarctic Research Expeditions (CHINARE) to collect surface water samples and conduct analyses of the spatio-temporal distribution patterns, source apportionment, and probabilistic ecological risk assessment of the 16 USEPA priority PAHs. We found that ∑PAH concentration in the study area ranged from 427 to 5782 pg/L, with median values of 1795, 1736, and 2559 pg/L for the 38 th , 39 th , and 40 th expeditions, respectively, showing a latitudinal gradient pattern of higher concentrations at lower latitudes and lower concentrations at higher latitudes. A significant concentration rebound was observed in the 40th expedition. Integrated analysis using molecular diagnostic ratios, PCA, and PMF revealed that this rebound was driven by a distinct “dual-pressure pattern”: intensified logistical traffic emissions (combustion sources) and the persistent release of fresh, unweathered PAHs. Source apportionment indicated an evolutionary trend from mixed petrogenic and ship-related liquid fuel combustion (38th) to episodic fresh local inputs (39th), culminating in the complex superposition of sources in the 40th survey. Probabilistic risk assessment using Monte Carlo simulations confirmed that acute risks to plankton remain low (the 95th percentile of ∑RQ MPC was 0.077); However, a structural shift towards hydrophobic high-molecular-weight PAHs (increasing to ~18% in 2024) signals a rising hidden potential for biomagnification in keystone species like Euphausia superba . These findings provide a critical scientific baseline for identifying pollution sources and supporting Antarctic ecosystem management under changing environmental conditions.

Enhanced Swin-Transformer model for real-time assessment of overall shield machine cutterhead wear - Haoyu Li; Shifan Qiao; Daolong Chen; Junkun Tan; Baoquan Cheng (Tunnelling and Underground Space Technology, 2026)

Corrigendum to “Utilization of current pyrolysis technology to convert biomass and manure waste into biochar for soil remediation: A review” [Sci. Total Environ., 864 (2023), 160990] - Shimeng Tan; Guoying Zhou; Quan Yang; Shengbo Ge; Junang Liu; Yoke Wang Cheng; Peter Nai Yuh Yek; Wan Adibah Wan Mahari; Sieng Huat Kong; Jo-Shu Chang; Christian Sonne; William Woei Fong Chong; et al. (Science of The Total Environment, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Fungal diversity drives soil health and agricultural sustainability in black soils - Teng Yang; Xu Liu; Leho Tedersoo; Xiyuan Xu; Guifeng Gao; Kunkun Fan; Luyao Song; Dan Zhao; Yuying Ma; Li Nie; Di Wu; Jingjing Liu; et al. (Science Bulletin, 2026)

Thiamethoxam resistance evolution, fitness cost, and transcriptome-based functional insights in the whitefly Bemisia tabaci - Jing Yang; Qimei Tan; Xuegao Wei; Jinjin Liang; Buli Fu; Cheng Yin; Youjun Zhang; Xin Yang (Pesticide Biochemistry and Physiology, 2026)

Sparteine-type alkaloids with anti-tomato spotted wilt virus from the seeds of Lupinus angustifolius L. - Jian-Guo Tan; Cheng-Feng Liu; Li Wang; Xing-Ya Wu; Li-Hua Zhao; Xiao-Jiang Hao; Zhan-Xing Hu (Pesticide Biochemistry and Physiology, 2026)

Geochemical transformation of ferrihydrite: A review on mechanisms, effects of coexisting molecules and environmental implications - Yupeng YAN; Cheng WANG; Muammar MANSOR; Rui JIANG; Xiaoming WANG; Qin ZHANG; Xionghan FENG; Wenfeng TAN; Andreas KAPPLER; Biao WAN (Pedosphere, 2026)

Adsorption-based strategies for the removal of complex pollutants in petrochemical wastewater: A critical review - Xuri Wu; Mengting Cheng; Hao Wang; Feng Tan (Journal of Water Process Engineering, 2026)

How to measure copresent ammonia and inorganic chloramines reliably: Some fundamental issues and novel solutions - Xiao Li; Longjie Cheng; Sen Lu; Yuheng Chen; Xiaoyu Tan; Bin Xu; Baiyang Chen (Journal of Hazardous Materials, 2026)

Al-doped α-MnO2 for low-temperature catalytic oxidation of formaldehyde - Zhengnan Lin; Zhao Zheng; Junchen Li; Cheng Zhang; Qingyan Fang; Peng Tan; Gang Chen (Journal of Environmental Chemical Engineering, 2026)

Thermal effects induced by high-intensity ultrasound cavitation on soy protein isolate: Structural modulations and gelation behaviors - Yuan Yuan; Tan Hu; Xi Cheng; Hongchen Su; Yuxin Xie; Hao Hu (Food Hydrocolloids, 2026)

Achieving 17.65% efficiency in organic solar cells by neutral linker engineering in dimerized small-molecule acceptors - Jianan Niu; Xue Zhou; Mingxin Sun; Fuzhen Bi; Guoqing Lin; Cheng Sun; Tan Wang; Mingliang Sun; Shuguang Wen; Xichang Bao (Chemical Engineering Journal, 2026)

Metagenomic sequencing reveals high reproducibility of human donor microbiota transplanted into germ-free mice via lower gut route - Yapeng Yang; Xiang Tan; Zeyue Zhang; Lifeng Liang; Zhifeng Wu; Jinhui He; Yuqing Wang; Miaomiao Dong; Jixia Zheng; Hang Zhang; Shuaifei Feng; Wei Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Pharmacological effects of cardamonin in metabolic diseases: a review on preclinical studies - Aizhi Zhang; AbdulRahman Muthanna; Yu Zhao Lee; Xuan Xin Yew; Rieyshmondraj Selvanathan; Zuo Shan Reuel Gan; Ji Wei Tan; Yu-Cheng Ho; Ming Tatt Lee; Chau Ling Tham (Inflammopharmacology, 2026)

MnO2-resistant ABTS spectrophotometry for trace permanganate - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Xuewei Yu; Bo Sun; Zhongda Yan; Haoqiang Tan; Qingfeng Cheng; Jun Ma (ENGINEERING Environment, 2026)

A nonlinear fractional-order damage creep model for yellow mudstone and its validation in tunnel deformation analysis - Qiaohai Tan; Bo Hu; Libiao Liu; Yugang Cheng; Mostafa Sharifzadeh; Mi Nie; Tao Zhang; Wenbin Guo; Liang Cheng (Bulletin of Engineering Geology and the Environment, 2026)

Altered Oceanic Crust Source for the Alkaline Rocks with Superchondritic Nb/Ta Ratios Due to the Steep Subduction - Xu Zhao; Ning-Bo Li; He-Cai Niu; Shu-Cheng Tan (Journal of Earth Science, 2026)

Orchestrating Ovarian Dysfunction- The Role of Programmed Cell Death in PCOS - Yuhua Chen; Di Cheng; Zhongcheng Mo; Yuanjie Xie; Siquan Wen; Yi Tan (Cell Biochemistry and Biophysics, 2026)

Size-dependent effects of polystyrene Nanoplastics on hepatic Immunometabolism and the gut-liver Axis in the Swamp Eel (Monopterus albus) - Mingming Han; Wenzong Zhou; Ji Liang; Aileen Tan Shau-Hwai; Zihan Zhou; Lin Cheng; Jiayuan Liao; Weiwei Huang; Qichen Jiang; Weiwei Lv (Aquaculture, 2026)

Residents’ heterogeneous willingness-to-pay for green roofs revealed via demographic segmentation: A case study in a southern Chinese city - Jiahong Wu; Pan Yang; Guanhui Cheng; Qian Tan (Urban Forestry & Urban Greening, 2026)

Cultivar-dependent effects of arbuscular mycorrhizal (AM) fungal inoculation on fruit quality and native AM fungal community in navel orange - Xin-Ping Tan; Cheng-Zhuo Li; Ying-Ning Zou; An-Qi Lei; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Integrating large language models and machine learning for sustainable electrochemical upgrading of biomass-derived 5-hydroxymethylfurfural to 2,5-bis(hydroxymethyl)furan - Cheng Zeng; Zhichao Tan; Youcai Zhao; Tao Zhou (Process Safety and Environmental Protection, 2026)

ABF-YOLO11: A multi-scale adaptive detection and lightweight recognition model for stored-grain pests - Li Hou; Mingliang Liu; Yanfen Liu; Xiaodong Tan; Chunxiang Cheng; Wentao Sun; Nan Tang (Journal of Stored Products Research, 2026)

Morphology and electronic configuration engineering of CoP as an excellent electrocatalyst for oxygen evolution reaction - Zhao Li; Wenjing Cheng; Chunmei Ni; Xuena Gao; Jianguo Dong; Huiming Yang; Wenyi Tan; Lin Tian (Fuel, 2026)

Floral fragrance in sweet osmanthus majorly repels pollen feeders - Hui-Hui Feng; Cheng-Xi Tan; Shao-Cheng Huang; Shuang-Quan Huang (Science China Life Sciences, 2026)

Removal of polypropylene microplastics from water by microalgae Desmodesmus sp.: Influences, kinetics and mechanisms - Qing Xie; Xiaoai Lin; Lang Tan; Longzao Luo; Shuang Luo; Xiaosong Tian; Qing Cheng; Shao Zhang; Yujing Wang (Algal Research, 2026)

High-resolution seismic data processing based on low-dimensional manifold constraints - Gang-lin Lei; Guang-liang Zhao; Suo Cheng; Yang Tan; Jiang-wei Shang; Ze-lin Li; Zi-lun Xiong; Zhu-kun Wang (Applied Geophysics, 2026)

Reservoir property estimation of interbedded sandstone and shale layers using segmented 3D rock-physics templates - Jing Ba; Xi-Ya Ba; Hong-Jing Dong; Jun-Wei Cheng; Cong Luo; Zhi-Fang Yang; Meng-Qiang Pang; Wen-Hui Tan (Applied Geophysics, 2026)

scMSDA: A Novel Multi-View Fusion Framework for Single-Cell RNA-seq Data Clustering with Semantic and Distribution Alignment - Congcong Jiang; Wenlan Chen; Yanyan Tan; Hai Zhong; Cheng Liang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Effects of different dietary iron sources on growth performance, appetite regulation and intestinal health of yellow catfish Pelteobagrus fulvidraco - Peng-Cheng Xu; Hua Zheng; Nermeen Abu-Elala; Zhi Luo; Chong-Chao Zhong; Hong Yang; Xiao-Ying Tan (Aquaculture, 2026)

Mechanisms of failure and permeability evolution in gas-bearing strata under tunnel-induced stress paths - Jiafeng Tan; Deyi Jiang; Rong Liu; Yi He; Jinyang Fan; Jianyu Liang; Cheng Qian; Hanlin He; Hong Zheng (Transportation Geotechnics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

An operational decision tree strategy optimizing the pairing of receptor model and classification approach in source apportionment of microplastics: Leveraging target source type and complexity - Cong Men; Jiayao Liu; Ke Xiong; Daniel Coulibaly; Nina Yang; Thi Kim Oanh Le; Loi Tan Huynh; The Anh Luu; Zhen Yang; Shikun Cheng; Zifu Li (Journal of Hazardous Materials, 2026)

Mobile MAX-DOAS measurements and source analysis of NO2, HCHO, and HONO during the Chengdu 2023 FISU world university games - Qijin Zhang; Chengzhi Xing; Miao Feng; Yinshuo Ding; Zhongmou Sun; Yikai Li; Haochen Peng; Wei Tan; Zhiguo Zhang; Tianjun Du; Cheng Liu (Journal of Environmental Sciences, 2026)

Self-heating characteristics of rice straw in a 120-L insulated container: Experiments & CFD studies - Mingshuo Cui; Xinke Chen; Yuan Li; Tingting Luo; Qianhua Huang; Qingyan Fang; Peng Tan; Cheng Zhang; Gang Chen; Chungen Yin (Fuel, 2026)

An integrated platform for predicting straw pyrolysis by flash joule heating: Optimizing three-phase product yields and properties using HRF algorithm - Yuanbo Song; Jiawei Tan; Xinnan Zheng; Mengyu Jin; Cheng Hou; Xiaoxia Wang; Yang Shi; Jianfei Zhu; Yalei Zhang; Zheng Shen (Fuel, 2026)

Structural remodeling and enzyme inhibition of coconut pomace dietary fiber via high-pressure homogenization and microfluidization: Evidence for multilevel structure-function mechanism - Shuxian Li; Yaoyao Tan; Xiaoqing Cheng; Anxin Wang; Sixin Liu; Congfa Li (Food Chemistry, 2026)

Films for salmon freshness monitor, prepared with lipophilic soy protein, hydroxypropyl methylcellulose, and octadecenylsuccinic anhydride-modified γ-cyclodextrin-MOF loaded with shikonin - Yuanda Sun; Haibo Xu; Yi Ma; Yingmeng Hou; Shasha Cheng; Mingqian Tan; Jingru Chang; Haitao Wang (Food Hydrocolloids, 2026)

Tunable synthesis of tailored high-energy-density fuels from coal-based fluorene - Bing-Wei Chen; Hua-Jun Zhai; Yan-Cheng Hu; Yan-Hong Tan; Jia Li; Zhilian Wu; Lin Shao; Jing-Pei Cao (Chemical Engineering Journal, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Fine-tuned Ce electron density directs H2O2 activation pathway in industrially employable CeO2 nanozymes for ∼100% specificity and boosted activity in (Bromo)peroxidase mimicking - Tianqi Cheng; Bo Yuan; Chao Zhao; Zicong Tan; Xinyu Wu; Jian Lin Chen; Juan Liu; Yufei Zhao; Hui Wei; Yung-Kang Peng (Chemical Engineering Journal, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Mechanistic analysis of root morphology on shear behavior in root-soil composites using discrete element method (DEM) - Xiang-Hua Song; Yong Tan; Ping Hu; Pan-Pan Cheng; Heng-Lin Xiao (CATENA, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Advancing citrus orchard soil health assessment through an environmental risk screening and multi-dimensional indicator integration framework - Zhenyu Wu; Jiayuan Wang; Yuzhi Zhou; Bao Cheng; Jie Zhang; Chang Chen; Marcelo J. Avena; Wenfeng Tan; Mingxia Wang (Applied Soil Ecology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Spatiotemporal Changes of Ocean Heat Content in the Seas around China - Xu Liu; Licheng Feng; Lijing Cheng; Zhetao Tan; Cuijuan Sui; Chunyang Song (Advances in Atmospheric Sciences, 2026)

Facilitating redox cycles of copper species by peroxydisulfate in the copper-catalyzed Fenton-like system for enhanced oxidation of organic contaminants - Bingyu Lu; Jianying Wu; Chenyu Tang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li; Jun Ma (Water Research, 2026)

Ceritinib–ibuprofen synergistic hepatotoxicity: Insights from real-world data and liver organoid models - Shiyi Tan; Yun Yang; Li Ma; Xulei Zuo; Jianhua Rao; Yuepu Pu; Feng Cheng; Zhongze Gu; Juan Zhang (Toxicology, 2026)

The biomarker signatures in the Niujiaotang sulfide ore field: Exploring the role of organic matter in ore formation - Yong Cheng; Jia-Xi Zhou; Yuzhao Hu; Saihua Xu; Shengbao Shi; Yiming Wen; Qi Nie; Ye Zhou; Kai Luo; Xiaolin Tan; Liang Zhou; Yadong Li; et al. (Marine and Petroleum Geology, 2026)

Unveiling the microplastic migration behavior in riverine systems: hydrodynamic impacts on transport and sedimentation - Kaifeng Wang; Quanhong Chen; Qiming Cheng; Yuqing Tan; Wenyu Xiao; Yihong Su; Fei Liu; Hongjun Xiao; Ye Rao; Zhen Liu; Yao Chen (Journal of Hydrology, 2026)

A sustainable strategy for efficient arsenic reduction, detoxification, and environmental assessment during the high-value utilization of multi-metallic tailings - Du Wei; Li Kongzhai; Yu Yong; Tan Cheng; Zheng Yongxing; Wang Xun; Hu Jianhang; Wang Hua (Journal of Hazardous Materials, 2026)

Programmable oil/water separation performance of wood-based membranes via structural anisotropy and delignification - Kaiwen Chen; Cheng Hao; Luyao Chen; Fengze Sun; Yujing Tan; Wenjuan Zhao; Hui Peng; Tianyi Zhan; Jianxiong Lyu; Ning Yan (Journal of Cleaner Production, 2026)

Advancing dam health monitoring with high-resolution Fiber-optic Distributed Acoustic Sensing - Feng Cheng; Jianbo Guan; Jianghai Xia; Xinmin Zhu; Jiemin Fu; Xuhui Yu; Lei Tan; Zuyuan He (Engineering Geology, 2026)

Financing climate-resilient infrastructure through long-term green bond - Jianxin Guo; Xianchun Tan; Yonglong Cheng; Xiangyin Chen (Ecological Economics, 2026)

Titanium suboxide-heteropoly blue self-assembled superlattices for solar photothermal high-efficiency water evaporation - Sihang Cheng; Cheng Sun; Cuimei Liu; Yanchun Liu; Xiuli Wang; Huaqiao Tan; Yangguang Li (Desalination, 2026)

Goose feather-inspired soy protein isolate films incorporating L-Cys@Cu nanofibers for sustainable packaging - Yuanda Sun; Keying Mou; Liubing Bai; Shasha Cheng; Wentao Su; Haitao Wang; Mingqian Tan (Chemical Engineering Journal, 2026)

Efficient nitrogen removal in nitrite-dependent anaerobic methane oxidation biofilms and associated nitrogen and sulfur transformation pathways - Zhi-Cheng Zhao; Guo-Jun Xie; Xin Tan; Lu-Yao Liu; Cheng-Cheng Dang; Xiao-Wei Wang; Xuan Wang; Xin-Yu Wan; Ya-Song Chen; Wan Sun; Nan-Qi Ren (Chemical Engineering Journal, 2026)

Nanoscale steric-engineering enables synergistic ion confinement and transport for large-strain electrochemical actuation - Yang Li; Hao Li; Cheng Yang; Zheng Zhang; Bo Zhao; Yueting Pu; Zhixiang Guo; Xiaoyan Li; Bonan Hao; Haoran Li; Fangju Tao; Shuangyi Li; et al. (Chemical Engineering Journal, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Flexible-rigid coupling configuration for advanced energy-sensing integrated microsystems - Chang-Liu He; Yao Tan; Hao Zheng; Cheng Tu; Xin-Ran Zhang; Dong-Ming Fang; Xu Zeng; Xiao-Sheng Zhang (Chemical Engineering Journal, 2026)

Metabolic engineering of Escherichia coli for highly efficient N-acetylneuraminic acid production - Chao Sun; Jinhang Yi; Ying Zhang; Xin Chen; Zhanpeng Cheng; Zhengjie Hou; Miao Tan; Junzhe Gao; Yan Chen; Heyun Wu; Qian Ma; Xixian Xie (Bioresource Technology, 2026)

VKORC1L1 Downregulation Induced Vitamin K Cycle Disorder Exacerbates Neuronal Ferroptosis After Spinal Cord Injury - Mingliang Tan; Chao Ma; Lingxia Min; Cheng Cheng; Jilan Wang; Zhou Feng; Jingming Hou (Molecular Neurobiology, 2026)

Geophysical Logging Curve Reconstruction Based on Diff-Mamba Modeling - Guozeng Zhang; Tan Chen; Jialin Chen; Junkai Chen; Cheng Zhang; Ziyan Feng; Cheng Feng (Mathematical Geosciences, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Dual-promoter systems drive plasmid loss via non-translational burden in geraniol-producing E. coli - Jia Zhou; Mengqi Cheng; Shengyang Su; Ziyi Li; Mengxin Lv; Die Hu; Xiaodie Zhang; Yilong Zhou; Hao Shi; Zhongbiao Tan; Ya Xin; Dianlong Wang; et al. (Archives of Microbiology, 2026)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Numerical simulation on creep behavior of argillaceous siltstone under compression-shear coupling and humidity variations - Jiajun Ran; Bo Hu; Qiaohai Tan; Xianghe Ye; Yugang Cheng; Zhiqiang Lv; Mostafa Sharifzadeh; Mi Nie; Jian Mu; Wenbin Guo (Ocean Engineering, 2025)

The role of Cu precursors and reaction mechanism for Cu/IM-5 hierarchical molecular sieve in NH3-SCR - Xinwei You; Zhifang Li; Wenyao Tan; Zhengzhong Cheng; Yuanyuan Ma; Qianhua Song; Jinxing Cui (Journal of Environmental Chemical Engineering, 2025)

Environmental risks and release mechanisms of Cu and As during the slow cooling of molten copper slag: Migrations and toxicity implications - Cao Tan; Cheng Tan; Biao Kuang; Cheng Yang; Yong Yu; Jianhang Hu; Hua Wang (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of high-performance crystalline zirconium phosphate adsorbents and its ammonium ion intercalation mechanism for next-generation hemodialysis - Jingwen Feng; Jianjun Cheng; Jingwen Li; Susu Jia; Feiping Cao; Jiajin Feng; Dapeng Zhou; Jiahua Shi; Choon-Hong Tan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2025)

Prior knowledge-informed semantic segmentation framework for precise glacial lake mapping from multimodal imagery - Huizhi Tan; Liming Jiang; Haoran Liu; Tingbin Zhang; Irene Cheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Associations between PM2.5 components, temperature, and semen quality: Insights from seminal plasma metabolome - Jun-feng Tan; Li-li Huang; Zhong-Hua Lu; Hang-Yu Xiang; Hong Yang; Hai-Xia Zhou; Tian-qing Meng; Cheng-liang Xiong; Yi-Xin Wang; Jie Zhang (Environmental Research, 2025)

Composition optimization of ternary Bi-Sn-In alloy anodes for magnesium ion batteries - Zhenhan Li; Kai Zheng; Meijia Song; Tianyi Kou; Xiangyu Fei; Zhenyu Tan; Guanhua Cheng; Zhonghua Zhang (Chemical Engineering Journal, 2025)

LNP targeted Pcolce mRNA delivery and calcium supplementation synergistically attenuate osteoporosis - Zhe Li; Xinyi Zhou; Yuxuan Zhang; Kun Tan; Tian Gan; Yunyun Xie; Jinglun Zhang; Yihong Cheng; Ning Du; Ruoyi Wu; Yan Liu; Fangfang Song; et al. (Chemical Engineering Journal, 2025)

A Transformer-based framework with generative spectral augmentation for online monitoring of hyaluronic acid fermentation - Weilu Tian; Lixuan Zang; Yunyi Li; Cheng Peng; Jinhua Zhang; Huarong Shao; Ruiqing Xian; Ru Sun; Fei Liu; Haining Tan; Peixue Ling (Carbohydrate Polymers, 2025)

The 7.2 ka cold event and its societal impact: climate-induced hiatus in the Dadiwan Culture of the Chinese Loess Plateau - Yuqing Yang; Xingxing Liu; Yuan Li; Liangcheng Tan; Xulong Wang; Long Ma; Lele Ren; Peng Cheng; Yuda Chui; Hongli Zhao; Youbin Sun (CATENA, 2025)

The whole genome sequence of Cordyceps cicadae — an edible and potential medicinal fungus - Yuwei Liu; Xueqian Li; Yiqi Meng; Yifan Wu; Yuting Jin; Xiaotong Ma; Wei Zhou; Yuchong Tan; Fu-Cheng Lin; Hongkai Wang (Molecular Genetics and Genomics, 2025)

A new dammarane-type triterpenoid saponin from the leaves of sour jujube - Jin-Yan Tan; Pei Li; Si-Qi Yang; Jia-Ning Zhang; Yan-Gang Cheng (Natural Product Research, 2025)

Analytical and numerical investigations of the interaction between nonlinear guided wave mixing and micro-cracks in pipe-like structures - Maoxun Sun; Miaohong Tan; Cheng Shan; Yue Zhang; Hongye Liu (Wave Motion, 2025)

Synergy of algal particle deposition and bioturbation amplifies the internal phosphorus loading - Fengrui Zhang; Lixian Tan; Wenxuan Han; Lei Zhang; Qiushi Shen; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Water Research, 2025)

Divergent responses of cropland soil available potassium to fertilization across the Sichuan Basin of China - Jinli Cheng; Dan Chen; Xinyi Chen; Yaruo Mao; Aiwen Li; Ke Zhu; Yaling Yu; Wanqi Tan; Bing Li; Bin Zhao; Qiquan Li (Soil and Tillage Research, 2025)

Microplastics: an overlooked particle organic carbon in river systems - Xuke Liu; Weijian Zhou; Peng Cheng; Fei Zhang; Liangcheng Tan; Yunchong Fu; Yukun Fan; Jianghu Lan; Huachun Gu; Wen Liu; Ting Wang (Science Bulletin, 2025)

Impacts of tail channel alterations on hydrodynamic and environmental conditions in Yellow River Estuary - Yuming Cheng; Xiaotian Ma; Jian Sun; Yuanyi Li; Fengze Zhao; Kok Weng Tan (Marine Environmental Research, 2025)

Application of Pichia kudriavzevii in solid-state fermentation of Zhenjiang aromatic vinegar: Microbial community structure and volatile flavor changes - Shengkai Hua; Xiang Wei; Leyi Wang; Yuqin Wang; Siyuan Cheng; Chunjia Bao; Xiaorui Zeng; Xinnuo Chen; Yongjian Yu; Jinhao Tan (International Journal of Food Microbiology, 2025)

Disentangling natural and anthropogenic influences on the spatial variability of soil cadmium contamination - Jing Geng; Yong Yu; Qiuyuan Tan; Guoxu Li; Huajun Fang; Yifan Guo; Shulan Cheng (Environmental Pollution, 2025)

Recognition of multiple geochemical anomalies by dual-branch convolutional neural network with adaptive feature fusion - Jundong He; Weirong Yang; Zhengbo Yu; Cheng Tan; Binbin Li (Computers & Geosciences, 2025)

Corrigendum to “Nanoplatforms derived from iron dextran combined with ascorbic acid for enhanced photothermal-chemodynamic therapy of tumors” [Chem. Eng. J. 496 (2024) 154044] - Bin Zhang; Xiao-Lin Hou; Xiao-Ting Xie; Lin-Fang Tan; Meng Guan; Dong-Hui Zhao; Sui Zhou; Kai Cheng; Jin-Xuan Fan; Bo Liu (Chemical Engineering Journal, 2025)

Ultra-sensitive and robust MXene/Ag-Ag nanocomposite-based conformal temperature sensor for broad-range thermal monitoring - Yingjie Niu; Ziqi Wang; Zhenxiang Xiong; Yuanyuan Tan; Zhijian Meng; Dejin Yan; Hui Cheng; Chenglin Yi; Kaifu Zhang (Chemical Engineering Journal, 2025)

Quasi-pure-phase 2D perovskites for high-efficiency and stable 2D/3D perovskite heterojunction solar cells - Fei Wu; Yuping Gao; Ye Zeng; Junhong Tan; Cheng Zhong; Xing Gao; Yingguo Yang; Yongsheng Liu; Linna Zhu (Chemical Engineering Journal, 2025)

Impacts of solar radiation modification on precipitation extremes in Central China - Zeqian Feng; Mou Leong Tan; Mohd Amirul Mahamud; Shiyuan Cheng; Chenglei Hou (Climate Dynamics, 2025)

Low-potential pyrene-coordinated MOFs and CoSOH nanosheets: An electrochemiluminescence energy resonance transfer system for aflatoxin B1 detection - Cheng Tan; Jiayuan Nie; Jingjing Xi; Xiao Mei; Kang Wu; Anping Deng; Xinjian Feng; Jianguo Li (Analytica Chimica Acta, 2025)

Glycosides constituents from Codonopsis pilosula - Yan-Gang Cheng; Si-Qi Yang; Pei Li; Yan Wang; Hui-feng Li; Xiang-Peng Kong; Jin-Yan Tan; Ying-Li Wang (Natural Product Research, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Associations between per- and polyfluoroalkyl substances and type 2 diabetes: The modifying effects of lifestyle and genetic risk - Xu Cheng; Fei Wang; Jin Zhang; Yu Wang; Lu Liu; Lin Liu; Hong Guo; Junya Gao; Yafei Tan; Meian He (Journal of Hazardous Materials, 2025)

Downward migration of functional microorganisms for nitrogen removal in soil layer of bioretention system under rainfall event - Houkun Wei; Fuguo Qiu; Yu Cheng; Yuqi Pan; Yulin Li; Yuanping Fang; Chaohong Tan; Haiyan Li (Journal of Environmental Chemical Engineering, 2025)

Texture design for improving the tribological performance of scroll compressors based on multi friction pair modeling - Shuai Cheng; Zehua Han; Shupeng Tan; Dongliang Liu; Xianghui Meng (International Journal of Refrigeration, 2025)

Crushing behaviors and optimization design of 3D printed rib-filled corrugated structures with shape-memory function - Guangyu Sun; Jin Wang; Qianbing Tan; Cheng Peng; Jing Zhang; Song Yao; Yong Peng; Kui Wang (Engineering Structures, 2025)

Leveraging reinforcement learning for optimal control of chiller plant with complex hydraulic and thermodynamic characteristics - Xiao Wang; Huiming Xu; Cheng Fan; Shengyu Tan; Xuyuan Kang; Yang Shi; Da Yan (Energy and Buildings, 2025)

High-efficiency enrichment process of uranium from amidoxime-functionalized fibers after treated by alkaline elution system - Shen Zhang; Wencai Cheng; Congcong Ding; Ze Qiu; Junwen Tan; Xirui Lu; Jun Wen; Hao Li (Chemical Engineering Journal, 2025)

Effects of slope aspect and tillage type on soil microbial biomass and its stoichiometric ratios in karst trough valley - Xiaohong Tan; Lisha Jiang; Wuyi Li; Yuanyue Xia; Xin Cheng; Xiuying Xu; Fengling Gan; Youjin Yan; Yuchuan Fan; Junbing Pu (CATENA, 2025)

Schizochytrium limacinum valorizes volatile fatty acid-rich dark fermentative effluent for docosahexaenoic acid production - Yingqiu Zhang; Jiawei E; Cheng Chen; Kaixin Wei; Liyun Sun; Gaoyi Tan; Xu Zhang; Jianhua Fan (Bioresource Technology, 2025)

Mobile measurements of atmospheric isoprene across subtropical forests in Southern China - Haifeng Yu; Xiangcheng Wu; Lin Cheng; Wen Tan; Liang Zhu; Yunhua Chang (Atmospheric Environment, 2025)

Multi-omics integration reveals gut Microbiome and Short-chain fatty acid profiles in gastric cancer cachexia patients and their clinical significance - Hao Liu; Yuxi Cheng; Shanjun Tan; Yidan Qu; Zhige Zhang; Mingyue Yan; Guohao Wu (World Journal of Microbiology and Biotechnology, 2025)

Effects of understory vegetation and climate change on forest litter decomposition: implications for plant and soil management - Xia Wu; Shengnan Ouyang; Xiangping Tan; Arun K. Bose; Wei Cheng; Liehua Tie (Plant and Soil, 2025)

Ground Subsidence and Stress Arching Due to Cavity Collapse from Buried Pipe Exfiltration - Jun-Cheng Liu; Yong Tan; Yi-Chun Cao (Geotechnical and Geological Engineering, 2025)

Enhancing Laying Hens’ Egg Quality and Health with Se-Enriched Earthworm Hydrolysate - Di Cheng; Zhuxia Zhong; Hai Lian; Donghai Tan; Yuling Tian; Xianhong Cao; Qiang Zhang; Lijuan Wu; Min Zhong; Jiangping Xiao; Xiaowen Lei; Yunping Zhong (Biological Trace Element Research, 2025)

The Mechanism of the Effect of FCC Slurry Oil Blending Ratio on the Colloidal Stability and Asphaltene Aggregation Behavior of Low-Sulfur Marine Fuel Oil - Aigang Li; Shengjun Guo; Jianwen Deng; Hong Chen; Jinxuan Wu; Ru Jiang; Jing Tan; Lihua Cheng; Libo Zhang; Qinzhen Fan (Journal of Marine Science and Engineering, 2025)
Addressing IMO 2020 compliance, this study investigates marine fuel oil production from hydrotreated residues, focusing on mitigating excessive total sediment potential (TSP) caused by over-hydrotreatment. This study systematically investigates the impact of blending ratios of Fluid Catalytic Cracking (FCC) slurry oil with Residue Desulfurization (RDS) heavy oil on TSP, colloidal stability, and asphaltene structure evolution. Techniques such as XRD, SEM, and XPS were employed to analyze the structural changes in asphaltenes during the TSP exceeding process. The results indicate that as the FCC slurry oil blending ratio increases, TSP in the blended oil initially rises and then decreases. The peak TSP value of 0.41% occurs at a 10% FCC slurry oil blending ratio, primarily due to high-saturation hydrocarbons in RDS heavy oil disrupting the colloidal stability of asphaltenes in FCC slurry oil. When the blending ratio reaches 25%, TSP significantly decreases to 0.09%, attributed to the solubilizing effect of high aromatic compounds in the FCC slurry oil on the asphaltenes. The ω(Asp)/ω(Res) ratio mirrors the TSP trend, and the colloidal solubilizing capacity of asphaltenes increases with the blending ratio. Asphaltenes in RDS heavy oil exhibit a spherical structure, whereas those in FCC slurry oil show a layered structure. The precipitated asphaltenes in the blends primarily result from the aggregation of asphaltenes in FCC slurry oil, with heteroatoms (N, S, O) mainly originating from RDS heavy oil asphaltenes. During the early stage of blending, TSP formation is dominated by FCC slurry oil asphaltenes, but increasing the aromatic content in the system can significantly reduce TSP. This work provides theoretical and technical support for optimizing marine fuel blending processes in petrochemical enterprises.

Atmospheric emerging pollutants of cyclic volatile methyl siloxanes across the Yangtze River Delta region revealed by mobile measurements - Lin Cheng; Yunhua Chang; Haifeng Yu; Xiang Che; Wen Tan; Liang Zhu (Chemosphere, 2025)

Leveraging artificial intelligence for research and action on climate change: opportunities, challenges, and future directions - Xianchun Tan; Zhe Peng; Yonglong Cheng; Yi Wang; Qingchen Chao; Xiaomeng Huang; Hongshuo Yan; Deliang Chen (Science Bulletin, 2025)

Maternal and early postnatal antibiotic exposure may increase the risk of autism spectrum disorder with regression - Boli Cheng; Xi Lai; Huan Liu; Si Wang; Xinghui Li; Mei Tan; Juan Liu; Yun He (Neurotoxicology and Teratology, 2025)

Fe(III)-induced ammonium production and its control strategy during nitrogen removal in denitrifying dependent anaerobic methane oxidation system - Xin Tan; Wen-Bo Nie; Kai Luo; Yang Lu; Xiao-Wei Wang; Cheng-Cheng Dang; Lu-Yao Liu; Xuan Wang; Zhi-Cheng Zhao; Nan-Qi Ren; Guo-Jun Xie (Journal of Environmental Management, 2025)

Warming promotes soil carbon sequestration in the Tianshan Mountains - Li-yuan Zheng; Yong Zhang; Lei Tang; Chao Lu; Bo Tan; Lai Jiang; Jin-meng Tang; Cheng-bang An (Global and Planetary Change, 2025)

Exposure to benzotriazole UV stabilizer-329 at environmental concentrations induces neurotoxicity by affecting neurotransmission in Caenorhabditis elegans - Yunjiang Yu; Hongzhi Guo; Shihui Tan; Huiyang Wang; Yao Dang; Haibo Chen; Qi Zhuang; Cheng Ding; Mingdeng Xiang (Environmental Pollution, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Lithium-doped silicon-hydroxyapatite nanowires alleviate early bone loss in periodontitis via γδ T cell modulation - Zhiyu Zhu; Ruomei Li; Peng Mei; Cheng Zhu; Tiancheng Li; Yixin Li; Wenduo Tan; Yueyi Yang; Yu Jin; Weiming Guo; Runzhe Fang; Lunguo Xia; et al. (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Targeted conversion of furfural from waste wood via catalyzed pyrolysis of acid-leaching residue - Shi Cheng; Cheng Tan; Yong Yu; Jun Huang; Jinlong Du; Jianhang Hu; Hua Wang (Bioresource Technology, 2025)

Enhancing lipid yield in freshwater microalgae through synergistic abiotic stressors for sustainable biodiesel production - Uganeeswary Suparmaniam; Cheng Yaw Li; Man Kee Lam; Nurul Tasnim Sahrin; Hemamalini Rawindran; Chin Seng Liew; Jun Wei Lim; Inn Shi Tan; Sie Yon Lau; Bridgid Lai Fui Chin (Biomass and Bioenergy, 2025)

Spatio-temporal aware graph convolution network for urban traffic speed prediction - Haitao Cheng; Xiaoying Tan; Ke Wang (Earth Science Informatics, 2025)

Data augmentation-based fault diagnosis framework for nuclear power plants with robust anti-data interference capability - Jiangkuan Li; Shangcai Zheng; Jiaoshen Xu; Meng Lin; Zhenfeng Niu; Jiahao Cheng; Chenxin Zhu; Ruifeng Tian; Sichao Tan (Annals of Nuclear Energy, 2025)

Enhancing soil organic carbon fixation with modified bentonite composites - Bing Liu; Yuwen Shen; Deshui Tan; Bohan Cheng; Haitao Lin; Rui Xue; Zongxin Li; Qiang Yao; Shuying Jiao (Applied Clay Science, 2025)

Exploring community energy cum Aquavoltaics in Taiwan - Sin Yee Tan; Kenneth Bicol Dy; Ching-Cheng Chang; Shih-Hsun Hsu (Aquaculture, 2025)

Spatiotemporal evolution and driving factors of urban form resilience under flood hazard disturbance: A case study of 137 cities in the southeast monsoon influence zone of China - Ling Zhu; Zhiqiang Xie; Yun Liu; Lihong Yang; Jing Tan; Wei Cheng; Zhongliang Cai; Qingyun Du; Shuliang Zhang (Science of The Total Environment, 2025)

Chemical constituents of the herb of Thermopsis lanceolata R. Br. and their stimulation of seed germination of Triticum aestivum L - Xing-Ya Wu; Jian-Guo Tan; Cheng-Feng Liu; Wen-Wen He; Cai-Yan Tian; Qiao An; Ping Yi; Chun-Mao Yuan; Xiao-Jiang Hao; Zhan-Xing Hu (Phytochemistry, 2025)

Response of rice flower carp (Cyprinus carpio var.) to high-temperature stress: Mechanisms and limits of tolerance - Chunxing Cheng; Wenfei Tian; Jinyou Wei; Linli Li; Haizhen Tan; Zhengjun Wu; Jiaoyun Jiang (Journal of Thermal Biology, 2025)

Translocation of polystyrene nanoplastics in distinct plant species: Novel insight from a split-root system and transcriptomic analysis - Xiang Xu; Cheng Peng; Jiaqi Tan; Qian Sui; Jing Wei; Chensi Shen; Wenwen Xie; Wei Zhang; Yongming Luo (Journal of Hazardous Materials, 2025)

Synergistic toxicity of DBDPE and Cd in a microcosm agrosystem: Insights into physiological, biochemical, nutrient elements and amino acid metabolic responses - Tianzi Liu; Zhihua Qiao; Kailin Gong; Yuhe Yang; Yanna Han; Jiaqi Tan; Cheng Peng; Wei Zhang (Journal of Hazardous Materials, 2025)

Polystyrene nanoplastics exposure trigger cognitive impairment mitigated by luteolin modulated glucose-6-phosphate dehydrogenase/glutathione-dependent pathway - Cheng Tan; Chunyang Kang; Pan Liu; Yajuan Sun; Hui Jin (Journal of Hazardous Materials, 2025)

Goethite-humic acid composites for multi-metal soil remediation: Mechanisms and environmental transformation - Xiangbang Ma; Ram Proshad; Yineng Lu; Rong Tan; Zihao Ding; Geng Cheng; Ziyi Li; Shuangting Zhang; Zhuanjun Zhao (Journal of Environmental Chemical Engineering, 2025)

Unveiling interactions between anammox and denitrification from long-term steady-state scale and transient kinetic scale in a granular sludge system - Hao Tan; Fengjun Yin; Jinjin Zheng; Xuehai Yue; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Hong Liu (Bioresource Technology, 2025)

Spatio-temporal interactions between snow leopards, prey, and livestock- implications for coexistence - Yang Hong; Minghai Zhang; Yuehong Cheng; Xiaoxing Bian; Yingchun Tan; Xiaogang Shi; Jindong Zhang; Vanessa Hull (Biological Conservation, 2025)

Fusing multi-modal data for comprehensive quality evaluation of urban ecological space at grid scale: A case study in Taizhou, China - Liqin Tan; Lei Ma; Cheng Chen; Gang Lu; Heng Lu (Sustainable Cities and Society, 2025)

Characteristics of inland ship and the effect of combined diesel oxidation catalyst (DOC) and diesel particulate filter (DPF) aftertreatment system on their pollutant emissions - Thi-Hieu Le; Zhi-Ping Hsu; Cindy Soo Yun Tan; Cheng-Di Dong; Chitsan Lin; Tsun-Lirng Yang; Xuan-Thanh Bui; Lin-Chi Wang (Environmental Pollution, 2025)

Scavenging intracellular reactive oxygen species to boost methanol assimilation - Haiyan Liu; Yun Chen; Jian Li; Cheng Zhu; Jiahui Peng; Ramon Gonzalez; Yanfen Bai; Zaigao Tan (Chemical Engineering Journal, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

The nematicidal activity of Bacillus thuringiensis Cry1Ia36 expressing in Escherichia coli - Feixue Cheng; Dongwei Wang; Jian Wang; Xin Wang; Minzhi Long; Shu-e Sun; Chunhui Zhu; Ju-e Cheng; Xinqiu Tan; Deyong Zhang; Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Crustal shear-wave velocity structure of the Namche Barwa massif, eastern Himalayan Syntaxis, Tibet from ambient noise tomography - Jiawei Tan; Xuzhang Shen; Siyuan Cheng; Rui Gao; Wentian Wang (Physics of the Earth and Planetary Interiors, 2025)

Deciphering nitrogen and sulfur metabolic pathways in thiosulfate-driven denitrification coupled with Anammox for enhanced nitrogen removal - Lu-Yao Liu; Cheng-Cheng Dang; Xin Tan; Kai Luo; Zhi-Cheng Zhao; Xuan Wang; Xiao-Wei Wang; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Journal of Environmental Chemical Engineering, 2025)

Quantitative assessment of rock plane replica orientation detection and extraction methods under controlled experimental conditions - Nirandoal Cheng; Tan Yon Ken; Mohd Ashraf Mohamad Ismail; Fatin Nadhirah Ahmad Pauzi; Nursyahirah Mohd Saleh; Yasuhiro Yokota (Geomechanics for Energy and the Environment, 2025)

Targeted amino acid metabolomic profiling revealed light-mediated quality variations in pink Auricularia cornea - Lei Ye; Lingzi Zhang; Jie Cheng; Wei Tan; Xiaolin Li; Xiaoping Zhang (Food Bioscience, 2025)

Development of novel starch/carboxymethyl cellulose-based films engineered with zeolitic imidazolate framework-8 for salmon preservation - Shiyu Jia; Yuanda Sun; Yingmeng Hou; Shasha Cheng; Wentao Su; Mingqian Tan; Haitao Wang (Chemical Engineering Journal, 2025)

Development of Brassica rapa-nigra monosomic alien addition lines: cytology, genetics, and morphology - Pengfei Li; Haiyan Wu; Shizhen Guo; Shunlin Wang; Mimi Zhang; Mengyang Liu; Wei Ma; Jianjun Zhao; Chen Tan; Cheng Cui; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2025)

Migrasome-related ITGA5 for predicting prognosis, immune infiltration and drug sensitivity of hepatocellular carcinoma - Wanjin Chen; Kailin Liu; Zhiling Wang; Hui Zhang; Ming Tan; Yuting Liu; Tingting Gao; Xiameng Su; Leirong Gu; Xinyan Chen; Shengtao Cheng (Apoptosis, 2025)

Record High Temperatures in the Ocean in 2024 - Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Huai-Min Zhang; Andrea Storto; Karina Von Schuckmann; Yuying Pan; Yujing Zhu; Michael E. Mann; Jiang Zhu; Fan Wang; et al. (Advances in Atmospheric Sciences, 2025)
Heating in the ocean has continued in 2024 in response to increased greenhouse gas concentrations in the atmosphere, despite the transition from an El Niño to neutral conditions. In 2024, both global sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached unprecedented highs in the historical record. The 0–2000 m OHC in 2024 exceeded that of 2023 by 16 ± 8 ZJ (1 Zetta Joules = 10 21 Joules, with a 95% confidence interval) (IAP/CAS data), which is confirmed by two other data products: 18 ± 7 ZJ (CIGAR-RT reanalysis data) and 40 ± 31 ZJ (Copernicus Marine data, updated to November 2024). The Indian Ocean, tropical Atlantic, Mediterranean Sea, North Atlantic, North Pacific, and Southern Ocean also experienced record-high OHC values in 2024. The global SST continued its record-high values from 2023 into the first half of 2024, and declined slightly in the second half of 2024, resulting in an annual mean of 0.61°C ± 0.02°C (IAP/CAS data) above the 1981–2010 baseline, slightly higher than the 2023 annual-mean value (by 0.07°C ± 0.02°C for IAP/CAS, 0.05°C ± 0.02°C for NOAA/NCEI, and 0.06°C ± 0.11°C for Copernicus Marine). The record-high values of 2024 SST and OHC continue to indicate unabated trends of global heating.

Proline improves the developmental competence of in vitro matured porcine oocytes by enhancing mitochondrial function - Yazhuo Cheng; Jiyong Shang; Xilong Jia; Yongda Zhao; Jing Liu; Yanjun Huan; Jinghe Tan; Mingju Sun (Theriogenology, 2025)

Life cycle assessment of apple production and consumption under different sales models in China - Juanjuan Cheng; Jin Yu; Dejun Tan; Qian Wang; Zhengyang Zhao (Sustainable Production and Consumption, 2025)

Recognizing and reducing effects of moisture-salt coexistence on soil organic matter spectral prediction：From laboratory to satellite - Danyang Wang; Yayi Tan; Cheng Li; Jingda Xin; Yunqi Wang; Huagang Hou; Lulu Gao; Changbo Zhong; Jianjun Pan; Zhaofu Li (Soil and Tillage Research, 2025)

Nonlinear tuning of multiple topological edge states in photovoltaic photonic lattices - Ruichang Chen; Wenchao Yan; Weijie Liu; Weizhao Cheng; Qingming Lu; Yang Tan; Feng Chen (Science Bulletin, 2025)

Rapid Indian Monsoon response to the Younger Dryas event in the Southeastern Tibetan Plateau - Xiqian Wang; Liangcheng Tan; Ashish Sinha; Hai Xu; Haiwei Zhang; Jianghu Lan; Jin Zhang; Tianli Wang; Dong Li; Le Ma; Jingjie Zang; Xing Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Metabolic profiling and evaluation of antioxidant and anti-inflammatory properties of Apis cerana cerana Honey from Sansha City, Hainan Province, China - Jiao Wu; Xiang-Tan Xu; Cheng Xing; Xin-Bao Hao; Xing-Yue Fang; Zhi-Hao Xie; Shan Zhao; Jing-Lin Gao; Lu Xu; Shi-Jie Wang (Food Chemistry, 2025)

Simple-efficient cultivation for rapeseed under UAV-sowing: Developing a high-density and high-light-efficiency population via tillage methods and seeding rates - Xiaoqiang Tan; Mingqiang Bai; Zongkai Wang; Chunmei Xiang; Yugui Cheng; Yufeng Yin; Jing Wang; Zhenghua Xu; Jie Zhao; Bo Wang; Jie Kuai; Guangsheng Zhou (Field Crops Research, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Flexible nanoporous copper film for efficient interfacial solar steam generation and water purification - Jiajia Liu; Yalong Liu; Jiameng Sun; Bin Yu; Xiangyu Fei; Ziwei Guo; Fuquan Tan; Guanhua Cheng; Zhonghua Zhang (Chemical Engineering Journal, 2025)

Anaerobic methane oxidation drives simultaneous nitrite and nitrous oxide removal - Xin Tan; Wen-Bo Nie; Yang Lu; Xiao-Wei Wang; Cheng-Cheng Dang; Xuan Wang; Lu-Yao Liu; Nan-Qi Ren; Bing-Jie Ni; Guo-Jun Xie (Bioresource Technology, 2025)

Validation of Interaction Between Sugarcane miR167d and Predicted Target Gene ScPUM1 and Analysis of Their Expression Under Cold Stress: A Novel Mechanism of miR167d - Qiqi Song; Pengjin Zhu; Jiahui Li; Qin Cheng; Qinliang Tan; Quanguang Zhou; Ping Lv; Zemei Nong (Journal of Plant Growth Regulation, 2025)

Function analysis of the cytidine deaminases in root-knot nematode, Meloidogyne incognita - Dongwei Wang; Jian Wang; Yingmei Li; Zhuo Zhang; Jue Cheng; Chunhui Zhu; Zhixiang Zhao; Xinqiu Tan; Deyong Zhang; Yong Liu; Feixue Cheng (European Journal of Plant Pathology, 2025)

Development of a rat airway organoids model for studying chronic obstructive pulmonary disease - Chuanlai Yang; Hongwei Yang; Yangling Xian; Nanyi Liu; Haoyin Tan; Zirui Ren; Yanzhen Lin; Huan Zhao; Changjian Fang; Kang Yu; Dequan Pan; Yali Zhang; et al. (Tissue and Cell, 2025)

VvABF5 promotes ABA-mediated chlorophyll degradation by transcriptional activation of VvSGR during rachis browning of grape - Zhiqian Li; Dongfang Zou; Changjiang Nie; Xing Chen; Chang He; Xianbo Zheng; Bin Tan; Jun Cheng; Wei Wang; Pedro Martínez Gómez; Xia Ye; Jiancan Feng (Postharvest Biology and Technology, 2025)

Enhancing soil quality and maize growth while reducing Cd accumulation with biochar and humic acid in northwestern China - Ziyi Li; Xiangbang Ma; Shuangting Zhang; Geng Chen; Yineng Lu; Rong Tan; Ram Proshad; Xifeng Zhang; Xiuwen Cheng; Zhuanjun Zhao (Journal of Environmental Chemical Engineering, 2025)

Highly enhanced removal of Cr(VI) by nZVI in presence of myo-inositol hexakisphosphate: The depassivation performance and multiple electron transfer mechanisms - Cheng Wang; Shuijing Zhou; Feng Jiang; Yupeng Yan; Xiaoming Wang; Hui Yin; Wenfeng Tan; Xionghan Feng (Journal of Environmental Sciences, 2025)

Petrogenesis of post-collisional felsic rocks and implications for continental growth: Insights from a Paleogene monzonitic intrusion, southeastern Tibetan Plateau - Hao Liu; Zheng Liu; Guo-Chang Wang; Shu-Cheng Tan (Journal of Asian Earth Sciences, 2025)

Determination of five alternaria toxins in peppermint by dispersive solid-phase extraction coupled with ultra-high performance liquid chromatography-tandem mass spectrometry based on MOF-808-TFA - Minhai Liu; Yan Zhang; Rui Cheng; Ting Tan; Lan Guo; Fan Liu; Yiqun Wan (Food Chemistry, 2025)

Improving flavor of Wuyi rock tea processed from rain-soaked leaves by optimizing withering conditions - Jiayao Tan; Zhou Fang; Caiyun Tian; Chengzhe Zhou; Cheng Zhang; Lele Jiang; Anru Zheng; Niannian Yang; Yuqiong Guo (Food Chemistry, 2025)

Dissolved oxygen prediction in the Dianchi River basin with explainable artificial intelligence based on physical prior knowledge - Junhao Wu; Xi Chen; Jinghan Dong; Nen Tan; Xiaoping Liu; Antonis Chatzipavlis; Philip LH. Yu; Adonis Velegrakis; Yining Wang; Yonggui Huang; Heqin Cheng; Diankai Wang (Environmental Modelling & Software, 2025)

Deleted in malignant brain tumors 1 (DMBT1) gene relate to immune priming and phagocytosis modulation in the small abalone Haliotis diversicolor - Tuo Yao; Junyuan Tan; Jie Lu; Shengli Fu; Zhilv Xie; Bing Li; Changhong Cheng; Lingtong Ye (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Transport characteristics of urban and rural aerosols based on vertical observations and deep learning predictions - Tiliang Zou; Chengzhi Xing; Jingkai Xue; Qihua Li; Wei Tan; Zehong Wu; Cheng Liu (Atmospheric Research, 2025)

PpSPL1 and PpSPL15 inhibit peach branching by increasing strigolactone synthesis - Wan Pei; Jie Zhang; Ruixian Shen; Hefang Xie; Yajia Zhang; Junjie Zhang; Xiaodong Lian; Haipeng Zhang; Nan Hou; Lei Wang; Xianbo Zheng; Jun Cheng; et al. (Planta, 2025)

Protecting mud crabs from pollution by microplastics, per- and polyfluoroalkyl substances, polycyclic aromatic hydrocarbons, pesticides, and heavy metals in mangroves - Wan Adibah Wan Mahari; Yiu Fai Tsang; Che-Jung Hsu; Hanafiah Fazhan; Youji Wang; Kianann Tan; Rock Keey Liew; Cheng-Di Dong; Khor Waiho; Su Shiung Lam (Environmental Chemistry Letters, 2025)

Ocular Myasthenia gravis: determining the predictive factors of secondary generalisation - Prasana Nair Gengadharan; Wei Ting Ong; Jie Ying Tan; Nortina Shahrizaila; Khean Jin Goh; Cheng Yin Tan (Acta Neurologica Belgica, 2025)

Responses of zebrafish to chronic environmental stressors: anxiety-like behavior and its persistence - Xiao-hong Li; Cheng Fu; Xue-ting Tan; Shi-jian Fu (Frontiers in Marine Science, 2025)
Introduction Fish in natural ecosystems face long-term environmental stressors, with anxiety being a critical stress response. This study investigates how chronic stressors—predators, social isolation, and caffeine—affect anxiety-like behavior and cortisol levels in zebrafish ( Danio rerio ), and examines the persistence of these effects post-stressor removal. Methods Zebrafish were exposed to three stressors for 14 days. Anxiety-like behavior and cortisol levels were measured for up to 28 days following the removal of the stressors. Results Chronic predator stress significantly increased anxiety-like behavior and cortisol levels, persisting for at least seven days post-removal. Social isolation reduced anxiety-like behavior and cortisol levels, with effects lasting no less than one day after re-socialization. Caffeine induced temporary anxiolytic effects, reversing one day post-withdrawal and persisting for at least seven days, while cortisol levels remained elevated. Discussion Zebrafish exhibit stressor-specific behavioral and physiological changes with varying persistence. These findings enhance understanding of fish responses to environmental stressors, offering insights into their survival strategies and ecosystem health.

The effects of phospholipids (PL) addition in the high fat diet on growth performance, oxidative stress, lipid and protein metabolism, and muscle development in yellow catfish Pelteobagrus fulvidraco - Qing-Lin Li; Biao Wang; Hua Zheng; Li-Xiang Wu; Peng-Cheng Xu; Xiao-Ying Tan (Aquaculture, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Corrigendum to “Mid-Holocene hydroclimatic change and hurricane activity in Central America recorded by an Isla de Mona Stalagmite” [Marine Geology 471 (2024) 107289] - Huiru Tang; Liangcheng Tan; Yongli Gao; Jingjie Zang; Le Ma; Yanzhen Li; R. Lawrence Edwards; Hai Cheng; Ashish Sinha; Xiqian Wang; Xing Cheng; Ángel A. Garcia; et al. (Marine Geology, 2025)

Systematic evaluations of receptor models in source apportionment of particulate solids in road deposited sediments: A practical application for tracking heavy metal sources on urban road surfaces - Zicheng Wang; Nian Hong; Yushan Chen; Guanhui Cheng; An Liu; Xiaowu Huang; Qian Tan (Journal of Hazardous Materials, 2025)

The inhibition mechanism of N2O generation in NH3-SCR process by water vapor - Junchen Li; Cheng Zhang; Dingli Fang; Zhao Zheng; Yan Zhao; Peng Tan; Qingyan Fang; Gang Chen (Journal of Hazardous Materials, 2025)

High-efficiency flavonoid deglycosylation of whole cells with surface display of α-L-rhamnosidase in Escherichia coli - Cheng-Hai Yan; Ding Wang; Ruo-Xi Mei; Lu Tan; Yi-Jiang-Cheng Li; Richard Ansah Herman; Yan Xu; Lu-Chan Gong; Jun Wang (Food Bioscience, 2025)

Novel thyme essential oil-loaded biodegradable emulsion film based on soybean lipophilic proteins for salmon preservation - Yuanda Sun; Shiyu Jia; Yingmeng Hou; Shasha Cheng; Mingqian Tan; Beiwei Zhu; Haitao Wang (Food Hydrocolloids, 2025)

Enhancing thermal conductivity, electromagnetic interference shielding, and joule heating in polyether ether ketone composites using three-dimensional scaly carbon fibre structures and structural optimisation - Yifan Wang; Fengyu Wen; Yashu He; Lin Cheng; Haoyuan Tan; Jierun Ma; Pengbo Lian; Yuxuan Gu; Rui Chen; Jianxin Mu (Chemical Engineering Journal, 2025)

Unveiling the potential gain in life expectancy by improving air quality for ambient ozone in eastern China - Jingjing Zhang; Cheng Wang; Yixiang Wang; Minjin Peng; Jiajun Shen; Yalin Zhang; Yuxi Tan; Hao Zheng; Yunquan Zhang (Atmospheric Environment, 2025)

Mobile measurements of atmospheric decamethylcyclopentasiloxane (D5) in Eastern China - Haifeng Yu; Yunhua Chang; Lin Cheng; Wen Tan; Liang Zhu; Jianlin Hu (Atmospheric Environment, 2025)

The role of liver sinusoidal endothelial cells in metabolic dysfunction-associated steatotic liver diseases and liver cancer: mechanisms and potential therapies - Hanjun Mo; Pengfei Yue; Qiaoqi Li; Yinxi Tan; Xinran Yan; Xinyue Liu; Yuanwei Xu; Yingzhe Luo; Suruiya Palihati; Cheng Yi; Hua Zhang; Minlan Yuan; et al. (Angiogenesis, 2025)

Transcriptomic and physiological analyses reveal the response mechanism of the liver under acute ammonia stress in the Chinese soft-shelled turtle (Pelodiscus sinensis) - Yujie Ding; Zhiwen Tan; Cheng Xu; Hetron Mweemba Munang’andu; Qiuya Huang; Chentao Liu; Wei Wang; Guoying Qian; Jiehao Xu (Aquaculture, 2025)

Enhanced interpretation of green space surface for land surface temperature through a novel voxel-based landscape index from UAV LiDAR - Lv Zhou; Xuejian Li; Zihao Huang; Cheng Tan; Huaguo Huang; Huaqiang Du (Urban Forestry & Urban Greening, 2025)

Characteristics and predictions of accumulative deformation of structured soft soil under long-term cyclic loading - Weizheng Liu; Jiming Tan; Weihua Lv; Cheng Chen; Shuai Qu (Soil Dynamics and Earthquake Engineering, 2025)

Air injection in paddy soil reduces N2O and NH3 emissions and regulates the nitrogen cycle - Jichao Tang; Quanyi Hu; Chengfang Li; Cougui Cao; Xuelin Zhang; Ying Zhang; Wenfeng Tan; Bo Cheng; Dongliang Xiong; Tianqi Liu; Yakov Kuzyakov (Soil and Tillage Research, 2025)

Microbial manganese redox cycling drives co-removal of nitrate and ammonium - Xuan Wang; Tian-Chen Liu; Xiao-Wei Wang; Cheng-Cheng Dang; Xin Tan; Yang Lu; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Journal of Environmental Management, 2025)

Deciphering the coupling of anoxic/aerobic and sulfur autotrophic denitrification: Performance, antibiotic resistance genes, and microbial community structure - Yang He; Zhigang Wang; Cheng Luo; Xin Li; Zhaoqi Wang; Aslan Temirkhanov; Zhadyrassyn Nurbekova; Zhouliang Tan; Sayan Zhangazin; Rui Wang; Yangwu Chen (Journal of Environmental Chemical Engineering, 2025)

Synthesis and application of astaxanthin-loaded procyanidins/sea cucumber peptide nanoparticles with good antioxidant and pH-responsive capacities - Shasha Huang; Zheng Hua; Kuiyou Wang; Yi Ma; Shasha Cheng; Mingqian Tan (Food Research International, 2025)

Enzymatic synthesis of structured phospholipids with ideal ω-6/3 fatty acid ratios via supplementation with α-linolenic acid from silkworm pupae oil - Lu Tan; Jin-Zheng Wang; Xin-Ying Wang; Cheng-Hai Yan; Ya-Xin Qu; Ze-Lai Huang; Tao Bai; Jun-Feng Qian; Jun Wang (Food Bioscience, 2025)

Effects of α-lipoic acid (LA) supplementation in high-fat diet on the growth, glycolipid metabolism and liver health of largemouth bass (Micropterus salmoides) - Tao Cheng; Jiandong Chen; Beiping Tan; Shuyan Chi (Fish & Shellfish Immunology, 2025)

The transition of tetragonal to monoclinic phase in BiVO4 coupled with peroxymonosulfate for photocatalytic degradation of tetracycline hydrochloride - Cixin Cheng; Huihong Tan; Weiwei Zhu; Lang Liu; Kao Chen; Jun Yan (Environmental Research, 2025)

Peroxisome-inspired T4 phage hybrid enzyme nanoreactors for photodynamic therapy of breast cancer - Xiao-Lin Hou; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Qiong Wang; Kai Cheng; Jin-Xuan Fan; Tian-Cai Liu; Bo Liu (Chemical Engineering Journal, 2025)

Thermophilic anaerobic ethane oxidation coupled with selenate and selenite reduction - Lu-Yao Liu; Cheng-Cheng Dang; Xin Tan; Bing-Feng Liu; Yang Lu; Zhi-Cheng Zhao; Xuan Wang; Xiao-Wei Wang; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Bioresource Technology, 2025)

An overview of advancements in biomass pyrolysis modeling: Applications, challenges, and future perspectives in rotary reactors - Chaowei Ma; Ruinan Zhu; Yulei Ma; Yong Yu; Cheng Tan; Shiliang Yang; Huili Liu; Jianhang Hu; Hua Wang (Biomass and Bioenergy, 2025)

Abnormal network homogeneity in patients with bipolar disorder in attention network - Mengling Tan; Yunxiao Guo; Sijun Liu; Wei Liu; Liang Cheng; Yujun Gao; Zhihong Ren (Brain Imaging and Behavior, 2025)

A comprehensive screening method of oxidation systems based on reaction rate constant (k value) and emergy (Em value) - Yawei Liu; Zhiquan Wang; Zhiwen Cheng; Yuanyang Ren; Yujia Tan; Tao Yuan; Zhemin Shen (Science of The Total Environment, 2025)

Mercury deposition in central China from the Last Glacial Maximum to the early Holocene recorded in an accurately-dated stalagmite - Yanzhen Li; Liangcheng Tan; Simin Jin; Hai Xu; Lüfan Chen; David B. Kemp; Ashish Sinha; Le Ma; Chunju Huang; Lawrence R. Edwards; Hai Cheng (Science Bulletin, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Negative carbon emission power generator: A combination of high temperature proton exchange membrane fuel cell and absorption carbon capture system - Chaohuan Tan; Linhao Cheng; Wanli Peng; Hanxin Yang; Rongxiang Luo; Juncheng Guo (Journal of Cleaner Production, 2025)

Promoting ovalbumin amyloid fibrils formation by cold plasma treatment and improving its emulsifying properties - Zhi-Wei Liu; Pan-Pan Tang; Chang Liu; Yi-Cheng Tan; Tian-Le Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Xiu-Bin Liu (Food Hydrocolloids, 2025)

Preparation and characterization of a pH-responsive smart film based on soy lipophilic protein/hydroxypropyl methylcellulose for salmon freshness monitoring and packaging - Yuanda Sun; Yi Ma; Yingmeng Hou; Shiyu Jia; Shasha Cheng; Wentao Su; Mingqian Tan; Beiwei Zhu; Haitao Wang (Food Packaging and Shelf Life, 2025)

Innovative Janus wood membranes: Harnessing wood anisotropy for superior liquid separation and transport - Kaiwen Chen; Xianfu Xiao; Cheng Hao; Fengze Sun; Haonan Zhang; Yujing Tan; Jianyi Zhu; Hui Peng; Tianyi Zhan; Jianxiong Lyu; Ning Yan (Chemical Engineering Journal, 2025)

Manganese-mediated dissimilatory nitrate reduction to ammonium of nitrate-dependent anaerobic methane oxidation - Xuan Wang; Xin Tan; Cheng-Cheng Dang; Lu-Yao Liu; Xiao-Wei Wang; Yang Lu; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Chemical Engineering Journal, 2025)

Metabolomics with gut microbiota analysis of podophyllotoxin-mediated cardiotoxicity in mice based on the toxicological evidence chain (TEC) concept - Lu Sun; Jiaojiao Liu; Yangyang Cheng; Yikang Wu; Tao He; Yingyue Zhang; Xiaorui Bai; Zixin Zhou; Xiayu Xu; Yuxin Yao; Yafei Tan; Qiang Qiu; et al. (Chemico-Biological Interactions, 2025)

Hydrothermal-mediated in-situ nitrogen doping to prepare biochar for enhancing oxygen reduction reactions in microbial fuel cells - Shiteng Tan; Ruikun Wang; Jialiang Dong; Kai Zhang; Zhenghui Zhao; Qianqian Yin; Jingwei Liu; Weijie Yang; Jun Cheng (Bioresource Technology, 2025)

Study on the resilience recovery of civil airport infrastructure under weather extremes - Xin Huang; Lizhi Yang; Kun Wu; Cheng-song Tan; Lin Qi; Yu Chen (Natural Hazards, 2025)

Photosynthetic Toxicological Effects of Organic Extracts from Zanthoxylum bungeanum Leaves on Controlling the Microcystis aeruginosa Blooms - Jie Cheng; Long Tan; Xue Lu; Mengyu Zheng; Chengshuai Xu; Wei Xu; Tong Jiang; Chaobo Zhang (Current Microbiology, 2025)

Experimental and numerical investigation on internal erosion induced by infiltration of defective buried pipe - Zi-Ye Wang; Jun-Cheng Liu; Yong Tan; Ying-Ying Long (Bulletin of Engineering Geology and the Environment, 2025)

PLCFishMOT: multiple fish fry tracking utilizing particle filtering and attention mechanism - Huachao Tan; Yuan Cheng; Dan Liu; Guihong Yuan; Yanbo Jiang; Hongyong Gao; Hai Bi (Aquaculture International, 2025)

Fast and Deterministic Underwater Point Cloud Registration for Multibeam Echo Sounder Data - Liang Zhao; Lan Cheng; Tingfeng Tan; Chun Cao; Feihu Zhang (Journal of Marine Science and Engineering, 2024)
Investigating underwater environments using Multi-Beam Echo Sounder (MBES) point cloud registration technology is a critical yet underdeveloped area in oceanographic research. This paper presents a fast, deterministic Branch-and-Bound (BnB) method with four degrees of freedom, which combines Inertial Measurement Unit (IMU) data with MBES point cloud data for precise registration. Given the prevalence of outliers and noise in underwater acoustic measurements, the BnB method is employed to provide globally deterministic solutions. However, due to the exponential convergence speed of the BnB method with respect to the dimensionality of the solution space, searching within a six-degree-of-freedom parameter space (three rotational and three translational degrees of freedom) can be extremely time-consuming. To this end, the Z-axis of the point cloud is aligned with the gravitational direction of the IMU, reducing the rotational degrees of freedom from three to one, specifically concerning yaw. Additionally, an outlier exclusion strategy is introduced to eliminate mismatches, significantly reducing the number of key-point correspondences and thereby improving registration efficiency. Experiments conducted on both public and real-world lake datasets demonstrate that the proposed method achieves a favorable balance between speed and accuracy, outperforming other tested methods and meeting the demands of contemporary research.

Recent advances on natural colorants-based intelligent colorimetric food freshness indicators: fabrication, multifunctional applications and optimization strategies - Deyang Yu; Shasha Cheng; Yu Li; Wentao Su; Mingqian Tan (Critical Reviews in Food Science and Nutrition, 2024)

Enrichment and characterization of thermophilic anaerobic ammonium oxidizing bacteria from hot spring - Xiao-Wei Wang; Xin Tan; Cheng-Cheng Dang; Lu-Yao Liu; Xuan Wang; Zhi-Cheng Zhao; Hong-Yu Ren; Bing-Feng Liu; Guo-Jun Xie (Water Research, 2024)

Unveiling the impacts of biodegradable microplastics on cadmium toxicity, translocation, transformation, and metabolome in lettuce - Xiang Xu; Cheng Peng; Xuechun Shao; Kailin Gong; Xuan Zhao; Wenwen Xie; Wei Zhang; Jiaqi Tan (Science of The Total Environment, 2024)

Global techno-economic analysis of MBR for hospital wastewater treatment - Junqing He; Zhenxing Zhang; Fangnan Cui; Xue Tan; Xiang Zheng; Rong Cheng (Science of The Total Environment, 2024)

Fish community dynamics following the low-head dam removal and newly installed fish passage in a headstream tributary of Jinsha River, Southwest China - Junjun Tan; Junjian Sun; Yuanyang Wang; Huiwu Tian; Bixin Cheng; Jie Qing; Xin Yan; Gan Sun; Senfan Ke; Giri Raj Kattel; Xiaotao Shi (Science of The Total Environment, 2024)

Enhanced tetracycline degradation by manganic iron‑manganese compounds with peroxymonosulfate(PMS): Experimental optimization and environmental fate estimation - Ruixi Ni; Jiale Tan; Rong Tan; Yineng Lu; Jiangwei Shang; Xiuwen Cheng (Journal of Water Process Engineering, 2024)

Transport behavior of Polymeric Methyl Methacrylate nanoplastics in saturated and unsaturated porous media: Combined influence of electrolyte and organic acids - Lihui Tan; Lulu Ding; Ming Wu; Zhou Cheng; Yanru Hao; Guoping Lu (Journal of Environmental Chemical Engineering, 2024)

Double-layer films based on konjac gum and hydroxypropyl methyl cellulose loaded with thyme essential oil Pickering emulsion: Preparation, characterization, and application - Yingmeng Hou; Yuanda Sun; Shiyu Jia; Wentao Su; Shasha Cheng; Mingqian Tan; Haitao Wang (Food Hydrocolloids, 2024)

Active polyvinyl alcohol packaging films incorporated with spermine functionalized carbon dots as antibacterial agents for salmon preservation - Shasha Cheng; Jiashu Li; Jiale Ma; Mingqian Tan (Food Packaging and Shelf Life, 2024)

Self‑supporting magnetic nanoporous silver-nickel films with broadband light absorption for efficient interfacial solar steam generation - Ziwei Guo; Yalong Liu; Bin Yu; Xiangyu Fei; Jiameng Sun; Fuquan Tan; Guanhua Cheng; Weimin Wang; Zhonghua Zhang (Chemical Engineering Journal, 2024)

Chitosan/dextran-based organohydrogel delivers EZH2 inhibitor to epigenetically reprogram chemo/immuno-resistance in unresectable metastatic melanoma - Qi Tang; Shaolong Leng; Yinqiu Tan; Huan Cheng; Qi Liu; Zhongjuan Wang; Yunsheng Xu; Linyu Zhu; Cuifeng Wang (Carbohydrate Polymers, 2024)

Genetic polymorphisms as potential pharmacogenetic biomarkers for platinum-based chemotherapy in non-small cell lung cancer - Hilary Sito; Shing Cheng Tan (Molecular Biology Reports, 2024)

Signature and function of plasma exosome-derived circular RNAs in patients with hypertensive intracerebral hemorrhage - Kejie Chen; Xiaoyuan Cheng; Shanshan Yuan; Yang Sun; Junli Hao; Quandan Tan; Yapeng Lin; Shuping Li; Jie Yang (Molecular Genetics and Genomics, 2024)

Factors associated with the distribution of brain metastases in lung cancer: a retrospective study - Yixin Hu; Weiwei Lei; Enhui Xin; Tan Cheng; Jiang Liu; Yu Tang; Yong Lai; Hong Yu; Yong Tan; Jing Yang; Junhao Huang; Daihong Liu; et al. (Clinical & Experimental Metastasis, 2024)

The numerical investigation of the thermal–hydraulic behavior in a 3 × 3 rod bundle with spacer grids - Cheng Yang; Yiwei Wang; Hongyang Wei; Sichao Tan; Ruifeng Tian; Fulong Zhao; Yitung Chen (Annals of Nuclear Energy, 2024)

Evaluating the phase evolution of CMIP GCMs for agricultural climate-change impact assessments in China - Linlin Yao; Qian Tan; Guanhui Cheng; Shuping Wang; Bingming Chen (Agricultural and Forest Meteorology, 2024)

Correction: Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Towards automatic urban tree inventory: Enhancing tree instance segmentation via moving object removal and a chord length-based DBH estimation approach - Wai Yi Chau; Jun Kang Chow; Tun Jian Tan; Jimmy WU; Mei Ling Leung; Pin Siang Tan; Siu Wai Chiu; Billy Chi Hang Hau; Hok Chuen Cheng; Yu-Hsing Wang (Computers and Electronics in Agriculture, 2024)

Novel multi-degree-of-freedom force–displacement mixed control framework for low loading rate substructure hybrid testing - Yucai Chen; Guoshan Xu; Huimeng Zhou; Cheng Chen; Shangyi Zhu; Zhiguo Sun; Ping Tan (Soil Dynamics and Earthquake Engineering, 2024)

A paleomagnetic study of the late paleocene sedimentary succession in the xigaze forearc basin, southern tibet, and its tectonic implications - Xingduo Ma; Yalin Li; Xiaodong Tan; Shuai Li; Jianbo Cheng; Zijian Li; Song Huang (Journal of Asian Earth Sciences, 2024)

Corrigendum to “Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the industrial revolution recorded by high-resolution stalagmites” [Global and Planetary Chang, 232 (2024) 104337] - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Photocorrosion suppression of copper sulfide via hybridization with amino-functionalized metal–organic framework for natural sunlight-driven photocatalysis - Zewei Liu; Cheng Tang; Zepeng Yu; Shu Li; Chengzhang Deng; Sijie Liu; Zhiqiang Wu; Rong Tan (Fuel, 2024)

Isolation and characterization of Bifidobacterium spp. from breast milk with different human milk oligosaccharides utilization and anti-inflammatory capacity - Xinxin Ma; Jianhui Mo; Lu Shi; Yue Cheng; Jiayu Feng; Jiale Qin; Wanghong Su; Jia Lv; Shaoru Li; Qiang Li; Hui Tan; Bei Han (Food Research International, 2024)

A novel cascade catalysis for one-pot enzymatically modified isoquercitrin (EMIQ) conversion from rutin and sucrose using rationally designed gradient temperature control - Yu-Fan Zhan; Zhuo-Hao Meng; Cheng-Hai Yan; Min Tan; Marriam Khurshid; Yi-Jiangcheng Li; Shao-Jun Zheng; Jun Wang (Food Chemistry, 2024)

YAP O-GlcNAcylation contributes to corneal epithelial cell ferroptosis under cigarette smoke exposure - Meng-Yuan Zhang; Ting-Ting Wei; Cheng Han; Cheng-Ye Tan; Tian-Hua Xie; Jiping Cai; Yong Yao; Lingpeng Zhu (Environmental Pollution, 2024)

Near-surface reconstruction strategy stabilizing high-voltage redox reactions in single crystal Li-rich Mn-based oxides - Huan Zhou; Wenhua Cheng; Qingcui Liu; Wei Wang; Weilu Zhang; Zhouliang Tan; Juan Ding; Yudai Huang (Chemical Engineering Journal, 2024)

In-situ and ex-situ preparation of Bi2S3 on the BiVO4/TiO2 to construct Bi2S3/BiVO4/TiO2 heterojunction for efficient Cr(VI) reduction - Hongwei Wang; Yuwei Zhu; Mahesh Kumar Joshi; Yuan Cheng; Pengyu Zhang; Minghui Tan; Renhong Yu; Zhiping Mao; Xinli Li (Chemical Engineering Journal, 2024)

Enhanced CO2-to-CH4 conversion via grain boundary oxidation effect in CuAg systems - Lei Wang; Xue Yao; Yi Xiao; Cheng Du; Xiyang Wang; Dmitry Akhmetzyanov; Zuolong Chen; Youchao Teng; Tao Guo; Yongzan Zhou; Joel P. Mills; Ning Chen; et al. (Chemical Engineering Journal, 2024)

Endocytic pathways and metabolic fate of colloidal bismuth subcitrate in human renal cells - Yang Yang; Mengfei Tan; Jinbin Cui; He Liu; Hezhang Meng; Xiaju Cheng; Yangyun Wang; Yong Wang; Leshuai W. Zhang (Chemico-Biological Interactions, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Topic modeling discovers trending topics in global research on the ecosystem impacts of microplastics - Kailin Gong; Shuangqing Hu; Wei Zhang; Cheng Peng; Jiaqi Tan (Environmental Geochemistry and Health, 2024)

Lithium isotope systematics in an endorheic saline lacustrine system: Insights from Qinghai Lake, China - Yin Li; Yang-Yang Wang; Fancui Kong; Haicheng Wei; Jack Geary Murphy; Dong-Bo Tan; Jing Chen; Jing Lei; Yigan Lu; Cheng-Long Yu; Yilin Xiao (Applied Geochemistry, 2024)

Highly efficient electrochemiluminescent properties of porphyrin-based metal-organic framework Zn-TCPP and its immunoassay application to the detection of ochratoxin A - Xiaolin Fan; Cheng Tan; Xiao Mei; Jun Ma; Kang Wu; Anping Deng; Xinjian Feng; Jianguo Li (Analytica Chimica Acta, 2024)

Diversity and phylogeny of demosponge fauna in the abyssal nodule fields of the eastern Clarion‐Clipperton Zone, Pacific Ocean - Swee‐Cheng Lim; Helena Wiklund; Guadalupe Bribiesca‐Contreras; Adrian G. Glover; Thomas G. Dahlgren; Koh‐Siang Tan (Zoologica Scripta, 2024)
More than 7000 demosponge species have been described to date globally but Plenaster craigi , the most common and abundant species in the eastern CCZ, represents a new family, and possibly in a new order. Interestingly, P. craigi and members of the families Polymastiidae and Hamacanthidae, all filter‐feeding demosponge species, are far more abundant in nodule fields than the carnivorous sponges (Cladorhizidae) which were widely known to be the most dominant demosponge group in the abyssal depths. Lastly, it is highly likely that such tiny demosponges are present in other habitats. They might have been overlooked and/or ignored by sponge researchers in the past due to their tiny size and nondescript habitus. These demosponges could be distinct new species, not juveniles or indeterminates and warrant full taxonomic treatment.

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

DC_OCEAN: an open-source algorithm for identification of duplicates in ocean databases - Xinyi Song; Zhetao Tan; Ricardo Locarnini; Simona Simoncelli; Rebecca Cowley; Shoichi Kizu; Tim Boyer; Franco Reseghetti; Guilherme Castelao; Viktor Gouretski; Lijing Cheng (Frontiers in Marine Science, 2024)
A high-quality hydrographic observational database is essential for ocean and climate studies and operational applications. Because there are numerous global and regional ocean databases, duplicate data continues to be an issue in data management, data processing and database merging, posing a challenge on effectively and accurately using oceanographic data to derive robust statistics and reliable data products. This study aims to provide algorithms to identify the duplicates and assign labels to them. We propose first a set of criteria to define the duplicate data; and second, an open-source and semi-automatic system to detect duplicate data and erroneous metadata. This system includes several algorithms for automatic checks using statistical methods (such as Principal Component Analysis and entropy weighting) and an additional expert (manual) check. The robustness of the system is then evaluated with a subset of the World Ocean Database (WOD18) with over 600,000 in-situ temperature and salinity profiles. This system is an open-source Python package (named DC_OCEAN) allowing users to effectively use the software. Users can customize their settings. The application result from the WOD18 subset also forms a benchmark dataset, which is available to support future studies on duplicate checks, metadata error identification, and machine learning applications. This duplicate checking system will be incorporated into the International Quality-controlled Ocean Database (IQuOD) data quality control system to guarantee the uniqueness of ocean observation data in this product.

Paleolatitude of Mafic Dykes in the Xiugugabu ophiolite: Implications for the intraoceanic Trans-Tethyan subduction zone and multistage India-Eurasia collision - Xingduo Ma; Xiaodong Tan; Yalin Li; Shuai Li; Zijian Li; Yongyong Jia; Siqi Xiao; Jianbo Cheng (Tectonophysics, 2024)

Efficient recovery and utilization of phosphorus from sewage sludge via alkalinous fenton-like oxidation with pyrolysis-modified red mud: Full resource utilization attempt - Jinshan Tang; Zhiliang Cheng; Shengmei Tan; Nanchuan Song; Zejun Wei; Yuan Liu (Journal of Cleaner Production, 2024)

Effects of municipal solid waste component on gasification performance and chromium partitioning behavior under CO2 atmosphere - Yan Zhao; Cheng Zhang; Lun Ma; Junchen Li; Zhao Zheng; Peng Tan; Qingyan Fang; Gang Chen (Chemical Engineering Journal, 2024)

Inflammatory microenvironment-responsive “double-insurance” nanoreactors for accurate sonodynamic-chemodynamic therapy of rheumatoid arthritis - Sui Zhou; Meng-Wen Ma; Shao-Zhe Cai; Kai-Lin He; Lin-Fang Tan; Kai Cheng; Jin-Xuan Fan; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2024)

Lag in pollutant removal efficiency relative to microbial community dynamics in a denitrifying phosphorus removal bioreactor - Xue Wang; Lirong Cheng; Qiuyang Tan; Yuzi Xing; Haoming Wu; Qi Tian; Yaoxin Zhang; Lei Zheng (Chemical Engineering Journal, 2024)

Current status of molecular rice breeding for durable and broad-spectrum resistance to major diseases and insect pests - Xiaoyan Cheng; Guohua Zhou; Wei Chen; Lin Tan; Qishi Long; Fusheng Cui; Lei Tan; Guoxing Zou; Yong Tan (Theoretical and Applied Genetics, 2024)
In the past century, there have been great achievements in identifying resistance ( R ) genes and quantitative trait loci (QTLs) as well as revealing the corresponding molecular mechanisms for resistance in rice to major diseases and insect pests. The introgression of R genes to develop resistant rice cultivars has become the most effective and eco-friendly method to control pathogens/insects at present. However, little attention has been paid to durable and broad-spectrum resistance, which determines the real applicability of R genes. Here, we summarize all the R genes and QTLs conferring durable and broad-spectrum resistance in rice to fungal blast, bacterial leaf blight (BLB), and the brown planthopper (BPH) in molecular breeding. We discuss the molecular mechanisms and feasible methods of improving durable and broad-spectrum resistance to blast, BLB, and BPH. We will particularly focus on pyramiding multiple R genes or QTLs as the most useful method to improve durability and broaden the disease/insect spectrum in practical breeding regardless of its uncertainty. We believe that this review provides useful information for scientists and breeders in rice breeding for multiple stress resistance in the future.

A novel neuroprotective method against ischemic stroke by accelerating the drainage of brain interstitial fluid - Jingge Lian; Liu Yang; Hanbo Tan; Shaoyi Su; Leonor Serrano Lopes; Fangxiao Cheng; Junhao Yan; Yu Fu; Wanyi Fu; Zhaoheng Xie; Jianfei Sun; Jicong Zhang; et al. (Science China Life Sciences, 2024)

Mechanistic Insights and Potential Therapeutic Implications of NRF2 in Diabetic Encephalopathy - Xin Cheng; Yejun Tan; Hongli Li; Zhen Zhang; Shan Hui; Zheyu Zhang; Weijun Peng (Molecular Neurobiology, 2024)

Signaling molecules in the microenvironment of hepatocellular carcinoma - Wanjin Chen; Ming Tan; Hui Zhang; Tingting Gao; Jihua Ren; Shengtao Cheng; Juan Chen (Functional & Integrative Genomics, 2024)

Cortical microstructural alterations in different stages of Parkinson’s disease - Xueqin Bai; Tao Guo; Xiaojun Guan; Cheng Zhou; Jingjing Wu; Haoting Wu; Xiaocao Liu; Chengqing Wu; Jingwen Chen; Jiaqi Wen; Jianmei Qin; Sijia Tan; et al. (Brain Imaging and Behavior, 2024)

Retraction Note: Comprehensive evaluation of water resources carrying capacity and analysis of obstacle factors in Weifang City based on hierarchical cluster analysis-VIKOR method - Haiyan Yang; Yinan Tan; Xiaobo Sun; Xiaowen Cheng; Guangqi Liu; Guangyu Zhou (Environmental Science and Pollution Research, 2024)

Inverting continuous in-tunnel passive seismic data for velocity structure mapping ahead of the TBM cutterhead - Enhedelihai Alex Nilot; Yunyue Elita Li; Gang Fang; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2024)

Insights gained into the injury mechanism of drug and herb induced liver injury in the hepatic microenvironment - Xiaomeng Zhang; Qi Geng; Lin Lin; Lulu Zhang; Changqi Shi; Bin Liu; Lan Yan; Zhiwen Cao; Li Li; Peipei Lu; Yong Tan; Xiaojuan He; et al. (Toxicology, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Cytotoxic xanthanolide sesquiterpenes from the fruits of Xanthium italicum Moretti - Yu-Tong Li; Cheng-Yong Tan; Jiang Fu; Hai-Qiang Wang; Yun-Bao Liu; Shuang-Gang Ma; Yong Li; Jing Qu; Shi-Shan Yu (Phytochemistry, 2024)

Iron (hydr)oxides-induced activation of sulfite for contaminants degradation: The critical role of structural Fe(III) - Cheng Wang; Wenfeng Tan; Xionghan Feng (Journal of Hazardous Materials, 2024)

Recovery of iron from copper slag using jatropha oil as a green reductant: Investigation of pyrolysis analysis, reaction kinetic and artificial neural network model prediction - Chaowei Ma; Cheng Tan; Yong Yu; Dongfang Li; Jianhang Hu; Hua Wang (Fuel, 2024)

Enhanced stability and antibacterial efficacy of edible oleogels-in-water high internal phase emulsions prepared from soybean lipophilic protein - Yuanda Sun; Pengjing Zhang; Yitong Hou; Shasha Cheng; Mingqian Tan; Beiwei Zhu; Haitao Wang (Food Hydrocolloids, 2024)

Brownification increases the abundance of microorganisms related to carbon and nitrogen cycling in shallow lakes - Yuzi Xing; Lirong Cheng; Lei Zheng; Haoming Wu; Qiuyang Tan; Xue Wang; Qi Tian (Environmental Research, 2024)

Nanoplatforms derived from iron dextran combined with ascorbic acid for enhanced photothermal-chemodynamic therapy of tumors - Bin Zhang; Xiao-Lin Hou; Xiao-Ting Xie; Lin-Fang Tan; Meng Guan; Dong-Hui Zhao; Sui Zhou; Kai Cheng; Jin-Xuan Fan; Bo Liu (Chemical Engineering Journal, 2024)

Bifunctional halloysite nanotube-based Ripk1 siRNA delivery system rescues cognitive impairment by targeting amyloid β plaques for clearance and reducing necrotic neurons in Alzheimer’s disease mice - Linmei Wu; Shuo Tan; Yizhu Yan; Lianghao Zhu; Zhaoyuan Wu; Zhihong Liu; Qiang Cheng; Qiuhao Qu; Xinyu Li; Qi Zhang; Jiayi Liu; Jun Chang; et al. (Chemical Engineering Journal, 2024)

Outdoor tubular photobioreactor microalgae-microorganisms biofilm treatment of municipal wastewater: Enhanced heterotrophic assimilation and synergistic aerobic denitrogenation - Pan Li; Yajun Luo; Jiansong Tian; Yiwei Cheng; Shiji Wang; Xin An; Jingxian Zheng; Heng Yan; Hongtao Duan; Jin Zhang; Zhicheng Pan; Yangwu Chen; et al. (Bioresource Technology, 2024)

Precise modelling and operation characteristics analysis of the small helium-xenon gas cooled reactor power system with the air heat sink - Haoyang Liao; Fulong Zhao; Yang Ming; Kun Cheng; Xiaoyu Wang; Sichao Tan; Ruifeng Tian (Annals of Nuclear Energy, 2024)

Epoxy resin coatings doped with layered double hydroxide for enhanced anti-permeation performance - Hanhai Dong; Yixuan Qiao; Kaiqi Yang; Yongqian Zhen; Wei Tan; Qingli Cheng; Yang Wang (Applied Clay Science, 2024)

Side-Scan Sonar Image Generator Based on Diffusion Models for Autonomous Underwater Vehicles - Feihu Zhang; Xujia Hou; Zewen Wang; Chensheng Cheng; Tingfeng Tan (Journal of Marine Science and Engineering, 2024)
In the field of underwater perception and detection, side-scan sonar (SSS) plays an indispensable role. However, the imaging mechanism of SSS results in slow information acquisition and high complexity, significantly hindering the advancement of downstream data-driven applications. To address this challenge, we designed an SSS image generator based on diffusion models. We developed a data collection system based on Autonomous Underwater Vehicles (AUVs) to achieve stable and rich data collection. For the process of converting acoustic signals into image signals, we established an image compensation method based on nonlinear gain enhancement to ensure the reliability of remote signals. On this basis, we developed the first controllable category SSS image generation algorithm, which can generate specified data for five categories, demonstrating outstanding performance in terms of the Fréchet Inception Distance (FID) and the Inception Score (IS). We further evaluated our image generator in the task of SSS object detection, and our cross-validation experiments showed that the generated images contributed to an average accuracy improvement of approximately 10% in object detection. The experimental results validate the effectiveness of the proposed SSS image generator in generating highly similar sonar images and enhancing detection accuracy, effectively addressing the issue of data scarcity.

Multi-emitter metal-organic frameworks as ratiometric luminescent sensors for food contamination and spoilage detection - Shanghua Xing; Shasha Cheng; Mingqian Tan (Critical Reviews in Food Science and Nutrition, 2024)

Corrigendum to “Detrimental effect of bisphenol S in mouse germ cell cyst breakdown and primordial follicle assembly” [Chemosphere. 2021 Feb;264(Pt 1):128445] - Wen-Xiang Liu; Farini Donatella; Shao-Jing Tan; Wei Ge; Jun-Jie Wang; Xiao-Feng Sun; Shun-Feng Cheng; Wei Shen (Chemosphere, 2024)

Efficient catalytic oxidation of formaldehyde by defective g–C3N4–anchored single-atom Pt: A DFT study - Zhao Zheng; Cheng Zhang; Junchen Li; Dingli Fang; Peng Tan; Qingyan Fang; Gang Chen (Chemosphere, 2024)

Combined exposure of PS-MPs with NaF induces Sertoli cell death and dysfunction via ferroptosis and apoptosis - Tan Ma; Huixian Cheng; Liang Kong; Chenghao Shen; Haibo Jin; Hongliang Li; Chun Pan; Jingyan Liang (Toxicology, 2024)

Blockchain for urban governance: Enhancing trust in smart city systems with advanced techniques - Xiangqian Zhu; Zhao Chen; Tan Cheng; Chengyu Yang; Donghui Wu; Yanmin Wu; Hong Wang (Sustainable Cities and Society, 2024)

Numerical prediction for vertical dynamic anti-sinking performance of underwater vehicle - Kunyu Han; Xide Cheng; Zuyuan Liu; Chenran Huang; Kangli Tan (Ocean Engineering, 2024)

Insight into the effect of exposed crystal facets of anatase TiO2 on HCHO catalytic oxidation of Mn-Ce/TiO2 - Zhao Zheng; Cheng Zhang; Junchen Li; Dingli Fang; Peng Tan; Qingyan Fang; Gang Chen (Journal of Hazardous Materials, 2024)

Dual pathways of aragonite-to-calcite transformation in stalagmites: Implications for paleoclimate reconstructions - Rui Zhang; Haiwei Zhang; Christoph Spötl; Hai Cheng; Yanjun Cai; Carlos Pérez-Mejías; Xiyu Dong; Lijuan Sha; Youwei Li; Liangcheng Tan; Jingjie Zang; Xunlin Yang; et al. (Geochimica et Cosmochimica Acta, 2024)

Impact of thermal ultrasound on enzyme inactivation and flavor improvement of sea cucumber hydrolysates - Yi-chao Cheng; Dan-li Jin; Wen-tao Yu; Bo-yang Tan; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2024)

Screening and identification of selenium-enriched purine-lowering Lactobacillus plantarum and Lactococcus lactis with high stress tolerance and antioxidant capacity - Jia-Jun Liao; Cai-Yue Tan; Lan Liang; Yi-Zhen Luo; Hong-Lin Li; Yan-Yi Chen; Xiao-Dong Pei; Cheng-Hua Wang (Food Bioscience, 2024)

Manipulated C5aR1 over/down-expression associates with IL-6 expression during bacterial inflammation in half-smooth tongue sole (Cynoglossus semilaevis) - Zhendong Wu; Shaoqing Zang; Wenwen Wang; Suxu Tan; Qian Xu; Xuejie Chen; Sen Han; Jie Ma; Kunpeng Shi; Ningning Wang; Jiayu Cheng; Zhenxia Sha (Fish & Shellfish Immunology, 2024)

Catalytic-separation technology for highly efficient removal of emerging pollutants, desalination, and antimicrobials: A new strategy for complex wastewater treatment - Ming Yi; Qi Xia; Jiale Tan; Jiangwei Shang; Xiuwen Cheng (Chemical Engineering Journal, 2024)

Establishment of an efficient regeneration system and in vitro polyploid induction based on the bulblet centre in Lilium rosthornii Diels - Yongyao Fu; Xiaomeng Liang; Hong Zhang; Shiyuan Cheng; Anqin Li; Minjing Liao; Lang Tan; Liping Yang; Xiangying Qi (In Vitro Cellular & Developmental Biology - Plant, 2024)

Halobacterium yunchengense sp. nov., Natronomonas amylolytica sp. nov., Halorientalis halophila sp. nov., Halobellus salinisoli sp. nov., halophilic archaea isolated from a saline lake and inland saline soil - Ling Cui; Yao Hu; Xin-Xin Li; Xue Ma; Mu Cheng; Shun Tan; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Methionine restriction diets: Unravelling biological mechanisms and enhancing brain health - Yi Liu; Jingjing Guo; Hao Cheng; Juan Wang; Yanfeng Tan; Jingjing Zhang; Hongxun Tao; Hongyan Liu; Jianbo Xiao; Dashi Qi; Xinyu Mei (Trends in Food Science & Technology, 2024)

Machine learning in modelling the urban thermal field variance index and assessing the impacts of urban land expansion on seasonal thermal environment - Maomao Zhang; Shukui Tan; Cheng Zhang; Enqing Chen (Sustainable Cities and Society, 2024)

Overexpression of the grape β-galactosidase gene VvBGAL3 delays the softening and extends the shelf life of tomato fruits - Shanshan He; Hongli Wei; Zhirui Xue; Meng Li; Jiannan Xie; Jiakang Qian; Xing Chen; Zhiqian Li; Chang He; Bin Tan; Xianbo Zheng; Jun Cheng; et al. (Postharvest Biology and Technology, 2024)

Hydrophobic nanosheet silicalite-1 zeolite for iodine and methyl iodide capture - Qian Zhao; Xin Li; Guangyuan Chen; Zeru Wang; Chuan Tan; Cheng Liu; Hao Zou; Jing Ma; Lin Zhu; Tao Duan (Journal of Hazardous Materials, 2024)

Functional properties and structure of soluble dietary fiber obtained from rice bran with steam explosion treatment - Xin-Yi Tian; Jian-Fu Liu; Cong-Cong Qiao; Zhuo Cheng; Na-Na Wu; Bin Tan (Journal of Cereal Science, 2024)

Structure, thermal stability, physicochemical and functional characteristics of insoluble dietary fiber obtained from rice bran with steam explosion treatment: Effect of different steam pressure and particle size of rice bran - Xin-Yi Tian; Jian-Fu Liu; Zhuo Cheng; Na-Na Wu; Bin Tan (Food Research International, 2024)

Deep insights into the biofilm formation mechanism and nitrogen-transformation network in a nitrate-dependent anaerobic methane oxidation biofilm - Zhi-Cheng Zhao; Sheng-Qiang Fan; Yang Lu; Xin Tan; Lu-Yao Liu; Xiao-Wei Wang; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Environmental Research, 2024)

Single-atom Al precisely modulate the strain of Pt3Co intermetallic for superior oxygen catalytic performance - Wei Wu; Wei Qu; Zichen Wang; Yangyang Tan; Runzhe Chen; Suhao Chen; Haifeng Lv; Jun Zhong; Niancai Cheng (Chemical Engineering Journal, 2024)

Students’ thermal comfort and cognitive performance in fan-assisted naturally ventilated classrooms in tropical Singapore - Chao Cen; Siyu Cheng; Erna Tan; Nyuk Hien Wong (Building and Environment, 2024)

Weak geostrophic wind driven ventilation in street canyons with trees and green walls: Cooperating or opposing dispersions of airborne pollutants? - Yu-Fei Tang; Hao Chen; Ming Yang; Zhi-Cheng Tan; Fu-Yun Zhao; Jiang-Hua Guo; Yueping Fang (Building and Environment, 2024)

A rapid and efficient Agrobacterium-mediated transient transformation system in grape berries - Jiannan Xie; Chang He; Zhiqian Li; Meng Li; Shanshan He; Jiakang Qian; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Jidong Li; Jiancan Feng; et al. (Protoplasma, 2024)

Cyanidin-3-O-glucoside protects Zearalenone-induced in vitro maturation disorders of porcine oocytes by alleviating NOX4-dependent oxidative stress and endoplasmic reticulum stress in cumulus cells - Xiuxiu Li; Yu Tian; Ning Zuo; Jiatian Tang; Shunfeng Cheng; Lan Li; Jinghe Tan; Jianxin Zhang; Wei Shen (Chemosphere, 2024)

National-scale 10 m annual maize maps for China and the contiguous United States using a robust index from Sentinel-2 time series - Yingze Huang; Bingwen Qiu; Peng Yang; Wenbin Wu; Xuehong Chen; Xiaolin Zhu; Shuai Xu; Laigang Wang; Zhanjie Dong; Jianyang Zhang; Joe Berry; Zhenghong Tang; et al. (Computers and Electronics in Agriculture, 2024)

Nitrate-dependent anaerobic methane oxidation coupled to Fe(III) reduction as a source of ammonium and nitrous oxide - Xin Tan; Yang Lu; Wen-Bo Nie; Paul Evans; Xiao-Wei Wang; Cheng-Cheng Dang; Xuan Wang; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Water Research, 2024)

Understanding the removal of heavy metals from stormwater runoff in permeable pavement system - Yujie Sun; Meipeng Jian; Yu Cheng; Changyi Huang; Jinxi Li; Zhihao Liu; Chaohong Tan; Ziyang Zhang; Xiaoran Zhang; Haiyan Li (Science of The Total Environment, 2024)

Absorption characteristics and molecular mechanism of a low viscosity iron-based ionic liquid for removing H2S - Zhonghao Li; Zhou Feng; Hongwei Jin; Kangkang Li; Hongzhi Xia; Shiqi Qu; Sujuan Ye; Huanong Cheng; Qingli Wei; Yugang Li; Xinshun Tan; Shiqing Zheng (Journal of Environmental Chemical Engineering, 2024)

Promising membrane photobioreactor for continuous flow treatment of Low C/N wastewater: Treating process, community structure, and cooperation mechanism - Junjie Li; Xin Li; Heng Yan; Hongtao Duan; Jin Zhang; Houzhen Zhou; Yangwu Chen; Yiwei Cheng; Zhouliang Tan (Journal of Environmental Chemical Engineering, 2024)

Catalytic oxidation of formaldehyde by MnOx-decorated anatase TiO2{001}: Investigation of the effect of calcination temperature on catalytic activity and reaction mechanism - Zhao Zheng; Cheng Zhang; Junchen Li; Yan Zhao; Dingli Fang; Ao Han; Peng Tan; Qingyan Fang; Gang Chen (Journal of Environmental Chemical Engineering, 2024)

An in-depth revelation of a novel facilitation mechanism of H2O on the NH3-SCR reaction of Mn-Ce/TiO2 catalyst with exposed anatase {001} facets - Junchen Li; Cheng Zhang; Dingli Fang; Zhao Zheng; Yan Zhao; Peng Tan; Qingyan Fang; Gang Chen (Fuel, 2024)

Novel chitosan-modified biochar prepared from a Chinese herb residue for multiple heavy metals removal: Characterization, performance and mechanism - Chengjiu Wang; Jixu Qiao; Jiandan Yuan; Zhentao Tang; Tianzhe Chu; Ruifeng Lin; Hongting Wen; Chuan Zheng; Hulan Chen; Haijiao Xie; Cheng Peng; Yuzhu Tan (Bioresource Technology, 2024)

Data analysis and preprocessing techniques for air quality prediction: a survey - Chengqing Yu; Jing Tan; Yihan Cheng; Xiwei Mi (Stochastic Environmental Research and Risk Assessment, 2024)

Tandem transcription factors PpNAC1 and PpNAC5 synergistically activate the transcription of the PpPGF to regulate peach softening during fruit ripening - Langlang Zhang; Xiaofei Wang; Kang Dong; Bin Tan; Xianbo Zheng; Xia Ye; Wei Wang; Jun Cheng; Jiancan Feng (Plant Molecular Biology, 2024)

Overexpression of cassava melatonin receptor PMTR1 plays dual roles in development under light and dark conditions in Arabidopsis - Xiao Cheng; Yu Zheng; Xinyu Liu; Lunhui Xu; Shiqin An; Yinghao Liu; Mengting Tan; Yunxie Wei; Haitao Shi (Plant Cell Reports, 2024)

Effects of experimental warming on competition between Rhopalosiphum padi and Sitobion avenae mediated by plant water content - Weiwei Li; Yang Wang; Coline C. Jaworski; Yumeng Cheng; Jin Miao; Julian Chen; Xiaoling Tan (Journal of Pest Science, 2024)

COVID-19 in Systemic Lupus Erythematosus patients treated with belimumab: a retrospective clinical study - Yinlan Wu; Yanhong Li; Tong Wu; Deying Huang; Jianhong Wu; Weihua Zhang; Xuejun Jiang; Chaoqiong Yao; Xiuping Liang; Lu Cheng; Zehui Liao; Fang Xu; et al. (Immunologic Research, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

New Record Ocean Temperatures and Related Climate Indicators in 2023 - Lijing Cheng; John Abraham; Kevin E. Trenberth; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Fujiang Yu; Ricardo Locarnini; John Fasullo; Fei Zheng; Yuanlong Li; et al. (Advances in Atmospheric Sciences, 2024)
The global physical and biogeochemical environment has been substantially altered in response to increased atmospheric greenhouse gases from human activities. In 2023, the sea surface temperature (SST) and upper 2000 m ocean heat content (OHC) reached record highs. The 0–2000 m OHC in 2023 exceeded that of 2022 by 15 ± 10 ZJ (1 Zetta Joules = 10 21 Joules) (updated IAP/CAS data); 9 ± 5 ZJ (NCEI/NOAA data). The Tropical Atlantic Ocean, the Mediterranean Sea, and southern oceans recorded their highest OHC observed since the 1950s. Associated with the onset of a strong El Niño, the global SST reached its record high in 2023 with an annual mean of ∼0.23°C higher than 2022 and an astounding > 0.3°C above 2022 values for the second half of 2023. The density stratification and spatial temperature inhomogeneity indexes reached their highest values in 2023.

Application of microbially induced calcium carbonate precipitation (MICP) process in concrete self-healing and environmental restoration to facilitate carbon neutrality: a critical review - Junjun Chang; Dongyang Yang; Cheng Lu; Zhitao Shu; Shengjiong Deng; Liwei Tan; Shaoqing Wen; Ke Huang; Pengchang Duan (Environmental Science and Pollution Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Fabrication of Carbon Dots with Singlet Oxygen Generation and Their Potential Photodynamic Therapy Applications - Pengli Zuo; Jun Peng; Yuyang Yao; Wei Tan; Lan Cheng; Jinyu Zhang; Xiuhua Lu (Journal of Fluorescence, 2024)

Density functional theory-based screening of Ti4C3O2-loaded single atoms for efficient selective catalytic oxidation of formaldehyde - Zhao Zheng; Cheng Zhang; Junchen Li; Dingli Fang; Peng Tan; Qingyan Fang; Gang Chen (Chemosphere, 2024)

Quantifying tunneling risks ahead of TBM using Bayesian inference on continuous seismic data - Gang Fang; Enhedelihai Alex Nilot; Yunyue Elita Li; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2024)

Modeling pipe-soil interaction under surface loading using material point method - Tian-Cheng Xie; Hong-Hu Zhu; Dao-Yuan Tan; Sanjay Kumar Shukla (Tunnelling and Underground Space Technology, 2024)

Reconstructing atmospheric 129I deposition over 170 years with the varved sediment in the Sihailongwan Maar Lake, northeast China - Luyuan Zhang; Ning Chen; Xiaolin Hou; Yongming Han; Tong Zhang; Dewen Lei; Weijian Zhou; Zhisheng An; Peng Cheng; Jianghu Lan; Liangcheng Tan; Qi Liu; et al. (Science of The Total Environment, 2024)

Effects of remediation agents on rice and soil in toxic metal(loid)s contaminated paddy fields: A global meta-analysis - Meng Liu; Ruiqing Xu; Xuedan Cui; Daibing Hou; Pengjie Zhao; Yanzhao Cheng; Yujie Qi; Guilan Duan; Guodong Fan; Aijun Lin; Xiao Tan; Yong Xiao (Science of The Total Environment, 2024)

Unlocking sustainable resource management: A comprehensive SWOT and thematic analysis of FinTech with a focus on mineral management - Mehrbakhsh Nilashi; Rabab Ali Abumalloh; Ooi Keng-Boon; Garry Wei-Han Tan; Tat-Huei Cham; Eugene Cheng-Xi Aw (Resources Policy, 2024)

Integrated management of abatement technology investment and resource extraction - Jianxin Guo; Xianchun Tan; Kaiwei Zhu; Yonglong Cheng (Resources Policy, 2024)

Overexpressing peach PpePAO1 gene improves the nutrient value of tomato and enhances resistance against Botrytis cinerea - Zhenguo Cui; Yabo Jiang; Yang Chen; Xin Cheng; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Zhiqian Li; Xianbo Zheng; Jiancan Feng; et al. (Postharvest Biology and Technology, 2024)

Mid-Holocene hydroclimatic change and hurricane activity in Central America recorded by an Isla de Mona Stalagmite - Huiru Tang; Liangcheng Tan; Yongli Gao; Jingjie Zang; Le Ma; Yanzhen Li; R. Lawrence Edwards; Hai Cheng; Ashish Sinha; Xiqian Wang; Xing Cheng; Ángel A. Garcia; et al. (Marine Geology, 2024)

Efficient degradation of tetracycline by activated peroxymonosulfate with high permeate flux FeTiOx reactive ceramic membrane: Membrane preparation, real wastewater application, and mechanism insight - Peng Chen; Zhiliang Cheng; Liping Zhang; Shengmei Tan; Jinyu Sun; Jialu Wang; Feifei Duan; Anke Du; Siqi Li (Journal of Water Process Engineering, 2024)

Comprehensive effect of increased calcium content in coal on the selenium emission from coal-fired power plants: Combined laboratory and field experiments - Yan Zhao; Cheng Zhang; Lun Ma; Shenghui Yu; Junchen Li; Peng Tan; Qingyan Fang; Guangqian Luo; Hong Yao; Gang Chen (Journal of Hazardous Materials, 2024)

Enhancing high-density microalgae cultivation via exogenous supplementation of biostimulant derived from onion peel waste for sustainable biodiesel production - Uganeeswary Suparmaniam; Man Kee Lam; Jun Wei Lim; Hemamalini Rawindran; Yeek Chia Ho; Inn Shi Tan; Jibrail Kansedo; Steven Lim; Yoke Wang Cheng; Salman Raza Naqvi (Journal of Environmental Management, 2024)

Oral polysaccharide-coated liposome-modified double-layered nanoparticles containing anthocyanins: preparation, characterization, biocompatibility and evaluation of lipid-lowering activity in vitro - Zhen Cheng; Jiaxin Wang; Yuanyuan Bian; Mingqian Tan; Yi Chen; Yuehua Wang; Bin Li (Food Chemistry, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

Understanding Malaysian consumers perception and acceptability of plant-based alternatives to chicken: Do texture, taste, and environmental impact matter? - Xin Yi Tan; Shi-Hui Cheng (Food and Humanity, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Microbial synergy achieving simultaneous nitrification-denitrification (SND) in salt-tolerant aerobic granular sludge - Jianxun Chen; Zhuodong Yu; Peijin Cheng; Yixiao Tan; Xuan Fan; Xiangyang Xu; Liang Zhu (Journal of Water Process Engineering, 2024)

Spatial distribution, environmental behavior, and health risk assessment of PAHs in soils at prototype coking plants in Shanxi, China: Stable carbon isotope and molecular composition analyses - Xiaofeng Liu; Xin Tan; Xinyang Li; Yuhuan Cheng; Kun Wang (Journal of Hazardous Materials, 2024)

Historical review and synthesis of global carbon neutrality research: A bibliometric analysis based on R-tool - Fenglong Tan; Jun Yang; Cheng Zhou (Journal of Cleaner Production, 2024)

Predicting the impacts of urban development on urban thermal environment using machine learning algorithms in Nanjing, China - Maomao Zhang; Shukui Tan; Jinshui Liang; Cheng Zhang; Enqing Chen (Journal of Environmental Management, 2024)

Paleomagnetic results from the Early–Middle Jurassic rocks in the Tethyan Himalayas and tectonic implications - Shuai Li; Yalin Li; Xiaodong Tan; Alessandro Todrani; Zhongpeng Han; Jianbo Cheng; Siqi Xiao; Xingduo Ma; Zijian Li; Yunchuan Xu; Zihao Wang; Chengshan Wang (Journal of Asian Earth Sciences, 2024)

A five-lump coupled kinetic model for residue hydrodesulfurization in an ebullated bed based on hydrocracking model - Xiaodong Cheng; Hailong Ge; Hexu Ma; Huihong Zhu; Tao Yang; Xiangdong Tan; Shuandi Hou (Fuel, 2024)

Simultaneously promoting CO2 permeability and selectivity of polyethylene oxide membranes via introducing CO2-philic KAUST-7 - Wen Hou; Jun Cheng; Yingyu Tan; Chen Yang; Xufeng Ren; Jinming Xie; Bangjiao Ye; Hongjun Zhang; Junhu Zhou (Fuel, 2024)

High internal phase pickering emulsion with DHA-algal oil stabilized by salmon protein-procyanidin complex and its application in sausages as fat replacer - Entao Chen; Kuiyou Wang; Siyuan Fei; Mingqian Tan; Shasha Cheng (Food Bioscience, 2024)

Enhanced photo-Fenton degradation of dyes under visible light with recyclable γ-Fe2O3/CQDs: Catalyst preparation, performance and mechanism insight - Qian Xu; Qian Xue; Shengmei Tan; Zhiliang Cheng; Xueqiang Qi; Chaoqun Yan (Environmental Pollution, 2024)

Photocatalytic activation of sulfite by maghemite (γ-Fe2O3) for iohexol degradation and alleviation effect of HCO3− on water acidification - Cheng Wang; Shuijing Zhou; Xiaoming Wang; Wenfeng Tan; Xionghan Feng (Environmental Pollution, 2024)

Pectic-AGP is a major form of Arabidopsis AGPs - Li Tan; Jielun Cheng; Liang Zhang; Jason Backe; Breeanna Urbanowicz; Christian Heiss; Parastoo Azadi (Carbohydrate Polymers, 2024)

Genome-based taxonomy of genera Haloarcula and Halomicroarcula, and description of six novel species of Haloarcula - Xue Ma; Yao Hu; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Analysis of Three Delignification Treatments of Corncob Residues for High Cellulosic Ethanol Production - KeKe Cheng; TianMei Wu; XiaoBi Tan; HuiXiong Zhong (BioEnergy Research, 2024)

Association of birthweight and risk of incident dementia: a prospective cohort study - Xiaxuan Huang; Shiqi Yuan; Yitong Ling; Shanyuan Tan; Hongtao Cheng; Anding Xu; Jun Lyu (GeroScience, 2024)

Exploring the antiviral potential of paeonol from medicinal plants: A promising strategy for controlling white spot syndrome virus - Cheng Chen; Chang-Shuai Liang; Xiang-Yu Qu; Peng-Fei Li; Xiao-Ping Tan; Fei Ling; Gao-Xue Wang (Aquaculture, 2024)

Observations of HONO and its precursors between urban and its surrounding agricultural fields: The vertical transports, sources and contribution to OH - Chengzhi Xing; Cheng Liu; Qihua Li; Shanshan Wang; Wei Tan; Tiliang Zou; Zhuang Wang; Chuan Lu (Science of The Total Environment, 2024)

IiAGL6 participates in the regulation of stamen development and pollen formation in Isatis indigotica - Liu Yang; Xin Qiao; Hao-En He; Wei-Wei Yi; Ya-Nan Gao; Xiao-Min Tan; Hao Cheng; Xiao-Fang Hou; Ye-Ye Ma; Hong-Li Wang; Xuan Huang; Yan-Qin Ma; et al. (Plant Science, 2024)

Discovery of ent-labdane derivatives from Andrographis paniculata and their anti-inflammatory activity - Yang Yu; Yang Wang; Lan Ding; Gui-Chun Wang; Hao Geng; Cheng-Yong Tan; Yi Wang; Jin-Song Liu; Guo-Kai Wang (Phytochemistry, 2024)

Highly efficient catalytic O3 oxidation degradation of levofloxacin by peanut shell pyrolysis-modified red mud wastes - Liping Zhang; Zhiliang Cheng; Xuan Zhang; Peng Chen; Shengmei Tan; Facheng Qiu (Journal of Water Process Engineering, 2024)

Ozone exposure affects corneal epithelial fate by promoting mtDNA leakage and cGAS/STING activation - Kai Fan; Nuo Dong; Meichai Fang; Zixun Xiang; Lan Zheng; Mengyuan Wang; Yukuan Shi; Gang Tan; Cheng Li; Yuhua Xue (Journal of Hazardous Materials, 2024)

Modeling of arsenic migration and emission characteristics in coal-fired power plants - Yan Zhao; Cheng Zhang; Lun Ma; Shenghui Yu; Changle Yuan; Junchen Li; Peng Tan; Qingyan Fang; Guangqian Luo; Gang Chen (Journal of Hazardous Materials, 2024)

A multi-layer nanocased model to explain the U-shaped evolution of shale gas permeability at constant confining pressure - Wangxing Cheng; Guanglei Cui; Yuling Tan; Derek Elsworth; Chunguang Wang; Chengxiang Yang; Tianyu Chen; Chuanzhong Jiang (Fuel, 2024)

Insights into ecological effects of fish and shellfish mariculture on microeukaryotic community - Weiwei Liu; Shaowei Wen; Zijun Cheng; Yehui Tan (Environmental Research, 2024)

EtOH-LN cryoembedding workflow to minimize freezing artifact in frozen tissues: A pilot study in preparing tissues compatible with mass spectrometry-based spatial proteomics application - Yong Chiang Tan; Muaatamarulain Mustangin; Nurwahyuna Rosli; Wan Syahira Ellani Wan Ahmad Kammal; Nurismah Md Isa; Teck Yew Low; Pey Yee Lee; Dinesh Kumar Chellappan; Razman Jarmin; Zamri Zuhdi; Azlanudin Azman; Chik Ian; et al. (Cryobiology, 2024)

Numerical simulation for vibration-induced settlement and permanent deformation accumulation in permafrost subgrades of the Qinghai-Tibet Railway - Chen-xuan Tang; Zhan-yuan Zhu; Yong Ma; Zhi Yao; Qiu-tong Tan; Zheng-yu Liu; Jiao Xu; Si-cheng Zheng (Computers and Geotechnics, 2024)

Engineering α-MoO3/TiO2 heterostructures derived from MOFs/MXene hybrids for high-performance triethylamine sensor - Weining Liu; Hairong Li; Dandan Huang; Xi Tan; Mingyang Zhao; Qionglin Cheng; Ming Yi; Qi Ding; Yaqian Ren; Guohan Liu (Chemical Engineering Journal, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Urolithin A Prevents Sleep-deprivation-induced Neuroinflammation and Mitochondrial Dysfunction in Young and Aged Mice - Afzal Misrani; Sidra Tabassum; Zai-yong Zhang; Shao-hua Tan; Cheng Long (Molecular Neurobiology, 2024)

Insights on the NF-κB system in polycystic ovary syndrome, attractive therapeutic targets - Wei Tan; Jie Zhang; Fangfang Dai; Dongyong Yang; Ran Gu; Lujia Tang; Hua Liu; Yan-xiang Cheng (Molecular and Cellular Biochemistry, 2024)

Health risk assessment and potential sources of metals in riparian soils of the Wujiang River, China - Shenwen Cai; Ziwei Shen; Shaoqi Zhou; Qinghe Wang; Junwei Cheng; Xiong Yan; Mingjie Tan; Guojing Tu; Yi Cen (Environmental Geochemistry and Health, 2024)

DNA methylation reprogramming mediates transgenerational diabetogenic effect induced by early-life p,p’-DDE exposure - Shuo Wang; Jingjing Wu; Zhong Chen; Wei Wu; Liping Lu; Yuzhou Cheng; Shuqi Li; Liangjing Chen; Xiaohua Tan; Lei Yang; Charles Wang; Yang Song (Chemosphere, 2024)

Risk characteristics of shellfish toxins in Mytilus unguiculatus around the Zhoushan Islands, East China Sea - Guanchao Zheng; Hanyu Che; Haiyan Wu; Ling Cheng; Yuxiang Deng; Mengmeng Guo; Jixing Peng; Lijuan Liu; Zhijun Tan (Marine Pollution Bulletin, 2024)

Corrigendum to “Sugar-based natural deep eutectic solvent (NADES): Physicochemical properties, antimicrobial activity, toxicity, biodegradability and potential use as green extraction media for phytonutrients” [Sustain. Chem. Pharm. 35 (2023) 101218] - Qi Qi Koh; Yin Leng Kua; Suyin Gan; Khang Wei Tan; Terri Zhuan Ean Lee; Wai Kit Cheng; Harrison Lik Nang Lau (Sustainable Chemistry and Pharmacy, 2024)

Insights into persulfate activation by dicyandiamide-derived carbon for 2,4-dichlorophenol degradation: Roles of nitrogen doping and defective carbon atoms - Dong Cheng; Dezhi Yang; Ying Pan; Yuansen Tan; Runhao Ma; Bo Chen; Feng He (Science of The Total Environment, 2024)

How does ESG performance affect green transformation of resource-based enterprises: Evidence from Chinese listed enterprises - Xiujie Tan; Gufeng Liu; Si Cheng (Resources Policy, 2024)

Occurrence and influencing factors of high groundwater manganese in the oxbow lakes of the middle reaches of Yangtze River - Jiasen Li; Caixiang Zhang; Haoyan Tan; Ming Zeng; Yikang Cheng (Journal of Hydrology, 2024)

Additive-free electroless deposition on graphene/copper foil: Photo-induced and defect-assisted approach for environmentally friendly plating - Hsiao-Chien Chen; Abdul Shabir; Kun-Hua Tu; Cher Ming Tan; Wei-Hao Chiu; Ruei-Cheng Fan; Nilim Akash Baruah (Journal of Environmental Chemical Engineering, 2024)

Simultaneous biodegradation of Teflaro contained wastewater and electricity generation in an air–cathode microbial fuel cell - Peng Cheng; Yingchuan Zhang; Xinlan Ying; Hongli Ma; Yanlei Zhang; Meiru Liu; Muhammad Usman; Xiangping Tan; Liqun Jiang (Fuel, 2024)

Physical, textural and crystallization properties of ground nut oil-based diacylglycerols in W/O margarine system - Wanting Ke; Yee-Ying Lee; Jianqiang Cheng; Chin-Ping Tan; Oi-Ming Lai; Aijun Li; Yong Wang; Zhen Zhang (Food Chemistry, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

Recent advances in the use of MXenes for photoelectrochemical sensors - Adriel Yan Sheng Tan; Hafiz Taimoor Ahmed Awan; Faliang Cheng; Min Zhang; Michelle T.T. Tan; Sivakumar Manickam; Mohammad Khalid; Kasturi Muthoosamy (Chemical Engineering Journal, 2024)

Effective free-standing electrodes with refined structure via sputtering Ti sublayer and altering working pressure for electrocatalytic benzaldehyde hydrogenation - Guanhua Cheng; Jiameng Sun; Yunfei Ran; Fuquan Tan; Wensheng Ma; Zhonghua Zhang (Chemical Engineering Journal, 2024)

Effects of evodiamine on ROS/TXNIP/NLRP3 pathway against gouty arthritis - Yuan Cheng; XiaoPeng Huang; Yi Tang; Juan Li; Yimin Tan; Qianghua Yuan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Ubiquitination-specific protease 7 enhances stemness of hepatocellular carcinoma by stabilizing basic transcription factor 3 - Mingchao Hu; Chengchen Dai; Xieyin Sun; Yinqi Chen; Nuo Xu; Zhaoyi Lin; Shiyu Xu; Chun Cheng; Zhonghua Tan; Saiyan Bian; Wenjie Zheng (Functional & Integrative Genomics, 2024)

Co-processing plastics waste and biomass by pyrolysis–gasification: a review - Peter Nai Yuh Yek; Yi Herng Chan; Shin Ying Foong; Wan Adibah Wan Mahari; Xiangmeng Chen; Rock Keey Liew; Nyuk Ling Ma; Yiu Fai Tsang; Christian Sonne; Yoke Wang Cheng; Yie Hua Tan; Su Shiung Lam (Environmental Chemistry Letters, 2024)

Preliminary Results of the Seismicity Monitoring Experiment around the 2019 Mw5.4 Earthquake Epicenter in the Central South China Sea Basin - Wenfei Gong; Aiguo Ruan; Xiongwei Niu; Zhenjie Wang; Pingchuan Tan; Xiaodong Wei; Wei Wang; Zhengyi Tong; Liqun Cheng; Fansheng Kong; Shaoping Lu; Jianke Fan; et al. (Journal of Earth Science, 2024)

Effects of dietary betaine supplementation on growth performance, feed intake, intestinal histology, lipid metabolism, and immune response of black tiger shrimp (Penaeus monodon) fed diets containing two levels of raw feed attractants - Gui-Lun He; Meng-Lin Shi; Yu-Cheng Liu; Liu-Tong Chen; Xin Chen; Wen-Bo Zhu; Zheng-Bang Chen; Bei-Ping Tan; Shi-Wei Xie (Aquaculture International, 2024)

Chronological features of Heinrich Stadial 2 based on a high-resolution analysis of δ18O stalagmite records from China, and possible links to changes in Atlantic Meridional Overturning Circulation - Yingfang Cui; Hao Xu; Yijia Liang; Kan Zhao; Jianshun Chen; Yongjin Wang; Jiaqi Cong; Hai Cheng; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects of temperature on the migration behaviour of arsenic and chromium in tannery sludge under CO2 gasification - Yan Zhao; Cheng Zhang; Lun Ma; Junchen Li; Peng Tan; Qingyan Fang; Gang Chen (Journal of Hazardous Materials, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

VOCs hyperspectral imaging: A new insight into evaluate emissions and the corresponding health risk from industries - Chengzhi Xing; Cheng Liu; Jinan Lin; Wei Tan; Ting Liu (Journal of Hazardous Materials, 2024)

Synergism of nitrogen removal and greenhouse gases emission reduction in pyrite/biochar-based bioretention system coupled with microbial fuel cell: Performance and mechanism - Yunqing Li; Yinghui Tang; Qiong Wu; Yang He; Zhen Liu; Shaochun Yuan; Qiming Cheng; Xiaoke Lian; Yuqing Tan; Yihong Su; Yao Chen (Journal of Cleaner Production, 2024)

Hydrological reduction and control effect evaluation of sponge city construction based on one-way coupling model of SWMM-FVCOM: A case in university campus - Yuqing Tan; Qiming Cheng; Fengwei Lyu; Fei Liu; Linhao Liu; Yihong Su; Shaochun Yuan; Wenyu Xiao; Zhen Liu; Yao Chen (Journal of Environmental Management, 2024)

Petrogenesis of Miocene high Ba–Sr granitoids from the Central Pamir: Implications for continental growth - Zheng Liu; Hao Liu; Qing-He Yan; He Wang; Shu-Cheng Tan (Journal of Asian Earth Sciences, 2024)

Process optimization, energy consumption analysis, and environmental assessment of total CO2 capture from syngas based on [NEMH][Ac] protic ionic liquid - Zhou Feng; Ning Wang; Xiaohan Li; Zhonghao Li; Kangkang Li; Hongwei Jin; Shiqi Qu; Hongzhi Xia; Huanong Cheng; Xinshun Tan; Shiqing Zheng (International Journal of Greenhouse Gas Control, 2024)

Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the Industrial Revolution recorded by high-resolution stalagmites - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Novel calcium hypochlorite/ferrous iron as an ultrafiltration membrane pretreatment process for purifying algae-laden water - Xiaoxiang Cheng; Wenxin Song; Fengxun Tan; Xinsheng Luo; Xuewu Zhu; Tao Yang; Zhiwei Zhou; Jingtao Xu; Daoji Wu; Heng Liang (Environmental Research, 2024)

Optimizing nitrogen application rate by establishing a unified critical nitrogen dilution curve for maize under different mulching planting patterns - Wenlong Li; Xiaobo Gu; Heng Fang; Tongtong Zhao; Rui Yin; Zhikai Cheng; Chuandong Tan; Zhihui Zhou; Yadan Du (European Journal of Agronomy, 2024)

3D printed composites based on the magnetoelectric coupling of Fe/FeCo@C with multiple heterogeneous interfaces for enhanced microwave absorption - Zhenyu Cheng; Jintang Zhou; Yijie Liu; Jing Yan; Shunan Wang; Jiaqi Tao; kexin Zou; Ruiyang Tan; Zhengjun Yao (Chemical Engineering Journal, 2024)

Functionally separated electronic band engineering via multi-element doping plus high-density defects advances board-temperature-range thermoelectric performance in GeTe - Jianglong Zhu; Xiaobo Tan; Dong Pan; Yanni Luo; Ruiheng Li; Xuri Rao; Ruihuan Cheng; Chengliang Xia; Yue Chen; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Inverse kinetic isotope effect of proton and deuteron permeation through pyridinic N-doped graphene - Jingwen Ba; Jinfan Chen; Renjin Xiong; Jingsong Xu; Haibo Li; Xiayan Yan; Cheng Qin; Rui Li; Qifa Pan; Xinxin Tan; Tao Tang; Xin Xiang; et al. (Chemical Engineering Journal, 2024)

Cross-scale coupling analysis method for OTSG in SFR and its application - Zhenguo Zhang; Xiaochang Li; Sichao Tan; Ruifeng Tian; Kai Liu; Hui Cheng (Annals of Nuclear Energy, 2024)

Research on neutron diffusion equation and nuclear thermal coupling method based on gradient updating finite volume method - Xiangyu Li; Kun Cheng; Tao Huang; Sichao Tan (Annals of Nuclear Energy, 2024)

Intracellular iron accumulation facilitates mycobacterial infection in old mouse macrophages - Stephen K. Kotey; Xuejuan Tan; Owen Fleming; Ramakrishnama Raju Kasiraju; Audrey L. Dagnell; Kyle N. Van Pelt; Janet Rogers; Steven D. Hartson; Nidheesh Thadathil; Ramasamy Selvarani; Rojina Ranjit; Sreemathi Logan; et al. (GeroScience, 2023)
Aging has a significant impact on the immune system, leading to a gradual decline in immune function and changes in the body’s ability to respond to bacterial infections. Non-tuberculous mycobacteria (NTM), also known as atypical mycobacteria or environmental mycobacteria, are commonly found in soil, water, and various environmental sources. While many NTM species are considered opportunistic pathogens, some can cause significant infections, particularly in individuals with compromised immune systems, such as older individuals. When mycobacteria enter the body, macrophages are among the first immune cells to encounter them and attempt to engulf mycobacteria through a process called phagocytosis. Some NTM species, including Mycobacterium avium ( M. avium ) can survive and replicate within macrophages. However, little is known about the interaction between NTM and macrophages in older individuals. In this study, we investigated the response of bone marrow–derived macrophage (BMMs) isolated from young (5 months) and old (25 months) mice to M. avium serotype 4, one of the main NTM species in patients with pulmonary NTM diseases. Our results demonstrated that BMMs from old mice have an increased level of intracellular iron and are more susceptible to M. avium serotype 4 infection compared to BMMs from young mice. The whole-cell proteomic analysis indicated a dysregulated expression of iron homeostasis–associated proteins in old BMMs regardless of mycobacterial infection. Deferoxamine, an iron chelator, significantly rescued mycobacterial killing and phagolysosome maturation in BMMs from old mice. Therefore, our data for the first time indicate that an intracellular iron accumulation improves NTM survival within macrophages from old mice and suggest a potential application of iron-chelating drugs as a host-directed therapy for pulmonary NTM infection in older individuals.

Air particulate pollution exposure associated with impaired cognition via microbiota gut-brain axis: an evidence from rural elderly female in northwest China - Jia Yuan; Hui Tan; Yue Cheng; Xinxin Ma; Sijin Jiang; Xinyao Hou; Shaoru Li; Lu Shi; Pu Li; Hongmei Xu; Jia Lv; Bei Han (Environmental Science and Pollution Research, 2023)

Dietary probiotic Aspergillus niger preparation improves the growth performance, health status, and gut microbiota of white shrimp, Penaeus vannamei - Ann-Chang Cheng; Xianfeng Peng; Wenzhen Chen; Deng-Yu Tseng; Zhigang Tan; Haijun Liu; Zonghua Qin; Rolissa Ballantyne; Chun-Hung Liu (Aquaculture, 2023)

A study of the thermal comfort in urban mountain parks and its physical influencing factors - Yisha Liu; Yumao Lai; Lin Jiang; Bin Cheng; Xinyu Tan; Fanxi Zeng; Shuang Liang; Aoyan Xiao; Xiaowei Shang (Journal of Thermal Biology, 2023)

Characterization of fifteen key genes involved in iron metabolism and their responses to dietary iron sources in yellow catfish Pelteobagrus fulvidraco - Peng-Cheng Xu; Chang-Chun Song; Xiao-Ying Tan; Tao Zhao; Chong-Chao Zhong; Jie-Jie Xu; Yu-Feng Song; Zhi Luo (Journal of Trace Elements in Medicine and Biology, 2023)

Enhanced nitrogen and phosphorus removal by a novel ecological floating bed integrated with three-dimensional biofilm electrode system - Qingyu Wu; Yao Chen; Yang He; Qiming Cheng; Qiong Wu; Zhen Liu; Yunqing Li; Zhenmei Yang; Yuqing Tan; Ying Yuan (Journal of Environmental Management, 2023)

FeOOH@WS2 as a high-efficiency catalyst for enhanced persulfate activation to remove sulfachloropyridazine - Yajuan Li; Qiongfang Wang; Xin Zhang; Lei Dong; Cheng Peng; Min Zhang; Yulin Yuan; Pinhua Rao; Naiyun Gao; Chaoqun Tan (Journal of Environmental Chemical Engineering, 2023)

Geniposide alleviated hydrogen peroxide-induced apoptosis of human hepatocytes via altering DNA methylation - Xinyue Peng; Luyi Tan; Jia Song; Yuefei Lai; Susu Yu; Feifei Xu; Qinzhi Wei; Zhini He; Wenli Cheng; Wenjuan Zhang; Xingfen Yang (Food and Chemical Toxicology, 2023)

Formation and evolution of a loess sinkhole in the southern Chinese Loess Plateau - Junli Ren; Wei Gong; Cheng Xue; Peng Cheng; Ting Li; Li Ai; Huan Jiang; Xingxing Liu; Yukun Fan; Jianghu Lan; Liangcheng Tan; Youbin Sun (CATENA, 2023)

α-Hederin induces human colorectal cancer cells apoptosis through disturbing protein homeostasis - Qijuan Wang; Hui Feng; Ziwen Li; Qibiao Wu; Liu Li; Dongdong Sun; Jiani Tan; Minmin Fan; Chengtao Yu; Changliang Xu; Yueyang Lai; Weixing Shen; et al. (Chemico-Biological Interactions, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Insights of microalgal municipal wastewater treatment at low temperatures: Performance, microbiota patterns, and cold-adaptation of tubular and aeration column photobioreactors - Jiansong Tian; Pan Li; Yajun Luo; Heng Yan; Jian Liu; Zhicheng Pan; Yangwu Chen; Rui Wang; Yiwei Cheng; Houzhen Zhou; Junjie Li; Xin Li; et al. (Chemosphere, 2023)

Remote sensing for chromophoric dissolved organic matter (CDOM) monitoring research 2003–2022: A bibliometric analysis based on the web of science core database - Zhihui Li; Fei Zhang; Jingchao Shi; Ngai Weng Chan; Mou Leong Tan; Hsiang-te Kung; Changjiang Liu; Chunyan Cheng; Yunfei Cai; Weiwei Wang; Xingyou Li (Marine Pollution Bulletin, 2023)

Litter traps: A comparison of four marine habitats as sinks for anthropogenic marine macro-litter in Singapore - Jenny Fong; Samuel Hsien Rong Lee; Yuchen Sun; Cheng Ling Lim; Yean Ai Jolin Tan; Yi Hong Tan; Mei Lin Neo (Marine Pollution Bulletin, 2023)

Enantioselective effect of the chiral fungicide tebuconazole on the microbiota community and antibiotic resistance genes in the soil and earthworm gut - Chao-Feng Li; Yi-Rong Zhang; Zhen-Chao Tan; Hui-Juan Xu; Cheng-Lan Liu (Science of The Total Environment, 2023)

A review on ignition in expanding gaseous media - Yaqin Tan; Rémy Mével; Yu Cheng Liu (Process Safety and Environmental Protection, 2023)

Macroscale composite principal-monotonicity distributed projection of climate-induced hydrologic changes: Tempo-spatial variabilities, and variation decompositions - Guanhui Cheng; Guohe (Gordon) Huang; Qian Tan; Cong Dong; Xiong Zhou (Journal of Hydrology, 2023)

Nitrogen removal performance and C, N, S transformation under dry-wet alterations of heterotrophic-autotrophic sequential bioretention system amended with waste reed and sulfur - Zhaoying Liu; Liyuan Wu; Yang Hao; Yu Cheng; Chaohong Tan; Jia Wang; Haiyan Li (Journal of Cleaner Production, 2023)

Assessing the impact of urban form and urbanization process on tropospheric nitrogen dioxide pollution in the Yangtze River Delta, China - Yuanyun Gao; Shuntian Wang; Chengxin Zhang; Chengzhi Xing; Wei Tan; Hongyu Wu; Xinhan Niu; Cheng Liu (Environmental Pollution, 2023)

SO42− immobilization regulated by reaction atmosphere over ABS poisoned α-Fe2O3 catalysts for efficient NOx removal - Zhiwen Gu; Chong Tan; Baiyun Zhu; Songil Sin; Jiawei Ji; Yan Wang; Lijun Cheng; Wang Song; Chunkai Huang; Meilin Tao; Changjin Tang (Chemical Engineering Journal, 2023)

Immune-microenvironment modulatory polyurethane-hyaluronic acid hybrid hydrogel scaffolds for diabetic wound treatment - Yuan Feng; Kecen Xiao; Jinlin Chen; Jingjing Lin; Yuanyuan He; Xueling He; Fuyi Cheng; Zhen Li; Jiehua Li; Feng Luo; Hong Tan; Qiang Fu (Carbohydrate Polymers, 2023)

The Association Between Serum Magnesium Levels and Gestational Diabetes Mellitus: a Systematic Review and Meta-Analysis - Qian Ren; Hongya Wang; Yan Zeng; Xiaozhen Tan; Xi Cheng; Tingting Zhou; Wei Huang; Yong Xu (Biological Trace Element Research, 2023)

Lithospheric velocity structure of South China Sea basin from ocean bottom seismometer ambient noise tomography - Liqun Cheng; Yinxia Fang; Xiongwei Niu; Tingzi Li; Chongzhi Dong; Yanghui Zhao; Hao Hu; Fansheng Kong; Pingchuan Tan; Aiguo Ruan; Shaoping Lu; Jianke Fan; et al. (Tectonophysics, 2023)

Sugar-based natural deep eutectic solvent (NADES): Physicochemical properties, antimicrobial activity, toxicity, biodegradability and potential use as green extraction media for phytonutrients - Qi Qi Koh; Yin Leng Kua; Suyin Gan; Khang Wei Tan; Terri Zhuan Ean Lee; Wai Kit Cheng; Harrison Lik Nang Lau (Sustainable Chemistry and Pharmacy, 2023)

Thermophilic microorganisms involved in the nitrogen cycle in thermal environments: Advances and prospects - Xiao-Wei Wang; Xin Tan; Cheng-Cheng Dang; Yang Lu; Guo-Jun Xie; Bing-Feng Liu (Science of The Total Environment, 2023)

PpeERF115 regulates peach fruit ripening by increasing polyamine turnover through up-regulation of genes involved in polyamine synthesis and catabolism - Xin Cheng; Zhenguo Cui; Yabo Jiang; Yang Chen; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Jidong Li; et al. (Postharvest Biology and Technology, 2023)

A study of waterside microenvironmental factors and their effects on summer outdoor thermal comfort in a Cfa-climate campus - Jie Xiong; Bin Cheng; Jian Zhang; Yisha Liu; Xinyu Tan; Manjiang Shi; Xumei He; Jierui Guo (Journal of Thermal Biology, 2023)

Dramatically enhanced phenol degradation upon FeS oxygenation by low-molecular-weight organic acids - Dong Cheng; Haoran Ding; Yuansen Tan; Dezhi Yang; Ying Pan; Wenjuan Liao; Feng He (Journal of Hazardous Materials, 2023)

Effective removal of cesium by ammonium molybdophosphate–polyethylene glycol magnetic nanoparticles - Chengyun Fu; Zhaomin Tan; Jianfeng Cheng; Jingli Xie; Xuezhi Dai; Yinyuan Du; Shan Zhu; Shaoqing Wang; Minhao Yan (Journal of Environmental Chemical Engineering, 2023)

Eco-friendly and intelligent cellulosic fibers-based packaging system for real-time visual detection of food freshness - Yali Zhao; Chao Li; Xiaodong Xia; Mingqian Tan; Haisong Wang; Yanna Lv; Yi Cheng; Yehan Tao; Jie Lu; Dongmei Li; Jian Du (Chemical Engineering Journal, 2023)

Elucidating role of alloying in electrocatalytic hydrogenation of benzaldehyde over nanoporous NiPd catalysts - Guanhua Cheng; Zhihua Zhai; Jiameng Sun; Yunfei Ran; Wanfeng Yang; Fuquan Tan; Zhonghua Zhang (Chemical Engineering Journal, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

NRF2 Antagonizes HIV-1 Tat and Methamphetamine-Induced BV2 Cell Ferroptosis by Regulating SLC7A11 - Shucheng Lin; Hao Cheng; Genmeng Yang; Chan Wang; Chi-Kwan Leung; Shuwei Zhang; Yi Tan; Huijie Zhang; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Neurotoxicity Research, 2023)

Effect of ice slurry ingestion on thermoregulatory responses during fixed-intensity cycling in humid and dry heat - Hui Cheng Choo; Darine Hui Wen Choo; Isabelle Tan; Jared Chang; Kin Ming Chow; Jason Kai Wei Lee; Stephen Francis Burns; Mohammed Ihsan (European Journal of Applied Physiology, 2023)

Detoxification of typical nitrogenous heterocyclic compound from pharmaceutical wastewater by mixed microbial consortia - Hongyu Jin; Zimeng Nie; Hongyu Niu; Ju Tan; Shuie Huang; Binghua Yan; Bozhi Cheng; Haijun Yang (Chemosphere, 2023)

Research progress of shell boring mud-blister worm infestation in shellfish aquaculture - Karsoon Tan; Dewei Cheng; Kit Yue Kwan; Ya Peng; Xiahui Cai; Leongseng Lim; Peng Xu; Kianann Tan (Aquaculture, 2023)

Real-time tunneling risk forecasting using vibrations from the working TBM - Enhedelihai Alex Nilot; Gang Fang; Yunyue Elita Li; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2023)

Assessing the impact of fractional vegetation cover on urban thermal environment: A case study of Hangzhou, China - Maomao Zhang; Shukui Tan; Cheng Zhang; Siyu Han; Shangjun Zou; Enqing Chen (Sustainable Cities and Society, 2023)

Effect of deep eutectic solvent extraction on Auricularia auricula polysaccharide solubilization and antioxidant potential - Jing Yao; Jiangying Zeng; Huinan Tang; Yirui Cheng; Jingjing Tan; Tianyuan Li; Xiangyu Li; Jiyuan He; Yongjun Zhang (Sustainable Chemistry and Pharmacy, 2023)

Acrylonitrile butadiene styrene microplastics aggravate the threat of decabromodiphenyl ethane to Eisenia fetida: Bioaccumulation, tissue damage, and transcriptional responses - Mengru Fu; Jiaqi Tan; Shanqi Zhou; Peng Liu; Zhihua Qiao; Yanna Han; Wei Zhang; Cheng Peng (Science of The Total Environment, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Effect of homogenization on lipid profiling in Saanen goat milk based on UHPLC-QTOF-MS lipidomics - Yixuan Tan; Jiafei Liu; Yang Yang; Xufeng Wang; Xiaomeng Sun; Jianjun Cheng (Food Chemistry, 2023)

Association between flavor composition and sensory profile in thermally processed mandarin juices by multidimensional gas chromatography and multivariate statistical analysis - Yujiao Cheng; Leng Han; Linhua Huang; Xiang Tan; Houjiu Wu; Guijie Li (Food Chemistry, 2023)

Endowing V6O13/CeVO4 heterojunction with substantial improvements on zinc ion storage performance - Jingyun Cheng; Shuai Nan; Shuang Yu; Kaitao Liu; Huaiqiang Gu; Lei Tan; Zhulin Niu; Dan Li; Hongqiang Wang (Chemical Engineering Journal, 2023)

Microwave absorption-based magnetic liquid metal nano-missiles for thermodynamic/immunological cascade hepatoma therapy - Zonghao Liu; Xin Tan; Yueru Huang; Weikun Li; Ning Yang; Renqiang Yuan; Qiang Cheng; Ling Liu; Liqin Ge (Chemical Engineering Journal, 2023)

Ultrafast self-assembled supramolecular nanoparticles for enhanced chemodynamic therapy and ferroptosis through lactic acid metabolism regulation - Qi Meng; Jia Tan; Weifang Tong; Changxiao Chen; Zhendong Liu; Sainan Liu; Meifang Wang; Ziyong Cheng; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2023)

Impact of land use change on the urban-rural temperature disparity in Eastern China - Yanyu Wang; Jun Wang; Huanxin Zhang; Nathan Janechek; Yi Wang; Meng Zhou; Pengke Shen; Jianguo Tan; Qianshan He; Tiantao Cheng; Cheng Huang (Atmospheric Environment, 2023)

Elucidating the role of T-cell exhaustion-related genes in colorectal cancer: a single-cell bioinformatics perspective - Wei Tu; Yan Tu; Chunhong Tan; Honghong Zhong; Sheng Xu; Jun Wang; Lv Huang; Ling Cheng; Haoguang Li (Functional & Integrative Genomics, 2023)

Calcium sulfite oxidation activated by ferrous iron integrated with membrane filtration for removal of typical algal contaminants - Wenxin Song; Zhimin Gao; Fengxun Tan; Xiaoxiang Cheng; Tao Yang; Daoji Wu; Jingxin Yang; Heng Liang (Chemosphere, 2023)

Classification and recycling of recyclable garbage based on deep learning - Yujin Chen; Anneng Luo; Mengmeng Cheng; Yaoguang Wu; Jihong Zhu; Yanmei Meng; Weilong Tan (Journal of Cleaner Production, 2023)

Mechanochemically-induced C–S bond transalkylation exchange in the waste nitrile rubber (NBR)/Poly (vinyl chloride) (PVC) insulation materials - Shuangxin Lai; Chaofeng Cheng; Xingrui Su; Yi Liao; Qianyue Tan; Shibing Bai (Journal of Cleaner Production, 2023)

Atmospheric gaseous aromatic hydrocarbons in eastern China based on mobile measurements: Spatial distribution, secondary formation potential and source apportionment - Lingling Yuan; Hongli Wang; Yaqin Gao; Guofa Ren; Yiqun Lu; Shengao Jing; Wen Tan; Liang Zhu; Yu Shang; Jing An; Cheng Huang (Journal of Environmental Sciences, 2023)

Low thermal pre-treatment of palm kernel expeller to enhance microalgal hydrogen production - Khairun Nadia Muhamad; Nurul Tasnim Sahrin; Raid Abdulrahman Alakeel; Rabbani Syed; Fatima Musa Ardo; Jia Min Woon; Wen Nee Tan; Chin Kui Cheng; Zakariyya Uba Zango; Chii-Dong Ho; Sze Mun Lam; Jin Chung Sin; et al. (Fuel, 2023)

Pickering emulsion stabilized by Haematococcus pluvialis protein particles and its application in dumpling stuffing - Chenyue Liu; Shasha Cheng; Haitao Wang; Mingqian Tan (Food Research International, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Salinilacihabitans rarus gen. nov., sp. nov., Natrononativus amylolyticus gen. nov., sp. nov., Natronobeatus ordinarius gen. nov., sp. nov., and Halovivax gelatinilyticus sp. nov., halophilic archaea, isolated from a salt lake and soda lakes - Xin-Xin Li; Shun Tan; Mu Cheng; Yao Hu; Xue Ma; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Chain hybridization‐based CRISPR‐lateral flow assay enables accurate gene visual detection - Meng Cheng; Caiwei Tan; Bo Xiang; Weihong Lin; Bolin Cheng; Xuechun Peng; Yihao Yang; Yongping Lin (Analytica Chimica Acta, 2023)

Carbon price prediction based on multiple decomposition and XGBoost algorithm - Ke Xu; Zhanguo Xia; Miao Cheng; Xiawei Tan (Environmental Science and Pollution Research, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Lipidomics of Sannen goat milk subjected to pasteurization and spray drying based on LC-ESI-MS/MS - Yixuan Tan; Junli Hao; Yuhang Jiang; Xiaomeng Sun; Jianjun Cheng (Food Research International, 2023)

Protein gel with designed network and texture regulated via building blocks to study dysphagia diet classifications - Guangxue Chen; Jinhua Hu; Yongxue Liang; Xueyao Huang; Geok Leng Seah; Jin Li; Dingrong Liu; Cheng Tan (Food Hydrocolloids, 2023)

Identification and characterization of the gene BraANS.A03 associated with purple leaf color in pak choi (Brassica rapa L. ssp. chinensis) - Chen Tan; Haidong Chen; Guoqiang Dai; Yi Liu; Wenjie Shen; Chenchen Wang; Duannv Liu; Sijia Liu; Shuqi Xu; Bo Zhu; Daozong Chen; Cheng Cui (Planta, 2023)

Hyperspectral imaging technique supports dynamic emission inventory of coal-fired power plants in China - Jinan Lin; Chengzhi Xing; Cheng Liu; Wei Tan; Wei Wang; Peng Wu; Chuan Lu; Qihua Li; Ting Liu (Science Bulletin, 2023)

Ambient air pollution and the health-related quality of life of older adults: Evidence from Shandong China - Jialong Tan; Nuo Chen; Jing Bai; Peizhe Yan; Xinyu Ma; Meiling Ren; Elizabeth Maitland; Stephen Nicholas; Wenjing Cheng; Xue Leng; Chen Chen; Jian Wang (Journal of Environmental Management, 2023)

Selective catalytic reduction of NO with NH3 over MnOx-CeO2 catalysts: The great synergy between CeO2 and crystalline phase of Mn3O4 - Lijun Cheng; Songil Sin; Jiawei Ji; Shan Yang; Chong Tan; Zhiwen Gu; Wang Song; Chunkai Huang; Chuanzhi Sun; Changjin Tang; Lin Dong (Fuel, 2023)

Effects of sucrose degradation product furfural on cyanidin-3-O-glucoside: Mechanism of action, stability, and identification of products in sugar solutions - Jiaxin Wang; Zhen Cheng; Ningxuan Gao; Ye Zhang; Mingshuang Wang; Guangyu Ren; Baoge Song; Qi Liang; Yiwen Bao; Hui Tan; Wei Chen; Bin Li; et al. (Food Research International, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Design of hybrid g-C3N4/GO/MCE photocatalytic membranes with enhanced separation performance under visible-light irradiation - Junyang Pan; Dan Hua; Yiping Hong; Xi Cheng; Fangsong Guo; Kok Bing Tan; Ziqi Zhong; Guowu Zhan (Chemical Engineering Journal, 2023)

Experimental investigation of the cooling capacity and thermal performance of the passive displacement dual cooling coil system in tropical climate - Steve Kardinal Jusuf; Aung Myat; Hui An; Yong Loke Soh; Jeggathishwaran Panisilvam; Peng Cheng Wang; Jing Hui Soo; Nicholas Tan; Poh Hong Neo; George Ng (Building and Environment, 2023)

Arbuscular Mycorrhizal Fungi and Rhizobium Facilitate Nitrogen and Phosphate Availability in Soybean/Maize Intercropping Systems - Yinghang Qin; Yixiu Yan; Lu Cheng; Yufan Lu; Jiabin Chen; Fang Liu; Jing Tan (Journal of Soil Science and Plant Nutrition, 2023)

Application of particle image velocimetry on velocity distribution in 5 × 5 rod bundle channel under rolling motion - Xin Li; Chao Qi; Kun Cheng; Sichao Tan; Shouxu Qiao; Dongyang Li (Annals of Nuclear Energy, 2023)

Review of through-wall leaking incidents during excavation of the subway stations of Nantong metro line 1 in thick water-rich sandy strata - Jun-Cheng Liu; Yong Tan (Tunnelling and Underground Space Technology, 2023)

Airflow Mitigation and Pollutant Purification in an Idealized Urban Street Canyon with Wind Driven Natural Ventilation: Cooperating and Opposing Effects of Roadside Tree Plantings and Non-uniform Building Heights - Yu-Fei Tang; Ya-Bing Wen; Hao Chen; Zhi-Cheng Tan; Yi-He Yao; Fu-Yun Zhao (Sustainable Cities and Society, 2023)

PpIBH1-1 limits internode elongation of peach shoot in a dose-dependent manner - Mengmeng Zhang; Beibei Feng; Yun Chen; Mingxi Geng; Ming Li; Xianbo Zheng; Haipeng Zhang; Langlang Zhang; Bin Tan; Xia Ye; Wei Wang; Jidong Li; et al. (Plant Science, 2023)

A practical method for identifying key factors in the distribution and formation of heavy metal pollution at a smelting site - Jiaqing Zeng; Wenshun Ke; Min Deng; Jingqiang Tan; Chuxuan Li; Yizhi Cheng; Shengguo Xue (Journal of Environmental Sciences, 2023)

Long-term variation and evaluation of air quality across Hong Kong - Yan Tan; Shuwen Han; Yi Chen; Zhongbiao Wu; Shun-cheng Lee (Journal of Environmental Sciences, 2023)

Poly(vinyl alcohol)-based highly permeable TFC nanofiltration membranes for selective dye/salt separation - Zhongyue Sun; Xuewu Zhu; Fengxun Tan; Weiwei Zhou; Yongrui Zhang; Xinsheng Luo; Jingtao Xu; Daoji Wu; Heng Liang; Xiaoxiang Cheng (Desalination, 2023)

Inversion of TEM measurement data via a quantum particle swarm optimization algorithm with the elite opposition-based learning strategy - Junjun Jiao; Jiulong Cheng; Yuben Liu; Haiyan Yang; Dingrui Tan; Peng Cheng; Yuqi Zhang; Chenglin Jiang; Zhi Chen (Computers & Geosciences, 2023)

pH and non-enzymatic glucose response at ultra-low concentration using submicrochannel heterogeneous membrane - Yuan-Ju Tang; Kai Cheng; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Wen-Ming Su; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Cyanidin-3- O -glucoside and its phenolic metabolites ameliorate intestinal diseases via modulating intestinal mucosal immune system: potential mechanisms and therapeutic strategies - Zhen Cheng; Xu Si; Hui Tan; Zhihuan Zang; Jinlong Tian; Chi Shu; Xiyun Sun; Zhiying Li; Qiao Jiang; Xianjun Meng; Yi Chen; Bin Li; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Molecular identification of a flavone synthase I/flavanone 3β-hydroxylase bifunctional enzyme from fern species Psilotum nudum - Jie Fu; Piao-Yi Wang; Rong Ni; Jiao-Zhen Zhang; Ting-Ting Zhu; Hui Tan; Jing Zhang; Hong-Xiang Lou; Ai-Xia Cheng (Plant Science, 2023)

Sluggish lithium isotopic response of continental intraplate basalts to recycled sedimentary carbonate - Yang-Yang Wang; Cheng-Long Yu; Dong-Bo Tan; He Sun; Hai-Ou Gu; Fengtai Tong; Li-Hui Chen; Yilin Xiao (Lithos, 2023)

Emphasizing egalitarianism in the allocation of China's provincial carbon emission allowances - Yonglong Cheng; Xianchun Tan; Baihe Gu; Chen Huang; Hongshuo Yan; Miaomiao Niu (Journal of Cleaner Production, 2023)

A new automatic quality control system for ocean profile observations and impact on ocean warming estimate - Zhetao Tan; Lijing Cheng; Viktor Gouretski; Bin Zhang; Yanjun Wang; Fuchao Li; Zenghong Liu; Jiang Zhu (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Chronic exposure to environmentally relevant concentrations of carbamazepine interferes with anxiety response of adult female zebrafish through GABA /5-HT pathway and HPI axis - Cheng-Ting Xie; Mei-Ling Tan; Ying-Wen Li; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Aggregation-induced color fine-tunable carbon dot phosphorescence covering from green to near-infrared for advanced information encryption - Qijun Li; Dengke Cheng; Hailing Gu; Daiqi Yang; Yuchen Li; Shuai Meng; Yunyang Zhao; Zikang Tang; YiBo Zhang; Jing Tan; Songnan Qu (Chemical Engineering Journal, 2023)

Integrated ferrate and calcium sulfite to treat algae-laden water for controlling ultrafiltration membrane fouling: High-efficiency oxidation and simultaneous cell integrity maintaining - Xiaoxiang Cheng; Jinchuan Lian; Bin Liu; Xuewu Zhu; Yan Jin; Lijie Zhang; Fengxun Tan; Daoji Wu; Heng Liang (Chemical Engineering Journal, 2023)

Natrinema caseinilyticum sp. nov., Natrinema gelatinilyticum sp. nov., Natrinema marinum sp. nov., Natrinema zhouii sp. nov., extremely halophilic archaea isolated from marine environments and a salt mine - Yao Hu; Xue Ma; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

The structure and properties of mechanochemically modified acrylonitrile butadiene rubber (NBR)/poly (vinyl chloride) (PVC) scraps and fresh NBR composites - Shuangxin Lai; Chaofeng Cheng; Yi Liao; Xingrui Su; Qianyue Tan; Shuangqiao Yang; Shibing Bai (Waste Management, 2023)

Volatile organic compounds at a roadside site in Hong Kong: Characteristics, chemical reactivity, and health risk assessment - Shuwen Han; Yan Tan; Yuan Gao; Xinwei Li; Steven Sai Hang Ho; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2023)

Utilization of current pyrolysis technology to convert biomass and manure waste into biochar for soil remediation: A review - Shimeng Tan; Guoying Zhou; Quan Yang; Shengbo Ge; Junang Liu; Yoke Wang Cheng; Peter Nai Yuh Yek; Wan Adibah Wan Mahari; Sieng Huat Kong; Jo-Shu Chang; Christian Sonne; William Woei Fong Chong; et al. (Science of The Total Environment, 2023)

Plutonium-based radiometric dating of rapidly accumulated sediments in the Sanyuan sinkhole, southern Chinese Loess Plateau - Yukun Fan; Huan Jiang; Junli Ren; Xingxing Liu; Jianghu Lan; Peng Cheng; Qi Liu; Liangcheng Tan; Cheng Xue; Youbin Sun; Xiaolin Hou (Science of The Total Environment, 2023)

Immobilize Nd2O3 as simulated nuclear waste in silicate-apatite glass-ceramics - Yanrong Cheng; Xiaoyan Shu; Mingfen Wen; Yuexiang Lu; Pan Tan; Xirui Lu; Lingshuang Li; Faqin Dong (Process Safety and Environmental Protection, 2023)

Diverse alkaloids from the aerial parts of Aconitum carmichaelii and antiproliferative activity of costemline via inhibiting SIRT1/ROCK1/P-STAT3 pathways - Yin-Lin Zhou; Duan-Na Zhang; Ji-Xu Qiao; Jing Wu; Yong-Ming Yan; Zhi-Xing Cao; Cheng Peng; Yu-Zhu Tan (Phytochemistry, 2023)

Immobilization of Zn(Ⅱ) and Cu(Ⅱ) in basic magnesium-sulfate-cementitious material system: Properties and mechanism - Yongshan Tan; Zhibin Zhang; Dingyi Yang; Jinmei Dong; Xiangyi Cheng; Hongfa Yu (Journal of Hazardous Materials, 2023)

Transmission paths and source areas of near-surface ozone pollution in the Yangtze River delta region, China from 2015 to 2021 - Youru Yao; Wei Wang; Kang Ma; Huarong Tan; Yong Zhang; Fengman Fang; Cheng He (Journal of Environmental Management, 2023)

Altitude and slope aspects as the key factors affecting the change of C:N:P stoichiometry in the leaf-litter-soil system of alpine timberline ecotones of the Sygera Mountains in Southeast Tibet, China - Peng He; Jie Lu; Yihua Ren; Jiangrong Li; Lei Hou; Xiangsheng Deng; Tan Gao; Fei Cheng (Geoderma Regional, 2023)

Insect biorefinery: A circular economy concept for biowaste conversion to value-added products - Phei Er Kee; Yu-Shen Cheng; Jo-Shu Chang; Hip Seng Yim; John Choon Yee Tan; Su Shiung Lam; John Chi-Wei Lan; Hui Suan Ng; Kuan Shiong Khoo (Environmental Research, 2023)

Effect of salinity stress on rice yield and grain quality: A meta-analysis - Cheng Zheng; Citao Liu; Ling Liu; Yanning Tan; Xiabing Sheng; Dong Yu; Zhizhong Sun; Xuewu Sun; Jin Chen; Dingyang Yuan; Meijuan Duan (European Journal of Agronomy, 2023)

Biosurfactant promoted enzymatic saccharification of alkali‑pretreated reed straw - Xinyuan Zhang; Yiqin Wang; Jie Lu; Miaomiao Liu; Wanting Tan; Yi Cheng; Yehan Tao; Jian Du; Haisong Wang (Bioresource Technology, 2023)

IiSVP of Isatis indigotica can reduce the size and repress the development of floral organs - Qi Meng; Xiao-Fang Hou; Hao Cheng; Xiao-Min Tan; Zuo-Qian Pu; Zi-Qin Xu (Plant Cell Reports, 2023)

A universal platform for one-pot detection of circulating non-coding RNA combining CRISPR-Cas12a and branched rolling circle amplification - Hui Chen; Zhiyuan Zhuang; Yan Chen; Cheng Qiu; Ying Qin; Chunyan Tan; Ying Tan; Yuyang Jiang (Analytica Chimica Acta, 2023)

MUSER and IPS telescopes for solar and space weather observations - Yihua Yan; Wei Wang; Linjie Chen; Fei Liu; Jin Fan; Zhijun Chen; Lihong Geng; Chengming Tan; Suli Ma; Sha Li; Cang Su; Jing Du; et al. (Advances in Space Research, 2023)

Mutual activation between ferrate and calcium sulfite for surface water pre-treatment and ultrafiltration membrane fouling control - Jinchuan Lian; Xiaoxiang Cheng; Xuewu Zhu; Xinsheng Luo; Jingtao Xu; Fengxun Tan; Daoji Wu; Heng Liang (Science of The Total Environment, 2023)

Superhydrophobic copper foam bed with extended permeation channels for water-in-oil emulsion separation with high efficiency and flux - Zehao Chen; Jihao Zuo; Ting Zhao; Qing Tan; Yunjun Nong; Shouping Xu; Jiang Cheng; Xiufang Wen; Pihui Pi (Journal of Environmental Chemical Engineering, 2023)

Influences of protein-corona on stability and aggregation kinetics of Ti3C2Tx nanosheets in aquatic environment - Shizhu Cheng; Feng Tan; Xuri Wu; Fan Dong; Jinghua Liu; Yan Wang; Hongxia Zhao (Environmental Research, 2023)

Criticality of solid electrolyte interphase in achieving high performance of sodium-ion batteries - Qian Cheng; Qiang Deng; Wentao Zhong; Ting Tan; Xiaozhao Liu; Changdong Chen; Junhua Hu; Zhang Lin; Kevin Huang; Chenghao Yang (Chemical Engineering Journal, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

The parallel electron transfer pathways of biofilm and self-secreted electron shuttles in gram-positive strain Rhodococcus pyridinivorans HR-1 inoculated microbial fuel cell - Peng Cheng; Yingchuan Zhang; Nianfang Ma; Lining Wang; Liqun Jiang; Zhen Fang; Yitong Wang; Xiangping Tan (Bioresource Technology, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

One-pot synthesis of injectable self-healing thermoresponsive halloysite nanotube-reinforced nanocomposite hydrogels for tissue engineering - Li Wen Wong; Pooria Pasbakhsh; Wai Teng Cheng; Calvin Bok Sun Goh; Joash Ban Lee Tan (Applied Clay Science, 2023)

When Does a Light Sphere Break Ice Plate Most by Using Its Net Buoyance? - Bao-Yu Ni; Hao Tan; Shao-Cheng Di; Chen-Xi Zhang; Zhiyuan Li; Luofeng Huang; Yan-Zhuo Xue (Journal of Marine Science and Engineering, 2023)
A free-rising buoyant sphere can break an ice plate floating above it. The problem is when the light sphere breaks the ice plate most, or the optimal relative density of the sphere which can break the ice plate the most severely. This experimental study was done to answer this problem. A set of experimental devices were designed, and a high-speed camera system was adopted to record the whole dynamic process, including the free-rising of the sphere, the collision between the sphere and the ice plate, the crack initiation and propagation, as well as the breakup of the ice plate. The failure mode of the ice plate under impact load was analyzed. It was found that conical cracks were formed under the reflected tensile wave at the top surface of the ice plate. On this basis, the influences of ice thickness, the initial submergence depth, and the relative density of the sphere on icebreaking were further investigated. An optimal relative density of the sphere was found when the sphere was released at a certain initial submergence depth, at which point the ice was damaged the most severely. For example, when the dimensionless initial submergence depth of the sphere was 2.31, the optimal relative density of the sphere was close to 0.4, with the probability of the ice plate breakup as high as 91.7%. It was also found from the experiments that the degree of damage to the ice plate correlated well with the kinetic energy of the sphere just before collision. Results showed that the optimal relative density can be estimated by theoretical analysis of the kinetic energy of the sphere, which will provide a reference for potential icebreaking applications in the future.

Sharply and simultaneously increasing pollutant accumulations in cells of organisms induced by rare earth elements in the environment of Nanjing - Qing Yang; Mengzhu Cheng; Qing Zhou; Lihong Wang; Yunlong Jiao; Yongqiang Liu; Shuya Zhang; Li Tan; Zhenhong Gu; Hong Zhu; Hongli Luo; Daozhe Lin; et al. (Chemosphere, 2023)

Impact of urban expansion on land surface temperature and carbon emissions using machine learning algorithms in Wuhan, China - Maomao Zhang; Abdulla - Al Kafy; Pengnan Xiao; Siyu Han; Shangjun Zou; Milan Saha; Cheng Zhang; Shukui Tan (Urban Climate, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

High-throughput sequencing reveals tuber mustard genes responsive to Plasmodiophora brassicae in the early stage of infection - Zhaoming Cai; Meiqin Xiang; Jing Tan; Chunhong Cheng; Ying Liu; Jiayu Shi; Meiling Shi; Jin Li; Diandong Wang (Physiological and Molecular Plant Pathology, 2023)

Microbiologically induced calcite precipitation for in situ stabilization of heavy metals contributes to land application of sewage sludge - Yong Zeng; Zezhi Chen; Qingyang Lyu; Yapeng Cheng; Chenchen Huan; Xinru Jiang; Zhiying Yan; Zhouliang Tan (Journal of Hazardous Materials, 2023)

An agro-hydrological process-based export coefficient model for estimating monthly non-point source loads in a semiarid agricultural area - Shan Zhang; Guanhui Cheng; Qian Tan; Hang Zhao; Tong Zhang (Journal of Cleaner Production, 2023)

Prospect of China's ambient air quality standards - Zongshuang Wang; Yufei Tan; Min Guo; Miaomiao Cheng; Yanyue Gu; Siyu Chen; Xuefang Wu; Fahe Chai (Journal of Environmental Sciences, 2023)

In vitro simulated digestion of and microbial characteristics in colonic fermentation of polysaccharides from four varieties of Tibetan tea - Yaowen Tan; Meiwen Li; Keyang Kong; Yushan Xie; Zhen Zeng; Zhengfeng Fang; Cheng Li; Bin Hu; Xinjie Hu; Caixia Wang; Saiyan Chen; Wenjuan Wu; et al. (Food Research International, 2023)

Residential greenness and risk of incident dementia: A prospective study of 375,342 participants - He-Ying Hu; Ya-Hui Ma; Yue-Ting Deng; Ya-Nan Ou; Wei Cheng; Jian-Feng Feng; Lan Tan; Jin-Tai Yu (Environmental Research, 2023)

PM2.5-related DNA methylation and the association with lung function in non-smokers - Ge Mu; Xiuquan Nie; Shijie Yang; Zi Ye; Man Cheng; Lieyang Fan; Weihong Qiu; Qiyou Tan; Min Zhou; Yanjun Guo; Weihong Chen (Environmental Pollution, 2023)

Ultra-robust, stretchable electrodes based on superamphiphobic surface for personal exercise monitoring - Shijia Tian; Xiaonan Wang; Wenjing Qin; Shougen Yin; Taixing Tan; Yuan Tian; Cheng Wang (Chemical Engineering Journal, 2023)

Crystalline boron significantly accelerates Fe(III)/PMS reaction as an electron donor: Iron recycling, reactive species generation, and acute toxicity evaluation - Chaoqun Tan; Xuejian Cheng; Tianhui Xu; Kaiyang Chen; Huiming Xiang; Lianghu Su (Chemical Engineering Journal, 2023)

Shape-controlled synthesis of Pd nanotetrahedrons with Pt-doped surfaces for highly efficient electrocatalytic oxygen reduction and formic acid oxidation - Liuxuan Luo; Zehao Tan; Cehuang Fu; Rui Xue; Xiaojing Cheng; Tianzi Bi; Lutian Zhao; Yangge Guo; Xiyang Cai; Jiewei Yin; Shuiyun Shen; Junliang Zhang (Chemical Engineering Journal, 2023)

Molten salt-induction of geometrically deformed ruthenium single atom catalysts with high performance for aerobic oxidation of alcohols - Xiuli Dong; Yufei Jia; Mingyang Zhang; Siqi Ji; Leipeng Leng; J. Hugh Horton; Chang Xu; Cheng He; Qiang Tan; Jiangwei Zhang; Zhijun Li (Chemical Engineering Journal, 2023)

Gomphrena globosa L. extract alleviates carbon tetrachoride-induced liver injury in mice by activating antioxidant signaling pathways and promoting autophagy - Yunfei Wei; Wenxi Tan; Haiyan Qin; Meiyu Jin; Hao Yu; Jiaqi Cheng; Haihua Feng (Molecular Biology Reports, 2023)

Characteristics of leachate from refuse transfer stations in rural China - Huiming Xiang; Le Cheng; Weiye Liu; Saier Wang; Yi Zhang; Lianghu Su; Chaoqun Tan; Yuping Li (Environmental Science and Pollution Research, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Genome-wide investigation on metal tolerance protein (MTP) genes in leguminous plants: Glycine max, Medicago truncatula, and Lotus japonicus - Yunjian Xu; Lu Cheng; Jiabin Chen; Yufan Lu; Yinghang Qin; Yixiu Yan; Fang Liu; Jing Tan (Acta Physiologiae Plantarum, 2023)

Effects of Selenium on the AsA-GSH System and Photosynthesis of Pakchoi (Brassica chinensis L.) Under Lead Stress - Zhanming Tan; Zhengying Xuan; Cuiyun Wu; Yunxia Cheng; Chongzhi Xu; Xinchao Ma; Desheng Wang (Journal of Soil Science and Plant Nutrition, 2022)

Effects of four endophytic bacteria on cadmium speciation and remediation efficiency of Sedum plumbizincicola in farmland soil - Xueyu Cheng; Xueying Cao; Changyin Tan; Lulu Liu; Jia Bai; Yufeng Liang; Runzhong Cai (Environmental Science and Pollution Research, 2022)

Genetic characterization of elite tropical, subtropical and temperate maize germplasm based on genome-wide SNP markers - Kun Wang; Lu Cheng; Jiabin Chen; Dandan Yang; Yixuan Zhang; Ji Luo; Jing Tan (Cereal Research Communications, 2022)

Chemical constituents from the aerial part of Polygala tenuifolia - Yan-Gang Cheng; Jin-Yan Tan; Jian-Li Li; Shi-Hui Wang; Kai-Li Liu; Jia-Min Wang; Ying-Li Wang (Natural Product Research, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

A visual knowledge map analysis of mine fire research based on CiteSpace - Feiran Wang; Bo Tan; Yue Chen; Xiyang Fang; Guowei Jia; Haiyan Wang; Gang Cheng; Zhuangzhuang Shao (Environmental Science and Pollution Research, 2022)

A systematic review and meta-analysis of non-vitamin K antagonist oral anticoagulants vs vitamin K antagonists after transcatheter aortic valve replacement in patients with atrial fibrillation - Amanda Jia Qi Ooi; Chloe Wong; Timothy Wei Ern Tan; Trina Priscilla Ng; Yao Neng Teo; Yao Hao Teo; Nicholas L. Syn; Andie H. Djohan; Yinghao Lim; Leonard L. L. Yeo; Benjamin Y. Q. Tan; Mark Yan-Yee Chan; et al. (European Journal of Clinical Pharmacology, 2022)

How Well Do CMIP6 and CMIP5 Models Simulate the Climatological Seasonal Variations in Ocean Salinity? - Yuanxin Liu; Lijing Cheng; Yuying Pan; Zhetao Tan; John Abraham; Bin Zhang; Jiang Zhu; Junqiang Song (Advances in Atmospheric Sciences, 2022)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Causal Effect of Genetically Determined Blood Copper Concentrations on Multiple Diseases: A Mendelian Randomization and Phenome-Wide Association Study - Xiuming Feng; Wenjun Yang; Lulu Huang; Hong Cheng; Xiaoting Ge; Gaohui Zan; Yanli Tan; Lili Xiao; Chaoqun Liu; Xing Chen; Zengnan Mo; Longman Li; et al. (Phenomics, 2022)

A Review on Hydraulic Fracture Height Growth for Layered Formation - Peng Tan; Jiawei Kao; Fushan Cheng; Yiliu Sun; Shihao Fu; Lejia Ren (Geotechnical and Geological Engineering, 2022)

Hb New York, preliminary results concerning the hematologic characteristics and the effects on thalassemia - Zhuru Cheng; Xiaonian Zhu; Dan Zeng; Qiao Feng; Baodong Tian; Haiqing Zheng; Shengkui Tan; Chunjiang Zhu (Molecular Biology Reports, 2022)

Whole-transcriptome sequencing identifies key mRNAs, miRNAs, lncRNAs, and circRNAs associated with unexplained recurrent pregnancy loss - Yan Wang; Qing Cheng; Zhengyi Xia; Ran Zhou; Yiming Li; Lulu Meng; Qing Xu; Jianxin Tan; Zhengfeng Xu (Cell and Tissue Research, 2022)

A Non-destructive Quantitative Transmission Raman Spectroscopy Method for Active Pharmaceutical Ingredient in Drug Product In-Use Samples Prepared in Dosing Vehicles - Gregory Doddridge; Edwin Hong; David Cheng Thiam Tan; Yemin Liu (AAPS PharmSciTech, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Localization of salt-tolerant QTL in rice germination stage under different salinity concentrations - Yanning Wang; Liping Chen; Guiting Song; Tao Huang; Guangliang Wu; Jingai Tan; Peng Wang; Qin Cheng; Caijing Li; Qi Zhong; Shiying Huang; Mengmeng Yang; et al. (Euphytica, 2022)

Comparison of different inversion methods of D-T2 two-dimensional nuclear magnetic resonance logging and applicability analysis - Cheng-Lin Li; Mao-Jin Tan; Ke-Wen Wang; Feng Zhou; Ying-Ming Liu; Hai-Tao Zhang; Li-Zhi Xiao (Applied Geophysics, 2022)

Multiple indeterminate domain (IDD)–DELLA1 complexes participate in gibberellin feedback regulation in peach - Yajun Jiang; Jiajia Chen; Xianbo Zheng; Bin Tan; Xia Ye; Wei Wang; Langlang Zhang; Jidong Li; Zhiqian Li; Jun Cheng; Jiancan Feng (Plant Molecular Biology, 2022)

D609 inhibition of phosphatidylcholine-specific phospholipase C attenuates prolonged insulin stimulation-mediated GLUT4 downregulation in 3T3-L1 adipocytes - Jinhui Ma; Xu Zhang; Yankun Song; Yan Qin; Yinghui Tan; Lishuang Zheng; Baoqian Cheng; Xin Xi (Journal of Physiology and Biochemistry, 2022)
Glucose uptake is stimulated by insulin via stimulation of glucose transporter 4 (GLUT4) translocation to the plasma membrane from intracellular compartments in adipose tissue and muscles. Insulin stimulation for prolonged periods depletes GLUT4 protein, particularly in highly insulin-responsive GLUT4 storage vesicles. This depletion mainly occurs via H 2 O 2 -mediated retromer inhibition. However, the post-receptor mechanism of insulin activation of oxidative stress remains unknown. Here, we show that phosphatidylcholine-specific phospholipase C (PC-PLC) plays an important role in insulin-mediated downregulation of GLUT4. In the study, 3T3-L1 adipocytes were exposed to a PC-PLC inhibitor, tricyclodecan-9-yl-xanthogenate (D609), for 30 min prior to the stimulation with 500 nM insulin for 4 h, weakening the depletion of GLUT4. D609 also prevents insulin-driven H 2 O 2 generation in 3T3-L1 adipocytes. Exogenous PC-PLC and its product, phosphocholine (PCho), also caused GLUT4 depletion and promoted H 2 O 2 generation in 3T3-L1 adipocytes. Furthermore, insulin-mediated the increase in the cellular membrane PC-PLC activity was observed in Amplex Red assays. These results suggested that PC-PLC plays an important role in insulin-mediated downregulation of GLUT4 and that PCho may serve as a signaling molecule.

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

The influence of omega-3 supplementation on vitamin D levels in humans: a systematic review and dose-response meta-analysis of randomized controlled trials - Habeeb Alhabeeb; Hamed Kord-Varkaneh; Shing Cheng Tan; Mihnea-Alexandru Găman; Bander Yayha Otayf; Almuhannad Ali Qadri; Osama Alomar; Hany Salem; Ismail A. Al-Badawi; Ahmed Abu-Zaid (Critical Reviews in Food Science and Nutrition, 2022)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

Morphologic changes of simple star dunes during the growth process in Dunhuang, China - Zhi-shan An; Ke-cun Zhang; Li-hai Tan; Qing-he Niu; Ben-li Liu; Bai-cheng Niu (Journal of Mountain Science, 2022)

Study of Hybrid Propulsion Systems for Lower Emissions and Fuel Saving on Merchant Ship during Voyage - Cheng Siong Chin; Yan-Jie Tan; Mohan Venkatesh Kumar (Journal of Marine Science and Engineering, 2022)
The hybrid propulsion system is a vehicle propulsion system with two or more sources of propulsion such as diesel, batteries, and other renewable energy. The use of hybrid propulsion systems is not new, and they have been adopted worldwide. There are many applications for hybrid propulsion systems, from powering land-based vehicles to marine vessels. With the success of hybrid propulsion systems, many large vessels still rely on two-stroke engines for power generation. In this paper, the benefits and feasibility of using battery systems or hybridizing existing conventional two-stroke engines onboard large intercontinental vessels is studied and simulated. The merchant ship, a bulk carrier with 82,000 deadweight tonnage capacity, is used. The model vessel travels along a simulated route of up to 4000 nautical miles using weather routing software to generate data for estimating emissions with the help of widely adopted empirical formulas. A reduction of up to 3.4 tonnes of emissions and fuel consumption of not more than 1 tonne per kWh from peak shaving and boosting applications for a 12-day voyage were observed.

Comparative Transcriptomic Analysis Reveals the Regulatory Mechanism of Terpene Trilactones Improvement by Exogenous Methyl Jasmonate in Ginkgo biloba - Junping Tan; Muxian Han; Dun Mao; Shuiyuan Cheng; Jiabao Ye; Xiaomeng Liu; Xian Zhang; Jiarui Zheng; Feng Xu; Zexiong Chen; Weiwei Zhang; Yongling Liao (Plant Molecular Biology Reporter, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Another Record: Ocean Warming Continues through 2021 despite La Niña Conditions - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Zhetao Tan; et al. (Advances in Atmospheric Sciences, 2022)
The increased concentration of greenhouse gases in the atmosphere from human activities traps heat within the climate system and increases ocean heat content (OHC). Here, we provide the first analysis of recent OHC changes through 2021 from two international groups. The world ocean, in 2021, was the hottest ever recorded by humans, and the 2021 annual OHC value is even higher than last year’s record value by 14 ± 11 ZJ (1 zetta J = 10 21 J) using the IAP/CAS dataset and by 16 ± 10 ZJ using NCEI/NOAA dataset. The long-term ocean warming is larger in the Atlantic and Southern Oceans than in other regions and is mainly attributed, via climate model simulations, to an increase in anthropogenic greenhouse gas concentrations. The year-to-year variation of OHC is primarily tied to the El Niño-Southern Oscillation (ENSO). In the seven maritime domains of the Indian, Tropical Atlantic, North Atlantic, Northwest Pacific, North Pacific, Southern oceans, and the Mediterranean Sea, robust warming is observed but with distinct inter-annual to decadal variability. Four out of seven domains showed record-high heat content in 2021. The anomalous global and regional ocean warming established in this study should be incorporated into climate risk assessments, adaptation, and mitigation.

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Quality control for ocean observations: From present to future - Zhetao Tan; Bin Zhang; Xiaofen Wu; Mingmei Dong; Lijing Cheng (Science China Earth Sciences, 2022)

PI3K/Akt Signaling Pathway Ameliorates Oxidative Stress-Induced Apoptosis upon Manganese Exposure in PC12 Cells - Yanli Tan; Hong Cheng; Cheng Su; Pan Chen; Xiaobo Yang (Biological Trace Element Research, 2022)

Correction to: Clinical profile of children with parechovirus meningitis in Singapore - Jessica Hui Yin Tan; Chew Thye Choong; Nancy Wen Sim Tee; Chia Yin Chong; Koh Cheng Thoon; Matthias Maiwald; Elis Yue Xian Lee; Melody Si Shan Tan; Natalie Woon Hui Tan (Journal of NeuroVirology, 2022)

Clinical profile of children with parechovirus meningitis in Singapore - Jessica Hui Yin Tan; Chew Thye Choong; Nancy Wen Sim Tee; Chia Yin Chong; Koh Cheng Thoon; Matthias Maiwald; Elis Yue Xian Lee; Melody Si Shan Tan; Natalie Woon Hui Tan (Journal of NeuroVirology, 2022)

Swimming behaviour of silver carp ( Hypophthalmichthys molitrix ) in response to turbulent flow induced by a D ‐cylinder - Senfan Ke; Zhiying Tu; Elsa Goerig; Junjun Tan; Bixin Cheng; Zhimin Li; Xiaotao Shi (Journal of Fish Biology, 2022)
Turbulence is a complex hydraulic phenomenon which commonly occurs in natural streams and fishways. Riverine fish are subjected to heterogeneous flow velocities and turbulence, which may affect their movements and ability to pass the fishways. However, studies focusing on fish response to turbulent flows are lacking for many species. Here we investigate the effects of the turbulence created by a vertical half‐cylinder of various diameters (1.9, 2.5, 3.2 and 5.0 cm) on the swimming ability and behaviour of silver carp, Hypophthalmichthys molitrix . The large D‐cylinders (3.0 and 5.0 cm) create specific vorticity and reduced velocities areas in their vicinity, which favours flow refuging behaviours (FRBs) and thus increased relative critical swimming speeds ( U rcrit , BL/s) of silver carp, by comparison to free‐flow conditions and cylinders of smaller diameter (1.9 and 2.5 cm). The flow speed at which silver carp maximized FRBs such as Karman gaiting downstream of the cylinder, holding position in the bow wake or entraining on the side ranged from 40 to 70 cm s −1 , depending on fish body size. When holding station near a cylinder under optimal flow speeds, the distance between the fish and the cylinder is related to the size of the fish, but also to the size of the cylinder and the produced vortices. The optimal holding region in the drag wake of the cylinder ranged from 28 to 40 cm downstream of the centre of the cylinder, depending on the size of the fish. Smaller fish, however, tend to use the reduced velocities areas located in the bow wake of the large cylinders. We hypothesize that fish will display FRBs, including maintaining a Karman gait in turbulent flow, when the ratio of the cylinder diameter to their body length is between 1:3 and 1:4. They also match their tail beat frequency to the vortex shedding frequency of the cylinder. Our results provide a better understanding of how silver carp respond to turbulent flows around physical structures, with implications for the design of nature‐like fishways or exclusion devices in both its native and invasive ranges.

Seven new glycosides from the leaves of Datura metel L. - Jin-Yan Tan; Yan Liu; Yan-Gang Cheng; Yan-Ping Sun; Xiao-Mao Li; Wei Guan; Juan Pan; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Identification of A-to-I RNA editing profiles and their clinical relevance in lung adenocarcinoma - Cheng Wang; Mingtao Huang; Congcong Chen; Yuancheng Li; Na Qin; Zijian Ma; Jingyi Fan; Linnan Gong; Hui Zeng; Liu Yang; Xianfeng Xu; Jun Zhou; et al. (Science China Life Sciences, 2022)

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Probing the Functional and Structural Connectivity Underlying EEG Traveling Waves - Yun Qin; Nan Zhang; Yan Chen; Yue Tan; Zhenglin Yang; Yi Shi; Cheng Luo; Tiejun Liu; Dezhong Yao (Brain Topography, 2022)

Different changes in pre- and postsynaptic components in the hippocampal CA1 subfield after transient global cerebral ischemia - Yan Zhang; Bai-Hong Tan; Shuang Wu; Cheng-Hao Wu; Jia-Le Suo; Yue Gui; Cheng-Mei Zhou; Yan-Chao Li (Brain Structure and Function, 2022)

Six-DOF CFD Simulations of Underwater Vehicle Operating Underwater Turning Maneuvers - Kunyu Han; Xide Cheng; Zuyuan Liu; Chenran Huang; Haichao Chang; Jianxi Yao; Kangli Tan (Journal of Marine Science and Engineering, 2021)
Maneuverability, which is closely related to operational performance and safety, is one of the important hydrodynamic properties of an underwater vehicle (UV), and its accurate prediction is essential for preliminary design. The purpose of this study is to analyze the turning ability of a UV while rising or submerging; the computational fluid dynamics (CFD) method was used to numerically predict the six-DOF self-propelled maneuvers of submarine model BB2, including steady turning maneuvers and space spiral maneuvers. In this study, the overset mesh method was used to deal with multi-body motion, the body force method was used to describe the thrust distribution of the propeller at the model scale, and the numerical prediction also included the dynamic deflection of the control planes, where the command was issued by the autopilot. Then, this study used the published model test results of the tank to verify the effectiveness of the CFD prediction of steady turning maneuvers, and the prediction of space spiral maneuvers was carried out on this basis. The numerical results show that the turning motion has a great influence on the depth and pitch attitude of the submarine, and a “stern heavier” phenomenon occurs to a submarine after steering. The underwater turning of a submarine can not only reduce the speed to brake but also limit the dangerous depth. The conclusion is of certain reference significance for submarine emergency maneuvers.

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Household environmental microbiota influences early‐life eczema development - Le Duc Huy Ta; Carina Jing Xuan Tay; Christophe Lay; Paola Florez de Sessions; Cheryl Pei Ting Tan; Michelle Jia Yu Tay; Hui Xing Lau; Atiqa Binte Zulkifli; Gaik Chin Yap; Elizabeth Huiwen Tham; Eliza Xin Pei Ho; Anne Eng Neo Goh; et al. (Environmental Microbiology, 2021)
Summary Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment.

The effect of fasting and energy restricting diets on markers of glucose and insulin controls: a systematic review and meta-analysis of randomized controlled trials - Somaye Fatahi; Ali Nazary-Vannani; Mohammad Hassan Sohouli; Zeinab Mokhtari; Hamed Kord-Varkaneh; Vihan Moodi; Shing Cheng Tan; Teck Yew Low; Fernando Zanghelini; Farzad Shidfar (Critical Reviews in Food Science and Nutrition, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Two new nor-sesquiterpenoids from Fusarium tricinctum , an endophytic fungus isolated from Ligusticum chuanxiong - Yu-Mei Cao; Da-Le Guo; Meng-Ying Jin; Lu Tan; Tian-Long Yang; Fang Deng; Yu-Cheng Gu; Xiao-Hua Li; Zhi-Xing Cao; Yun Deng (Natural Product Research, 2021)

Additive and Epistatic QTL on Cadmium (Cd) Tolerance Associated with Seed Germinating Ability in Rice - Changsheng Li; Peng Wang; Guangliang Wu; Yanning Wang; Qin Cheng; Yicong Cai; Dahu Zhou; Caijing Li; Xiangyu Zhang; Jingai Tan; Cuijuan Li; Haohua He; et al. (Journal of Plant Growth Regulation, 2021)

Correction to: Regulation of algal and cyanobacterial auxin production, physiology, and application in agriculture: an overview - Cheng-Yau Tan; Ian Charles Dodd; Jit Ern Chen; Siew-Moi Phang; Chiew Foan Chin; Yoon-Yen Yow; Shyamala Ratnayeke (Journal of Applied Phycology, 2021)

Regulation of algal and cyanobacterial auxin production, physiology, and application in agriculture: an overview - Cheng-Yau Tan; Ian Charles Dodd; Jit Ern Chen; Siew-Moi Phang; Chiew Foan Chin; Yoon-Yen Yow; Shyamala Ratnayeke (Journal of Applied Phycology, 2021)

Correlations between Dual-Pathway White Matter Alterations and Language Impairment in Patients with Aphasia: A Systematic Review and Meta-analysis - Jie Zhang; Shuchang Zhong; Liang Zhou; Yamei Yu; Xufei Tan; Min Wu; Peng Sun; Wei Zhang; Juebao Li; Ruidong Cheng; Yanfei Wu; Yanmei Yu; et al. (Neuropsychology Review, 2021)

RETRACTED ARTICLE: Comprehensive evaluation of water resources carrying capacity and analysis of obstacle factors in Weifang City based on hierarchical cluster analysis-VIKOR method - Haiyan Yang; Yinan Tan; Xiaobo Sun; Xiaowen Cheng; Guangqi Liu; Guangyu Zhou (Environmental Science and Pollution Research, 2021)

Modulation of the 5-HT 3 A receptor current by desacylbaldrinal - Li-Xia Wang; Hu-Lan Chen; Hong-Ling Yan; Fei Tang; Hai Zhang; Hong-Xiang Li; Qiang Ye; Cheng Peng; Yu-Zhu Tan (Natural Product Research, 2021)

Experimental and Numerical Characterization of Lower Huron Shale as a Heterogeneous Material - Ming Fan; Yanhui Han; Xinyu Tan; Liang Fan; Ellen S. Gilliland; Nino Ripepi; Cheng Chen (Rock Mechanics and Rock Engineering, 2021)

The trophocytes and oenocytes of worker and queen honey bees (Apis mellifera) exhibit distinct age-associated transcriptome profiles - Cheng-Yen Lu; Yu-Ting Weng; Bertrand Tan; Chin-Yuan Hsu (GeroScience, 2021)

Experiment on the Effect of Freezing–Thawing Cyclic on Mechanical Properties of Solidified Sludge - Cheng Peng; Zongkun Tian; Hui Long; Yuqing Tan (Geotechnical and Geological Engineering, 2021)

An underlying mechanism of qE deficiency in marine angiosperm Zostera marina - Wei Zhao; Quan Sheng Zhang; Ying Tan; Zhe Liu; Ming Yu Ma; Meng Xin Wang; Cheng Ying Luo (Photosynthesis Research, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Global transcriptomic profiles of circulating leucocytes in early lactation cows with clinical or subclinical mastitis - Zhangrui Cheng; Laura Buggiotti; Mazdak Salavati; Cinzia Marchitelli; Sergio Palma-Vera; Alistair Wylie; Haruko Takeda; Lijing Tang; Mark A. Crowe; D. Claire Wathes; Mark Crowe; Niamh McLoughlin; et al. (Molecular Biology Reports, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Arbuscular mycorrhizal fungi and its major role in plant growth, zinc nutrition, phosphorous regulation and phytoremediation - Parashuram Bhantana; Muhammad Shoaib Rana; Xue-cheng Sun; Mohamed G. Moussa; Muhammad Hamzah Saleem; Muhamad Syaifudin; Ashrafuzzaman Shah; Amrit Poudel; Amar Bahadur Pun; Mufid Alam Bhat; Dhanik Lal Mandal; Sujit Shah; et al. (Symbiosis, 2021)

Water abundance prediction of sandstone aquifers based on the distance function - Fei Tan; Xiaozhi Cheng; Daolei Xie; Xiaoquan Man; Jiuchuan Wei; Jianguo Xu; Jie Han; Guangxue Zhang (Arabian Journal of Geosciences, 2021)

A rapid assessment method for calculating the drag coefficient in wave attenuation by vegetation - Zhilin Zhang; Bensheng Huang; Hongxiang Ji; Xin Tian; Jing Qiu; Chao Tan; Xiangju Cheng (Acta Oceanologica Sinica, 2021)

AKR1C1 Contributes to Cervical Cancer Progression via Regulating TWIST1 Expression - Xing Wei; Zhongheng Wei; Yueyong Li; Zhongqiu Tan; Cheng Lin (Biochemical Genetics, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Novel Peptide Inhibitors of β-Catenin Effectively Suppress the Tumorigenesis of Colorectal Cancer - Honglin Liu; Xingyun Liu; Yuexi Li; Xia Zhou; Xiutao Tan; Bo Niu; Niuliang Cheng; Hailin Liu (International Journal of Peptide Research and Therapeutics, 2021)

Fireflies in Southeast Asia: knowledge gaps, entomotourism and conservation - Shawn Cheng; Mohd Azahari Faidi; Sek-Aun Tan; Jeyanny Vijayanathan; Masbudi Abdul Malek; Bidasari Bahashim; Mohd Noor Mat Isa (Biodiversity and Conservation, 2021)

Polyamine oxidase (PAO)–mediated polyamine catabolism plays potential roles in peach (Prunus persica L.) fruit development and ripening - Wei Wang; Xianbo Zheng; Shihao Liu; Bin Tan; Jun Cheng; Xia Ye; Jidong Li; Jiancan Feng (Tree Genetics & Genomes, 2021)

Two-dimensional transition metal phthalocyanine sheet as a promising electrocatalyst for nitric oxide reduction: a first principle study - Shiqiang Liu; Yawei Liu; Zhiwen Cheng; Xiaoping Gao; Yujia Tan; Zhemin Shen; Tao Yuan (Environmental Science and Pollution Research, 2021)

Rapid assessment of landslide risk level based on deep learning - Fei Tan; Jin Yu; Yu-Yong Jiao; Dawei Lin; Jiahe Lv; Yi Cheng (Arabian Journal of Geosciences, 2021)

Progress and prospects of applied research on physical geography and the living environment in China over the past 70 years (1949–2019) - Fahu Chen; Shaohong Wu; Peng Cui; Yunlong Cai; Yili Zhang; Yunhe Yin; Guobin Liu; Zhu Ouyang; Wei Ma; Linsheng Yang; Duo Wu; Jiaqiang Lei; et al. (Journal of Geographical Sciences, 2021)

Electro-Acupuncture Inhibits p66Shc-Mediated Oxidative Stress to Facilitate Functional Recovery After Spinal Cord Injury - Ming Cheng; Xiaojing Wu; Fei Wang; Bo Tan; Jiang Hu (Journal of Molecular Neuroscience, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Numerical simulations of incompressible fluid flow in synthetic fractures using lattice Boltzmann method - Guan Rong; Long Cheng; Junsong Quan; Yaosheng Tan; Renhui He; Jie Tan (Arabian Journal of Geosciences, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

A multiple-proxy stalagmite record reveals historical deforestation in central Shandong, northern China - Liangcheng Tan; Wen Liu; Tianli Wang; Peng Cheng; Jingjie Zang; Xiqian Wang; Le Ma; Dong Li; Jianghu Lan; R. Lawrence Edwards; Hai Cheng; Hai Xu; et al. (Science China Earth Sciences, 2020)

Key Role of Pro-inflammatory Cytokines in the Toxic Effect of Fluoride on Hepa1-6 Cells - Yan Zhang; Bian-hua Zhou; Pan-pan Tan; Yu Chen; Cheng-yi Miao; Hong-wei Wang (Biological Trace Element Research, 2020)

The characteristics and genome analysis of vB_ApiP_XC38, a novel phage infecting Acinetobacter pittii - Mengjun Cheng; Man Luo; Hengyu Xi; Yunze Zhao; Shuai Le; Li-Kuang Chen; Demeng Tan; Yuan Guan; Tianqi Wang; Wenyu Han; Nannan Wu; Tongyu Zhu; et al. (Virus Genes, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Solution of a Bolted Spherical Cavity in Elastoplastic Medium and Its Application to Extrusion Analysis of Tunnel Face - Cheng Hua TAN (Rock Mechanics and Rock Engineering, 2020)

Bergaptol, a mechanism-based inactivator of CYP2C9 - Tingting Jiang; Ting Cheng; Jing Li; Mengyue Zhou; Rong Tan; Xiaojing Yang; Yang Wang; Weiwei Li; Jiang Zheng (Medicinal Chemistry Research, 2020)

Genetic analysis of germinating ability under alkaline and neutral salt stress by a high-density bin genetic map in rice - Xin Luo; Haodong Deng; Peng Wang; Xiangyu Zhang; Caijing Li; Cuijuan Li; Jingai Tan; Guangliang Wu; Yanning Wang; Qin Cheng; Haohua He; Jianmin Bian (Euphytica, 2020)

A comparative study of UV/H2O2 and UV/PDS for the degradation of micro-pollutants: kinetics and effect of water matrix - Jing Gao; Congwei Luo; Lu Gan; Daoji Wu; Fengxun Tan; Xiaoxiang Cheng; Weiwei Zhou; Shishun Wang; Fumiao Zhang; Jun Ma (Environmental Science and Pollution Research, 2020)

Improved Production of Pyrroloquinoline Quinone by Simultaneous Augmentation of Its Synthesis Gene Expression and Glucose Metabolism in Klebsiella pneumoniae - Zhiwei Mi; Jingchao Cheng; Peng Zhao; Pingfang Tian; Tianwei Tan (Current Microbiology, 2020)

A compartmental approach to isosteviol’s disposition in Sprague-Dawley rats - Ayorinde ADEHIN; Keai Sinn TAN; Chengjuan ZOU; Zhiqiang LU; Yue LIN; Dongfang WANG; Qing CHENG; Wen TAN (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

P-wave velocity structures of the crust across the Southern Taiwan Strait imaged by using air-gun data recorded from ocean-bottom seismometers - Tan K. Wang; Jia Ming Deng; Jing Wang; Yu Hsuan Cheng; Zhi Zhao Xie; Yi Feng Zhang (Marine Geophysical Research, 2020)

Pictalignans D-F, three new neolignan derivatives from Selaginella picta - Fei Cheng; Zhen-Xing Zou; Ping-Sheng Xu; Shui-Han Zhang; Yan Zhang; Cai-Ping Yao; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Biocontrol potential of Bacillus subtilis IBFCBF-4 against Fusarium wilt of watermelon - Jiuxiang Zhu; Taimeng Tan; Airong Shen; Xiebin Yang; Yongting Yu; Chunsheng Gao; Zhimin Li; Yi Cheng; Jia Chen; Litao Guo; Xiangping Sun; Zhun Yan; et al. (Journal of Plant Pathology, 2020)

Shewanella oneidensis MR-1 impregnated Ca-alginate capsule for efficient Cr(VI) reduction and Cr(III) adsorption - Cheng Yu; Yi Zhang; Yu Fang; Yujie Tan; Ke Dai; Shilin Liu; Qiaoyun Huang (Environmental Science and Pollution Research, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

HOXB13 expression is correlated with hepatic inflammatory activity of patients with hepatic fibrosis - Lingyun Zuo; Tingting Tan; Cheng Wei; Huali Wang; Luxuan Tan; Yingying Hao; Jingjing Qian; Yuxin Chen; Chao Wu (Journal of Molecular Histology, 2020)

Clinical and biochemical indexes from 2019-nCoV infected patients linked to viral loads and lung injury - Yingxia Liu; Yang Yang; Cong Zhang; Fengming Huang; Fuxiang Wang; Jing Yuan; Zhaoqin Wang; Jinxiu Li; Jianming Li; Cheng Feng; Zheng Zhang; Lifei Wang; et al. (Science China Life Sciences, 2020)

Novel mutations in SPEF2 causing different defects between flagella and cilia bridge: the phenotypic link between MMAF and PCD - Chaofeng Tu; Hongchuan Nie; Lanlan Meng; Weili Wang; Haiyu Li; Shimin Yuan; Dehua Cheng; Wenbin He; Gang Liu; Juan Du; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2020)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Experimental Study on Interaction Between Degrees of Freedom in a Wave Buoy - Shuting Huang; Hongda Shi; Feifei Cao; Junzhe Tan; Haixun Cheng; Demin Li; Shangze Liu; Haoxiang Gong; Ji Tao (Journal of Ocean University of China, 2019)

Numerical and Experimental Study on the Cracking Behavior of Marble with En-Echelon Flaws - Yi Cheng; Yu-Yong Jiao; Fei Tan (Rock Mechanics and Rock Engineering, 2019)

Correction to: SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

Changes in area and number of nature reserves in China - Zhijun Ma; Ying Chen; David S. Melville; Jun Fan; Jianguo Liu; Jinwei Dong; Kun Tan; Xuefei Cheng; Richard A. Fuller; Xiangming Xiao; Bo Li (Conservation Biology, 2019)
Nature reserves (NR) are the cornerstone of biodiversity conservation. Over the past 60 years, the rapid expansion of NRs in China, one of the world's megadiverse countries, has played a critical role in slowing biodiversity loss. We examined the changes in the number and area of China's NRs from 1956 to 2014 and analyzed the effect of economic development on the expansion of China's NRs from 2005 to 2014 with linear models. Despite a continuing increase in the number of NRs, the total area of China's NRs decreased by 3% from 2007 to 2014. This loss resulted from downsizing and degazettement of existing NRs and a slowdown in the establishment of new ones. Nature reserves in regions with rapid economic development exhibited a greater decrease in area, suggesting that downsizing and degazettement of NRs are closely related to the intensifying competition between economic growth and conservation. For example, boundary adjustments to national NRs, the most strictly protected NRs, along the coast of China's Yellow Sea, a global biodiversity hotspot with a fast‐growing economy, resulted in the loss of one‐third of the total area. One of the most important ecosystems in these NRs, tidal wetlands, decreased by 27.8% because of boundary adjustments and by 25.2% because of land reclamation. Our results suggest conservation achievement, in terms of both area and quality, are declining at least in some regions in the Chinese NR estate. Although the designation of protected areas that are primarily managed for sustainable use has increased rapidly in recent years in China, we propose that NRs with biodiversity conservation as their main function should not be replaced or weakened.

Paleocene Neo-Tethyan slab rollback constrained by A1-type granitic intrusion in the Gaoligong–Tengliang–Yingjiang belt of the Eastern Himalayan Syntaxis, SE Tibet - Zheng Liu; Shi-Yong Liao; Shu-Cheng Tan; Xiao-Hu He; Guo-Chang Wang; Dong-Bing Wang; Qing Zhou (International Journal of Earth Sciences, 2019)

Self-rooted grafting influences the growth and cadmium accumulation characteristics in the post generation of Cosmos sulphureus - Jin Wang; Yumei Tan; Ming’an Liao; Lijin Lin; Yi Tang; Huifen Zhang; Hui Xia; Dong Liang; Qunxian Deng; Xiulan Lv; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

Rainfall seasonality changes and its possible teleconnections with global climate events in China - Shulin Deng; Ni Yang; Manchun Li; Liang Cheng; Zhenjie Chen; Yanming Chen; Tan Chen; Xiaoqiang Liu (Climate Dynamics, 2019)

Is Chinese stalagmite δ18O solely controlled by the Indian summer monsoon? - Dong Li; Liangcheng Tan; Yanjun Cai; Xiuyang Jiang; Le Ma; Hai Cheng; R. Lawrence Edwards; Haiwei Zhang; Yongli Gao; Zhisheng An (Climate Dynamics, 2019)

Late Holocene hydroclimatic variations and possible forcing mechanisms over the eastern Central Asia - Jianghu Lan; Hai Xu; Keke Yu; Enguo Sheng; Kangen Zhou; Tianli Wang; Yuanda Ye; Dongna Yan; Huixian Wu; Peng Cheng; Waili Abuliezi; Liangcheng Tan (Science China Earth Sciences, 2019)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

Characteristics of failure area and failure mechanism of a bedding rockslide in Libo County, Guizhou, China - Lianheng Zhao; Dejian Li; Hanhua Tan; Xiao Cheng; Shi Zuo (Landslides, 2019)

Skipping of an exon with a nonsense mutation in the DMD gene is induced by the conversion of a splicing enhancer to a splicing silencer - Yanrong Zhu; Huiting Deng; Xiangfa Chen; Hui Li; Cheng Yang; Shuo Li; Xiaoying Pan; Siqi Tian; Shuxin Feng; Xiaoyue Tan; Masafumi Matsuo; Zhujun Zhang (Human Genetics, 2019)

A panel analysis of the sustainability of logistics industry in China: based on non-radial slacks-based method - Lingling Tan; Qunqi Wu; Qian Li; Wen Cheng; Yulei Gu (Environmental Science and Pollution Research, 2019)

Correction to: On the variation of the Pacific center: a revisit to the physical nature of Arctic Oscillation - Qian Cheng; Benkui Tan (Climate Dynamics, 2019)

On the variation of the Pacific center: a revisit to the physical nature of Arctic Oscillation - Qian Cheng; Benkui Tan (Climate Dynamics, 2019)

Application of Avaatech X-ray fluorescence core-scanning in Sr/Ca analysis of speleothems - Dong Li; Liangcheng Tan; Fei Guo; Yanjun Cai; Youbin Sun; Gang Xue; Xing Cheng; Hong Yan; Hai Cheng; R. Lawrence Edwards; Yongli Gao; Jessica Kelley (Science China Earth Sciences, 2019)

Genome-wide identification of Ziziphus jujuba TCP transcription factors and their expression in response to infection with jujube witches’ broom phytoplasma - Peng Chen; Jidong Li; Xia Ye; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Huiyu Wang; Liyuan Gu; Jiancan Feng (Acta Physiologiae Plantarum, 2019)

Isolation and identification of a Bacillus subtilis HZ-72 exhibiting biocontrol activity against flax seedling blight - Taimeng Tan; Jiuxiang Zhu; Airong Shen; Jilie Li; Yongting Yu; Mengjun Zhang; Mengrui Zhao; Zhimin Li; Jia Chen; Chunsheng Gao; Yi Cheng; Litao Guo; et al. (European Journal of Plant Pathology, 2019)

Reconstructing the western boundary variability of the Western Pacific Subtropical High over the past 200 years via Chinese cave oxygen isotope records - Jingyao Zhao; Hai Cheng; Yan Yang; Liangcheng Tan; Christoph Spötl; Youfeng Ning; Haiwei Zhang; Xing Cheng; Zhe Sun; Xianglei Li; Hanying Li; Wen Liu; et al. (Climate Dynamics, 2019)

Spatiotemporal analysis of hydro-meteorological drought in the Johor River Basin, Malaysia - Mou Leong Tan; Vivien P. Chua; Cheng Li; K. Brindha (Theoretical and Applied Climatology, 2019)

Two new compounds from the fruit of Ailanthus altissima - Jian-Cheng Ni; Jian-Ting Shi; Qing-Wei Tan; Qi-Jian Chen (Natural Product Research, 2019)

Validation results of maximum S4 index in F-layer derived from GNOS on FY3C satellite - Weihua Bai; Yueqiang Sun; Junming Xia; Guangyuan Tan; Cheng Cheng; Guanglin Yang; Qifei Du; Xianyi Wang; Danyang Zhao; Yusen Tian; Xiaoxin Zhang; Mi Liao; et al. (GPS Solutions, 2019)

Exogenous application of GA3 inactively regulates axillary bud outgrowth by influencing of branching-inhibitors and bud-regulating hormones in apple (Malus domestica Borkh.) - Ming Tan; Guofang Li; Xiaojie Liu; Fang Cheng; Juanjuan Ma; Caiping Zhao; Dong Zhang; Mingyu Han (Molecular Genetics and Genomics, 2018)

Neuritogenic and in vitro antioxidant activities of Malaysian Gracilaria manilaensis Yamamoto & Trono - Jun-Rui Pang; Veronica Ming-Jun Goh; Cheng-Yau Tan; Siew-Moi Phang; Kah-Hui Wong; Yoon-Yen Yow (Journal of Applied Phycology, 2018)

Analysis of meteorological dryness/wetness features for spring wheat production in the Ili River basin, China - Cheng Li; Ranghui Wang; Jianxiang Xu; Yunjian Luo; Mou Leong Tan; Yelin Jiang (International Journal of Biometeorology, 2018)

Case histories of rock bursts under complicated geological conditions - Tong-bin Zhao; Wei-yao Guo; Yun-liang Tan; Cai-ping Lu; Cheng-wu Wang (Bulletin of Engineering Geology and the Environment, 2018)

Molecular role of cytokinin in bud activation and outgrowth in apple branching based on transcriptomic analysis - Guofang Li; Ming Tan; Fang Cheng; Xiaojie Liu; Siyan Qi; Hongfei Chen; Dong Zhang; Caiping Zhao; Mingyu Han; Juanjuan Ma (Plant Molecular Biology, 2018)

Reinforcement of resistance of modern rose to black spot disease via hybridization with Rosa rugosa - Tingliang Xu; Yuying Wu; Xingwan Yi; Jiongrui Tan; Hongxia Zhao; Chao Yu; Le Luo; Tangren Cheng; Jia Wang; Huitang Pan; Qixiang Zhang (Euphytica, 2018)

Dune dynamics in the southern edge of Dunhuang Oasis and implications for the oasis protection - Zhi-shan An; Ke-cun Zhang; Li-hai Tan; Hu Zhang; Bai-cheng Niu (Journal of Mountain Science, 2018)

A Forchheimer Equation-Based Flow Model for Fluid Flow Through Rock Fracture During Shear - Guan Rong; Jie Yang; Long Cheng; Jie Tan; Jun Peng; Chuangbing Zhou (Rock Mechanics and Rock Engineering, 2018)

Genistein has the function of alleviating and treating disseminated intravascular coagulation caused by lipopolysaccharide - Xueqin Chen; Jingyi Tan; Mengqi Yang; Zhi-Kai Liao; Cheng Lu; Youwei Huang; Liang-Cai Wu (Journal of Natural Medicines, 2018)

Physical Simulation of Water Inrush through the Mine Floor from a Confined Aquifer - Baohua Guo; Tan Cheng; Long Wang; Tao Luo; Xiaoyu Yang (Mine Water and the Environment, 2018)

Mechanisms of Interaction Between an Arch Dam and Abutment Slope Using Physical Model Tests - Guanhua Sun; Shan Lin; Shengguo Cheng; Tan Sui; Chunguang Li; Hong Zheng (Rock Mechanics and Rock Engineering, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

Risk prediction in infective endocarditis by modified MELD-XI score - Peng-cheng He; Xue-biao Wei; Si-ni Luo; Xiao-lan Chen; Zu-hui Ke; Dan-qing Yu; Ji-yan Chen; Yuan-hui Liu; Ning Tan (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Modelling the Diurnal Variations of Methane Emissions from the Cyperus malaccensis Tidal Marsh in the Minjiang River Estuary - Yinrui Cheng; Chuan Tong; Dandan Du; Lishan Tan; Hangfei Li; Qinghua Rao (Wetlands, 2018)

Enhancement of the thermal and alkaline pH stability of Escherichia coli lysine decarboxylase for efficient cadaverine production - Fengyu Kou; Jing Zhao; Jiao Liu; Cunmin Sun; Yanmei Guo; Zijian Tan; Feng Cheng; Zhimin Li; Ping Zheng; Jibin Sun (Biotechnology Letters, 2018)

Excitation transfer and trapping kinetics in plant photosystem I probed by two-dimensional electronic spectroscopy - Parveen Akhtar; Cheng Zhang; Zhengtang Liu; Howe-Siang Tan; Petar H. Lambrev (Photosynthesis Research, 2018)

The complete mitochondrial genome sequence of Changbai Mountains wild boar (Cetartiodactyla: Suidae) - Zhen-Dong Tan; Lin-Yuan Shen; Xiao Cheng; Mai-Lin Gan; Shun-Hua Zhang; Li Zhu (Conservation Genetics Resources, 2018)

Resveratrol induces apoptosis and inhibits adipogenesis by stimulating the SIRT1-AMPKα-FOXO1 signalling pathway in bovine intramuscular adipocytes - Xiaomu Liu; Hongbo Zhao; Qing Jin; Wei You; Haijian Cheng; Yifan Liu; Enliang Song; Guifen Liu; Xiuwen Tan; Xianglun Zhang; Fachun Wan (Molecular and Cellular Biochemistry, 2018)

The validation of two major QTLs related to the timing of spring bud flush in Camellia sinensis - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Kang Wei; Yao Zou; Sheng-Xiang Chen; Pin-Wu Li; Qian Tang; Hao Cheng (Euphytica, 2018)

Development of Brassica oleracea-nigra monosomic alien addition lines: genotypic, cytological and morphological analyses - Chen Tan; Cheng Cui; Yi Xiang; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2017)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

A new genus and species of abyssal sponge commonly encrusting polymetallic nodules in the Clarion-Clipperton Zone, East Pacific Ocean - Swee-Cheng Lim; Helena Wiklund; Adrian G. Glover; Thomas G. Dahlgren; Koh-Siang Tan (Systematics and Biodiversity, 2017)

Multiple locus genome-wide association studies for important economic traits of oil palm - Maizura Ithnin; Yang Xu; Marhalil Marjuni; Norhalida Mohamed Serdari; Mohd Din Amiruddin; Eng-Ti Leslie Low; Yung-Chie Tan; Soon-Joo Yap; Leslie Cheng Li Ooi; Rajanaidu Nookiah; Rajinder Singh; Shizhong Xu (Tree Genetics & Genomes, 2017)

The in vitro photodynamic activity, photophysical and photochemical research of a novel chlorophyll-derived photosensitizer - Guanghui Tan; Qi Wang; Hongyue Zhang; Jianjun Cheng; Zhiqiang Wang; Fengyu Qu; Changhong Guo; Yingxue Jin (Medicinal Chemistry Research, 2017)

Transgenic Mice Overexpressing the Divalent Metal Transporter 1 Exhibit Iron Accumulation and Enhanced Parkin Expression in the Brain - Cheng-Wu Zhang; Yee Kit Tai; Bing-Han Chai; Katherine C. M. Chew; Eng-Tat Ang; Fai Tsang; Bryce W. Q. Tan; Eugenia T. E. Hong; Abu Bakar Ali Asad; Kai-Hsiang Chuang; Kah-Leong Lim; Tuck Wah Soong (NeuroMolecular Medicine, 2017)

MiR-9 enhances the sensitivity of A549 cells to cisplatin by inhibiting autophagy - Yan Zhang; Xia Meng; Cheng Li; Zhoulin Tan; Xinwei Guo; Zhiting Zhang; Tao Xi (Biotechnology Letters, 2017)

Uptake, transport and distribution of molybdenum in two oilseed rape (Brassica napus L.) cultivars under different nitrate/ammonium ratios - Shi-yu Qin; Xue-cheng Sun; Cheng-xiao Hu; Qi-ling Tan; Xiao-hu Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Association of Toll-like receptor 3 gene polymorphism with the severity of enterovirus 71 infection in Chinese children - Hongfang He; Shihai Liu; Pei-pei Liu; Qiu-bo Li; Yu-xia Tan; Ya Guo; Fei Li; Yuan-yuan Wang; Ye-dan Liu; Cheng-qing Yang; Zong-bo Chen (Archives of Virology, 2017)

Fine mapping of a Phytophthora-resistance gene RpsWY in soybean (Glycine max L.) by high-throughput genome-wide sequencing - Yanbo Cheng; Qibin Ma; Hailong Ren; Qiuju Xia; Enliang Song; Zhiyuan Tan; Shuxian Li; Gengyun Zhang; Hai Nian (Theoretical and Applied Genetics, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effectiveness of SO2 emission control policy on power plants in the Yangtze River Delta, China—post-assessment of the 11th Five-Year Plan - Jiani Tan; Joshua S. Fu; Kan Huang; Cheng-En Yang; Guoshun Zhuang; Jian Sun (Environmental Science and Pollution Research, 2017)

Decreasing monsoon precipitation in southwest China during the last 240 years associated with the warming of tropical ocean - Liangcheng Tan; Yanjun Cai; Zhisheng An; Hai Cheng; Chuan-Chou Shen; Yongli Gao; R. Lawrence Edwards (Climate Dynamics, 2017)

Applying the strategy of light environment control to improve the biomass and polysaccharide production of Nostoc flagelliforme - Pei-pei Han; Shi-gang Shen; Hui-Yan Wang; Shun-yu Yao; Zhi-lei Tan; Cheng Zhong; Shi-ru Jia (Journal of Applied Phycology, 2017)

Inhibitory effect of Shenqi Fuzheng injection combined with docetaxel on lung cancer cells - Bo-yu Dong; Cheng Wang; Li Tan; Ning Tan; Meng-di Zhao; Yang Lu; Shou-ying Du (Journal of Zhejiang University-SCIENCE B, 2017)

Transcriptome analysis reveals critical genes and key pathways involved in early phyllotaxy development in maize - Xiaojian Peng; Wenbo Chai; Yingquan Tan; Qing Dong; Haiyang Jiang; Beijiu Cheng; Yang Zhao (Genes & Genomics, 2017)

Permian–Triassic boundary microbialites (PTBMs) in southwest China: implications for paleoenvironment reconstruction - Hao Tang; Stephen Kershaw; Hong Liu; Xiucheng Tan; Fei Li; Guang Hu; Cheng Huang; Lichao Wang; Chengbo Lian; Ling Li; Xuefei Yang (Facies, 2017)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

A comparison of two photosynthesis parameterization schemes for an alpine meadow site on the Qinghai-Tibetan Plateau - Xufeng Wang; Guodong Cheng; Xin Li; Ling Lu; Mingguo Ma; Peixi Su; Gaofeng Zhu; Junlei Tan (Theoretical and Applied Climatology, 2016)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

Effect of solvent on debromination of decabromodiphenyl ether by Ni/Fe nanoparticles and nano zero-valent iron particles - Lei Tan; Bin Liang; Wen Cheng; Zhanqiang Fang; Eric Pokeung Tsang (Environmental Science and Pollution Research, 2016)

A CONSTANS-like transcriptional activator, OsCOL13, functions as a negative regulator of flowering downstream of OsphyB and upstream of Ehd1 in rice - Peike Sheng; Fuqing Wu; Junjie Tan; Huan Zhang; Weiwei Ma; Liping Chen; Jiachang Wang; Jie Wang; Shanshan Zhu; Xiuping Guo; Jiulin Wang; Xin Zhang; et al. (Plant Molecular Biology, 2016)

The Role of MAPT in Neurodegenerative Diseases: Genetics, Mechanisms and Therapy - Cheng-Cheng Zhang; Ang Xing; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Distinct subgenome stabilities in synthesized Brassica allohexaploids - Jiannan Zhou; Chen Tan; Cheng Cui; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2016)

SSR-based genetic mapping and QTL analysis for timing of spring bud flush, young shoot color, and mature leaf size in tea plant (Camellia sinensis) - Li-Qiang Tan; Li-Yuan Wang; Li-Yi Xu; Li-Yun Wu; Min Peng; Cheng-Cai Zhang; Kang Wei; Pei-Xian Bai; Hai-Lin Li; Hao Cheng; Gui-Nian Qi (Tree Genetics & Genomes, 2016)

Prevalence of Balantidium coli infection in sows in Hunan province, subtropical China - De-Ming Yin; Cong-Cong Lv; Lei Tan; Tie-Niu Zhang; Cheng-Zhi Yang; Yi Liu; Wei Liu (Tropical Animal Health and Production, 2015)

Aptamers Selected by Cell-SELEX for Molecular Imaging - Cheng Jin; Jing Zheng; Chunmei Li; Liping Qiu; Xiaobing Zhang; Weihong Tan (Journal of Molecular Evolution, 2015)

MicroRNA expression profile of mature dendritic cell in chronic rhinosinusitis - Zu-Xia Ma; Xi Tan; Yang Shen; Xia Ke; Yu-Cheng Yang; Xing-Bo He; Zhi-Hai Wang; Yu-Bing Dai; Su-Ling Hong; Guo-Hua Hu (Inflammation Research, 2015)

Fingerprinting 128 Chinese clonal tea cultivars using SSR markers provides new insights into their pedigree relationships - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Sheng-Xiang Chen; Yao Zou; Gui-Nian Qi; Hao Cheng (Tree Genetics & Genomes, 2015)

Metformin synergizes 5-fluorouracil, epirubicin, and cyclophosphamide (FEC) combination therapy through impairing intracellular ATP production and DNA repair in breast cancer stem cells - Jaslyn Sian-Siu Soo; Char-Hong Ng; Si Hoey Tan; Rozita Abdul Malik; Yew-Ching Teh; Boon-Shing Tan; Gwo-Fuang Ho; Mee-Hoong See; Nur Aishah Mohd Taib; Cheng-Har Yip; Felicia Fei-Lei Chung; Ling-Wei Hii; et al. (Apoptosis, 2015)

Assessment of a Four-View Mammographic Image Feature Based Fusion Model to Predict Near-Term Breast Cancer Risk - Maxine Tan; Jiantao Pu; Samuel Cheng; Hong Liu; Bin Zheng (Annals of Biomedical Engineering, 2015)

Antigenic variation of the human influenza A (H3N2) virus during the 2014–2015 winter season - Sha Hua; XiYan Li; Mi Liu; YanHui Cheng; YouSong Peng; WeiJuan Huang; MinJu Tan; HeJiang Wei; JunFeng Guo; DaYan Wang; AiPing Wu; YueLong Shu; et al. (Science China Life Sciences, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Experimental studies on the Danxia landscape morphogenesis in Mt. Danxiashan, South China - Cheng Zhu; Li Wu; Tongxin Zhu; Rongfeng Hou; Zhinong Hu; Yan Tan; Wei Sun; Tianjiao Jia; Hua Peng (Journal of Geographical Sciences, 2015)

Endoplasmic reticulum stress participates in the progress of senescence of bone marrow-derived mesenchymal stem cells in patients with systemic lupus erythematosus - Zhifeng Gu; Yan Meng; Tao Tao; Genkai Guo; Wei Tan; Yunfei Xia; Chun Cheng; Hong Liu (Cell and Tissue Research, 2015)

Comparison of bacterial community structures of terrestrial cyanobacterium Nostoc flagelliforme in three different regions of China using PCR-DGGE analysis - Pei-pei Han; Shi-gang Shen; Shi-ru Jia; Hui-yan Wang; Cheng Zhong; Zhi-lei Tan; He-xin Lv (World Journal of Microbiology and Biotechnology, 2015)

Longikaurin E induces apoptosis of pancreatic cancer cells via modulation of the p38 and PI3K/AKT pathways by ROS - Hai-bo Cheng; Yun Bo; Wei-xing Shen; Xian-guo Ren; Jia-ni Tan; Zhi-rong Jia; Chang-Liang Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Sec Pathway Influences the Growth of Deinococcus radiodurans - Liangyan Wang; Hongmei Tan; Kaiying Cheng; Mingfeng Li; Xin Xu; Jing Wang; Yuejin Hua (Current Microbiology, 2015)

Detection and attribution of vegetation greening trend in China over the last 30 years - Shilong Piao; Guodong Yin; Jianguang Tan; Lei Cheng; Mengtian Huang; Yue Li; Ronggao Liu; Jiafu Mao; Ranga B. Myneni; Shushi Peng; Ben Poulter; Xiaoying Shi; et al. (Global Change Biology, 2015)
The reliable detection and attribution of changes in vegetation growth is a prerequisite for the development of strategies for the sustainable management of ecosystems. This is an extraordinary challenge. To our knowledge, this study is the first to comprehensively detect and attribute a greening trend in China over the last three decades. We use three different satellite‐derived Leaf Area Index ( LAI ) datasets for detection as well as five different process‐based ecosystem models for attribution. Rising atmospheric CO 2 concentration and nitrogen deposition are identified as the most likely causes of the greening trend in China, explaining 85% and 41% of the average growing‐season LAI trend ( LAI GS ) estimated by satellite datasets (average trend of 0.0070 yr −1 , ranging from 0.0035 yr −1 to 0.0127 yr −1 ), respectively. The contribution of nitrogen deposition is more clearly seen in southern China than in the north of the country. Models disagree about the contribution of climate change alone to the trend in LAI GS at the country scale (one model shows a significant increasing trend, whereas two others show significant decreasing trends). However, the models generally agree on the negative impacts of climate change in north China and Inner Mongolia and the positive impact in the Qinghai–Xizang plateau. Provincial forest area change tends to be significantly correlated with the trend of LAI GS ( P P = 0.07) correlated with the residual of LAI GS trend, calculated as the trend observed by satellite minus that estimated by models through considering the effects of climate change, rising CO 2 concentration and nitrogen deposition, across different provinces. This result highlights the important role of China's afforestation program in explaining the spatial patterns of trend in vegetation growth.

Cloning of a caffeoyl-coenzyme A O-methyltransferase from Camellia sinensis and analysis of its catalytic activity - Yue Zhang; Hai-peng Lv; Cheng-ying Ma; Li Guo; Jun-feng Tan; Qun-hua Peng; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Effects of metal cations and fulvic acid on the adsorption of ciprofloxacin onto goethite - Yinyue Tan; Yong Guo; Xueyuan Gu; Cheng Gu (Environmental Science and Pollution Research, 2015)

Using enriched stable isotope technique to study Cu bioaccumulation and bioavailability in Corbicula fluminea from Taihu Lake, China - Wenhong Fan; Jinqian Ren; Chenguang Wu; Cheng Tan; Xiaolong Wang; Minming Cui; Kuang Wu; Xiaomin Li (Environmental Science and Pollution Research, 2014)

Toll-like receptor 3 inhibits Newcastle disease virus replication through activation of pro-inflammatory cytokines and the type-1 interferon pathway - Jinghua Cheng; Yingjie Sun; Xiaorong Zhang; Fanqing Zhang; Shilei Zhang; Shengqing Yu; Xusheng Qiu; Lei Tan; Cuiping Song; Song Gao; Yantao Wu; Chan Ding (Archives of Virology, 2014)

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

Metabolomic approach to optimizing and evaluating antibiotic treatment in the axenic culture of cyanobacterium Nostoc flagelliforme - Pei-pei Han; Shi-ru Jia; Ying Sun; Zhi-lei Tan; Cheng Zhong; Yu-jie Dai; Ning Tan; Shi-gang Shen (World Journal of Microbiology and Biotechnology, 2014)

Albino midrib 1, encoding a putative potassium efflux antiporter, affects chloroplast development and drought tolerance in rice - Peike Sheng; Junjie Tan; Mingna Jin; Fuqing Wu; Kunneng Zhou; Weiwei Ma; Yueqin Heng; Jiulin Wang; Xiuping Guo; Xin Zhang; Zhijun Cheng; Linglong Liu; et al. (Plant Cell Reports, 2014)

Highly sensitive electrochemiluminescence biosensors for cholesterol detection based on mesoporous magnetic core–shell microspheres - Juanjuan Zhang; Shihong Chen; Xingrong Tan; Xia Zhong; Dehua Yuan; Yinfeng Cheng (Biotechnology Letters, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Two new bufadienolides from the rhizomes of Helleborus thibetanus with inhibitory activities against prostate cancer cells - Wei Cheng; Ya-Fang Tan; Hai-Yan Tian; Xiang-Wen Gong; Ke-Li Chen; Ren-Wang Jiang (Natural Product Research, 2014)

Betanin attenuates carbon tetrachloride (CCl4)-induced liver injury in common carp (Cyprinus carpio L.) - Junyan Han; Cheng Gao; Shaobin Yang; Jun Wang; Dehong Tan (Fish Physiology and Biochemistry, 2014)

Effect of age on the pathogenesis of DHV-1 in Pekin ducks and on the innate immune responses of ducks to infection - Cuiping Song; Shengqing Yu; Yunbing Duan; Yue Hu; Xvsheng Qiu; Lei Tan; Yingjie Sun; Mingshu Wang; Anchun Cheng; Chan Ding (Archives of Virology, 2014)

Gene expression divergence between malaria vector sibling species Anopheles gambiae and An. coluzzii from rural and urban Yaoundé Cameroon - Bryan J. Cassone; Colince Kamdem; Changde Cheng; John C. Tan; Matthew W. Hahn; Carlo Costantini; Nora J. Besansky (Molecular Ecology, 2014)
Divergent selection based on aquatic larval ecology is a likely factor in the recent isolation of two broadly sympatric and morphologically identical African mosquito species, the malaria vectors Anopheles gambiae and An. coluzzii . Population‐based genome scans have revealed numerous candidate regions of recent positive selection, but have provided few clues as to the genetic mechanisms underlying behavioural and physiological divergence between the two species, phenotypes which themselves remain obscure. To uncover possible genetic mechanisms, we compared global transcriptional profiles of natural and experimental populations using gene‐based microarrays. Larvae were sampled as second and fourth instars from natural populations in and around the city of Yaoundé, capital of Cameroon, where the two species segregate along a gradient of urbanization. Functional enrichment analysis of differentially expressed genes revealed that An. coluzzii – the species that breeds in more stable, biotically complex and potentially polluted urban water bodies – overexpresses genes implicated in detoxification and immunity relative to An. gambiae, which breeds in more ephemeral and relatively depauperate pools and puddles in suburbs and rural areas. Moreover, our data suggest that such overexpression by An. coluzzii is not a transient result of induction by xenobiotics in the larval habitat, but an inherent and presumably adaptive response to repeatedly encountered environmental stressors. Finally, we find no significant overlap between the differentially expressed loci and previously identified genomic regions of recent positive selection, suggesting that transcriptome divergence is regulated by trans‐acting factors rather than cis‐acting elements.

Iron and zinc binding activity of Escherichia coli topoisomerase I homolog YrdD - Zishuo Cheng; Guoqiang Tan; Wu Wang; Xiaolu Su; Aaron P. Landry; Jianxin Lu; Huangen Ding (BioMetals, 2014)

Rhodamine B induces long nucleoplasmic bridges and other nuclear anomalies in Allium cepa root tip cells - Dehong Tan; Bing Bai; Donghua Jiang; Lin Shi; Shunchang Cheng; Dongbing Tao; Shujuan Ji (Environmental Science and Pollution Research, 2014)

Coupling typhoon rainfall forecasting with overland-flow modeling for early warning of inundation - Tsung-Yi Pan; Lung-Yao Chang; Jihn-Sung Lai; Hsiang-Kuan Chang; Cheng-Shang Lee; Yih-Chi Tan (Natural Hazards, 2014)

Cyclic AMP-Dependent Protein Kinase Enhances SC35-Promoted Tau Exon 10 Inclusion - Caoyi Chen; Nana Jin; Wei Qian; Wen Liu; Xiangling Tan; Fei Ding; Xiaosong Gu; Khalid Iqbal; Cheng-Xin Gong; Ji Zuo; Fei Liu (Molecular Neurobiology, 2014)

Wnt/β-catenin signaling mediates the senescence of bone marrow-mesenchymal stem cells from systemic lupus erythematosus patients through the p53/p21 pathway - Zhifeng Gu; Wei Tan; Guijuan Feng; Yan Meng; Biyu Shen; Hong Liu; Chun Cheng (Molecular and Cellular Biochemistry, 2014)

Effect of a single-dose rifampin on the pharmacokinetics of pitavastatin in healthy volunteers - Yao Chen; Wei Zhang; Wei-hua Huang; Zhi-rong Tan; Yi-cheng Wang; Xi Huang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

Quantitative trait loci mapping for yield components and kernel-related traits in multiple connected RIL populations in maize - Chunhui Li; Yongxiang Li; Baocheng Sun; Bo Peng; Cheng Liu; Zhizhai Liu; Zhaozhao Yang; Qingchao Li; Weiwei Tan; Yan Zhang; Di Wang; Yunsu Shi; et al. (Euphytica, 2013)

Identification of Regulatory Relationships in Parkinson's Disease - Hao Wang; Cheng Sun; Yusi Liang; Heying Zhang; Yonggang Tan (Journal of Molecular Neuroscience, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Correlations and comparisons of quantitative trait loci with family per se and testcross performance for grain yield and related traits in maize - Bo Peng; Yongxiang Li; Yang Wang; Cheng Liu; Zhizhai Liu; Yan Zhang; Weiwei Tan; Di Wang; Yunsu Shi; Baocheng Sun; Yanchun Song; Tianyu Wang; et al. (Theoretical and Applied Genetics, 2013)

Use of a bovine genome chip to identify new biological pathways for beef quality in cattle - Liu Guifen; Liu Xiaomu; Wan Fachun; Tan Xiuwen; Cheng Haijian; Song Enliang (Molecular Biology Reports, 2012)

Whole-body vibration and resistance exercise prevent long-term hindlimb unloading-induced bone loss: independent and interactive effects - Zhili Li; Cheng Tan; Yonghua Wu; Ye Ding; Huijuan Wang; Wenjuan Chen; Yu Zhu; Honglei Ma; Honghui Yang; Wenbin Liang; Shizhong Jiang; Desheng Wang; et al. (European Journal of Applied Physiology, 2012)

Usefulness of Speckle Tracking Imaging to Assess Myocardial Contractility in Intra-Abdominal Hypertension: Study in a Mini-Pig Model - Wen-Hua Du; Wang Xiang; Dao-Cheng Liu; Lian-Yang Zhang; Tao Li; Shi-Jin Sun; Hao Tan (Cell Biochemistry and Biophysics, 2012)

Closed Solutions for Transient Heat Transport in Geological Media: New Development, Comparisons, and Validations - Haochen Tan; Xiaohui Cheng; Hongxian Guo (Transport in Porous Media, 2012)

Synthesis, structure, and biological activity of novel (oxdi/tri)azoles derivatives containing 1,2,3-thiadiazole or methyl moiety - Xing-Hai Liu; Li Pan; Jian-Quan Weng; Cheng-Xia Tan; Yong-Hong Li; Bao-Lei Wang; Zheng-Ming Li (Molecular Diversity, 2012)

Identification of valid housekeeping genes for quantitative RT-PCR analysis of cardiosphere-derived cells preconditioned under hypoxia or with prolyl-4-hydroxylase inhibitors - Suat Cheng Tan; Carolyn A. Carr; Kar Kheng Yeoh; Christopher J. Schofield; Kay E. Davies; Kieran Clarke (Molecular Biology Reports, 2012)

Protective effects of 7-difluoromethyl-5,4′-dimethoxygenistein against human aorta endothelial injury caused by lysophosphatidyl choline - Fei Liu; Jian-Guo Cao; Cheng Li; Jin-Seng Tan; Xiao-Hua Fu (Molecular and Cellular Biochemistry, 2012)

Establishment of a transgenic mouse model with liver-specific expression of secretory immunoglobulin D - Ping Wang; ZhiGuo Wei; BoWen Yan; Tan Huang; KeMian Gou; YunPing Dai; Min Zheng; MeiLi Wang; XueQian Cheng; XiFeng Wang; Chen Xu; Yi Sun (Science China Life Sciences, 2012)

Successful vitrification of mouse ovaries using less-concentrated cryoprotectants with Supercool X-1000 supplementation - Xiuwen Tan; Enliang Song; Xiaomu Liu; Guifen Liu; Haijian Cheng; Fachun Wan (In Vitro Cellular & Developmental Biology - Animal, 2012)

Characteristics and evolution of the PUF gene family in Bombyx mori and 27 other species - Chun-Dong Zhang; Min-Hui Pan; Juan Tan; Fang-Fang Li; Jun Zhang; Ting-Ting Wang; Cheng Lu (Molecular Biology Reports, 2012)

A preliminary study on the molecular evolution of the two routes of intrauterine transmission of HBV - H. Sun; X. Tang; B. Wang; J. Zhang; H. Cheng; H. Su; F. Li; K. Men; S. Wang; L. Zhao; J. Xu; X. Yu; et al. (Archives of Virology, 2012)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Divergent transcriptional response to thermal stress by Anopheles gambiae larvae carrying alternative arrangements of inversion 2La - BRYAN J. CASSONE; MATTHEW J. MOLLOY; CHANGDE CHENG; JOHN C. TAN; MATTHEW W. HAHN; NORA J. BESANSKY (Molecular Ecology, 2011)
The African malaria mosquito Anopheles gambiae is polymorphic for chromosomal inversion 2La, whose frequency strongly correlates with degree of aridity across environmental gradients. Recent physiological studies have associated 2La with resistance to desiccation in adults and thermal stress in larvae, consistent with its proposed role in aridity tolerance. However, the genetic basis of these traits remains unknown. To identify genes that could be involved in the differential response to thermal stress, we compared global gene expression profiles of heat‐hardened 2La or 2L+ a larvae at three time points, for up to eight hours following exposure to the heat stress. Treatment and control time series, replicated four times, revealed a common and massive induction of a core set of heat‐shock genes regardless of 2La orientation. However, clear differences between the 2La and 2L+ a arrangements emerged at the earliest (0.25 h) time point, in the intensity and nature of the stress response. Overall, 2La was associated with the more aggressive response: larger numbers of genes were heat responsive and up‐regulated. Transcriptionally induced genes were enriched for functions related to ubiquitin‐proteasomal degradation, chaperoning and energy metabolism. The more muted transcriptional response of 2L+ a was largely repressive, including genes involved in proteolysis and energy metabolism. These results may help explain the maintenance of the 2La inversion polymorphism in An. gambiae , as the survival benefits offered by high thermal sensitivity in harsh climates could be offset by the metabolic costs of such a drastic response in more equable climates.

QTL analysis for yield components and kernel-related traits in maize across multi-environments - Bo Peng; Yongxiang Li; Yang Wang; Cheng Liu; Zhizhai Liu; Weiwei Tan; Yan Zhang; Di Wang; Yunsu Shi; Baocheng Sun; Yanchun Song; Tianyu Wang; et al. (Theoretical and Applied Genetics, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Cu(II): a “signaling molecule” of the mangrove endophyte Fusarium oxysporum ZZF51? - Jia-hui Pan; Yong-cheng Lin; Ni Tan; Yu-cheng Gu (BioMetals, 2010)

Proteomic analysis of differentially expressed proteins in mice with concanavalin A-induced hepatitis - Xu-fei Tan; Feng Chen; Shan-shan Wu; Yu Shi; Dong-cheng Liu; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2010)

An optimal water allocation for an irrigation district in Pingtung County, Taiwan - Yun Cheng; Cheng‐Haw Lee; Yih‐Chi Tan; Hsin‐Fu Yeh (Irrigation and Drainage, 2009)
This paper presents a linear programming model to study the conjunctive use of surface water and groundwater for optimal water allocation in Taiwan. Increasing demand for water emphasizes the proper need for effective planning and development of irrigated resources. A groundwater simulation model was performed to construct the hydrogeological structure of the regional Pingtung Plain in the southwest part of Taiwan and the optimal withdrawal of three irrigation areas in Pingtung Plain was analysed. The optimal ratios for allocating water of three canals are analysed in this research. The optimal distribution rate of each canal depends on the season, irrigation methods and crops, which are two paddy rice and one upland crop. After simulation of various scenarios, optimal simulation results show that the minimal amount of required groundwater and the maximum amount of excess water amounts in the area can be satisfied by current agricultural practices. Copyright © 2008 John Wiley & Sons, Ltd.

Bioactive compounds of inhibiting xanthine oxidase from Selaginella labordei - Wen-Jie Tan; Jia-Cheng Xu; Li Li; Ke-Li Chen (Natural Product Research, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

Expression of β-carotene hydroxylase gene (crtR-B) from the green alga Haematococcus pluvialis in chloroplasts of Chlamydomonas reinhardtii - Cong-Ping Tan; Fang-Qing Zhao; Zhong-Liang Su; Cheng-Wei Liang; Song Qin (Journal of Applied Phycology, 2007)

Effects of biological soil crusts on emergence of desert vascular plants in North China - Yan-Gui Su; Xin-Rong Li; Ying-Wu Cheng; Hui-Juan Tan; Rong-Liang Jia (Plant Ecology, 2007)

Antimicrobial potentials of endophytic fungi residing in Quercus variabilis and brefeldin A obtained from Cladosporium sp. - F. W. Wang; R. H. Jiao; A. B. Cheng; S. H. Tan; Y. C. Song (World Journal of Microbiology and Biotechnology, 2007)

Effects of species and cellular activity of oviductal epithelial cells on their dialogue with co-cultured mouse embryos - Xiu-Wen Tan; Suo-Feng Ma; Jian-Ning Yu; Xia Zhang; Guo-Cheng Lan; Xin-Yong Liu; Zheng-Bin Han; Jing-He Tan (Cell and Tissue Research, 2006)

Effect of Nutritional Parameters on Laccase Production by the Culinary and Medicinal Mushroom, Grifola frondosa - Z. T. Xing; J. H. Cheng; Q. Tan; Y. J. Pan (World Journal of Microbiology and Biotechnology, 2006)

Effect of nutritional parameters on laccase production by the culinary and medicinal mushroom, Grifola frondosa - Z.T. Xing; J.H. Cheng; Q. Tan; Y.J. Pan (World Journal of Microbiology and Biotechnology, 2006)

Molecular Cloning, Characterization and Evolutionary Analysis of Phytoene Desaturase (PDS) Gene from Haematococcus pluvialis - Cheng W. Liang; Fang Q. Zhao; Chun X. Meng; Cong P. Tan; Song Qin (World Journal of Microbiology and Biotechnology, 2006)

Endonuclease-like activity of heme proteins - Willy B. Tan; Wunhuey Cheng; Andrew Webber; Akhilesh Bhambhani; Michael R. Duff; Challa V. Kumar; George L. McLendon (JBIC Journal of Biological Inorganic Chemistry, 2005)

Determination of the magnitudes and values for groundwater recharge from Taiwan's paddy field - Chen-Wuing Liu; Chih-Huang Tan; Cheng-Chang Huang (Paddy and Water Environment, 2005)

Dechlorination by combined electrochemical reduction and oxidation - Yan-qing Cong; Zu-cheng Wu; Tian-en Tan (Journal of Zhejiang University-SCIENCE B, 2005)

Classification of cryosols: Significance, achievements and challenges - Jie Chen; Zi-tong Gong; Zhi-cheng Chen; Man-zhi Tan (Chinese Geographical Science, 2003)